Polygonatum cyrtonema polysaccharide-based emulsion coating for postharvest preservation of satsuma mandarin and the underlying dual omics mechanisms - Yan Shi; Chenyu Wang; Lei Huo; Yihan Wang; Pan Wang; Miaomiao Yao; Jinping Si; Huqing Yang; Wanying Ge (Postharvest Biology and Technology, 2027)

A machine learning-based dual system coupling model of catalytic-gasification: a calcium-based case study with mechanistic interpretability - Yadong Ge; HongRu Li; Zaixin Li; Zhi Wang; Xiaoqiang Cui; Beibei Yan; Junyu Tao; Zhanjun Cheng; Ningbo Gao (Bioresource Technology, 2027)

Piperazine derivatives monomer-based TFC nanofiltration membranes with enhanced mineral/organic selectivity for efficient surface water purification - Xuewu Zhu; Xiaowen Zhang; Xiangfeng Jia; Yixuan Li; Wenxin Yan; Feiyue Ge; Feilong Zhang; Xinwei Kang; Yongshan Ma; Daliang Xu (Desalination, 2026)

Mechanistic Insights into LGALS3-Mediated Osteoarthritis Progression: Activation of the cGAS-STING Pathway as a Key Driver of Senescence-Related Osteoarthritis - Ruolan Wu; Tong Xiao; Zhen Chen; Qitao Yan; Ying Wang; Dingwei Peng; Jingli Chen; Ge Zeng (Journal of Pharmaceutical Innovation, 2026)

Root accumulation and efficient translocation of steroids in mangrove plants: Implications for an overlooked coastal reservoir - Ji-Xun Chen; Nian-Nian Wu; Shan Liu; Yuan Liu; Qin-Ge Zhou; Qing-Song Yang; Juan Ling; Xiao-Fang Huang; Yan-Kuan Tian; Chang-Gui Pan; Xiang-Rong Xu (Marine Pollution Bulletin, 2026)

Precise H2 supply enables quantitative control of on-demand deep nitrate removal while preserving denitrification completeness - Ge Yan; Zhen-Xiang Jiang; Jia-Le Wu; Ting Wang; Jun-Tong Hu; Li-Wen Qiu; Chen Zhou; Hongqiang Ren (Water Research, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Constraints on Paleo-Pacific Plate rollback from magmatic spatiotemporal evolution, isotopic composition variations, and crustal thickness changes: Insights from Early Cretaceous adakitic granitoids in the northeastern Asian continental margin - Xinping Li; Yu Dong; Wenchun Ge; Simiao Wang; Junhui Bi; Hao Yang; Jie Tang; Hongying Zhou; Yan Jing; Guochun Zhao (Lithos, 2026)

Numerical simulation of thermal-hydraulic-chemical multi-physical field coupling for large-scale experimental models of CO2 hydrate sequestration - Lei Wang; Xianjie Yan; Yang Ge; Ruirui Li; Zhaoran Wu; Jinyan Lan; Jiefeng Liu (Fuel, 2026)

Morphology-dependent transport of atmospheric microplastics and the indicator role of polyester fibers across the estuarine- offshore gradient - Fei Jiang; Yan Yang; Pingang Wei; Xuanzheng Wang; Yuang Liu; Xinyue Tang; Zhenming Ge; Dan Zhang; Qiqing Chen (Environmental Pollution, 2026)

A compact isolator for multi-directionally coupled vibration - Mingzhu Jin; Ge Yan; Xiang Yu; Xiuhui Hou; Zichen Deng; Li Cheng (Engineering Structures, 2026)

Bipyridine-based covalent organic framework for trace-level nanofluidic detection of chlorobenzoquinone - Xu-Qin Ran; Xin-Ge Cai; Xiao-Jiao Ren; Xiu-Ping Yan; Hai-Long Qian (Chemical Engineering Journal, 2026)

Urbanization drives rapid convergence of riverine greenhouse gas levels in the urban agglomeration, North China - Ling Wen; Zhengkui Ge; Yulin Qi; Dietrich A. Volmer; Chao Ma; Chunmei Chen; Zhifeng Yan; Pingqing Fu; Si-Liang Li (Agriculture, Ecosystems & Environment, 2026)

An integrated pump-suction electrocoagulation system for accelerated hardness removal: Process intensification and crystallization mechanisms - Yunxian Liu; Yuexin Chang; Xu Liu; Wei Yan; Min-ge Tian; Hao Xu (Water Research, 2026)

Fine-scale mapping of urban evergreen and deciduous forests with high-resolution JL-1 multispectral satellite images using a weakly supervised deep neural network model - Yuan Zhang; Chentian Ge; Wenjia Yan; Guilian Zhang; Zhekui Fan; Chao Zhang (Urban Forestry & Urban Greening, 2026)

A novel mycotoxin-degrading enzyme complex alleviates the combined toxicity of AFB1, DON, and ZEN in laying hens - Yan-Qi Ning; Yu Zhang; Yu-Hao Ge; Li-Jia Guo; Wen-Jie Yang; Lv-Hui Sun; Yu-Xuan Huang (Toxicon, 2026)

Systematic review of naturally occurring benzylisoquinoline alkaloids (2015–2024): phytochemistry, bioactivity and structure-activity relationship - Jing Liu; Tao Liu; Mu-Yan Liu; Hui-Hui Li; Xiao-Yu Zhao; Hui Zhang; Yan Ge; Ze-Dong Nan (Phytochemistry, 2026)

Bench-scale proof-of-concept evaluation of whole-cell quorum quenching for fouling mitigation in a constant-flux membrane bioreactor. - Jiale Han; Xiaohui Chen; Xiaoyu Wang; Zimiao Yan; Xinjiao Dong; Yaru Li; Chenjie Mei; Shimei Ge (Journal of Water Process Engineering, 2026)

Interfacial polymerization for sustainable microencapsulation: Bio-based core/shell design, mechanistic principles, and emerging applications - Limin Gu; Xueqing Qin; Ziyan Ren; Yan Su; Shuai Li; Linya Zhang; Yanrui Ge; Fengxia Sun (Journal of Environmental Chemical Engineering, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Coal seams respond to astronomical forcing climate from a tidal-influenced to river-dominated deltaic environment: Insights from the late Eocene Xihu Sag, the East China Sea Shelf Basin - Xian Liu; Jiawang Ge; Xiaoming Zhao; Xuesong Zhou; Guofeng Yin; Shumei Yan; Brian G. Jones (Journal of Asian Earth Sciences, 2026)

Dual-swirl micro-combustor for enhanced overall micro thermophotovoltaic system performance: optimizing temperature uniformity and system efficiency - Yonghong Wu; Yunfei Yan; Chenghua Zhang; Chang Liu; Junzhe Huang; Ge Pu; Xuelin Zhao (Fuel, 2026)

Comparative Lipidomics and microstructural characterization of Milk fat globule membrane protein powders from bovine buttermilk and cheese whey - Kuolin Si; Mengxueyao Zhang; Xuexing Zong; Yin Pei; Lu Liu; Xiuxiu Zhang; Meiling Ge; Xiaodong Li; Qingquan Yan (Food Research International, 2026)

Ultrasound-assisted three-phase partitioning produces a pectin-leaning polysaccharide fraction from Idesia polycarpa Maxim cake meal with stable rheology and prebiotic-like potential - Yuanfu Zhang; Wenlin Zhang; Xin Shi; Longfeng Tan; Zhiyou Zhao; Yan Hu; Renshuai Huang; Yonghui Ge; Kewei Chen; Guangjing Chen (Food Chemistry, 2026)

A systematic review of emerging pretreatments, drying technologies, and artificial intelligence applied in processing blueberry - Qiao-Yi Ma; Yan Ge; Magdalena Zielinska; Jia-Xuan Shu; Shan-Yu Wang; Xiaojun Huang; Zi-Liang Liu (Food Control, 2026)

Regional patterns and drivers of 15N fertilizer fate across China’s wheat systems: Integrating meta-analysis and machine learning - Yan’ge Yan; Shuiqin Zhang; Yingqiang Zhang; Meng Xu; Jiukai Xu; Yanting Li; Bingqiang Zhao; Liang Yuan (Field Crops Research, 2026)

Climate and soil properties drive microplastic enrichment patterns in agricultural soils across a multi-country survey - Martine Graf; Michaela K. Reay; Yingming Sun; Fan Ding; Siyang Ren; Kai Wang; Changrong Yan; Shitong Li; Tida Ge; Xuejun Liu; Ruimin Qi; Jixiao Cui; et al. (Environmental Pollution, 2026)

A novel Chaphamaparvovirus detected in breeding Muscovy Ducks with hepatitis - Yadong Gao; Jiawen Dong; Ouyang Peng; Zhuanqiang Yan; Meiting Chen; Yingshan Yin; Minhua Sun; Junqin Zhang; Yunzhen Huang; Yong Xiang; Zhai Qi; Junwei Ge; et al. (Veterinary Research Communications, 2026)

Transient Trim25 Knockdown Enhances Transfection Efficiency in Two Teleost Fish Cell Lines - Yajun Wang; Xiaohuan Ge; Tiange Guo; Mengda Du; Yan He (Marine Biotechnology, 2026)

A robust HPLC-HILIC enrichment system for O-glycoproteomics profiling of plasma and cerebrospinal fluid across Alzheimer's disease progression - Zhenpeng Deng; Yan Wang; Lei Liu; Xin Guo; Haiyang Zhu; Mingming Dong; Yusong Ge; Yongliang Yu; Mingliang Ye (Analytica Chimica Acta, 2026)

‘From growth monitoring to berry quality prediction: Advances and challenges in UAV remote sensing for precision viticulture - Jinyu Yang; Mengyuan Wei; Qifan Chen; Tingting Ma; Qian Ge; Yue Yan; Jiming Li; Baofeng Su; Yulin Fang; Xiangyu Sun (Computers and Electronics in Agriculture, 2026)

Construction of chemical looping gasification model based on machine learning: focusing on performance prediction, feature importance and parameter optimization - Juan Zhao; Mohan Yang; Yadong Ge; Zhi Wang; Beibei Yan; Jianwu Zhang (Waste Management, 2026)

1-Methylcyclopropene regulates ethylene and polyamine metabolism of fig fruit during cold storage - Jingyi Lv; Xin Sun; Sijie Dong; Siqi Yan; Yonghong Ge; Jianrong Li (Postharvest Biology and Technology, 2026)

BrAKT1 overexpression enhances clubroot susceptibility through dysregulation of host physiological processes in pak choi - Samiah Arif; Yǔmeng Yan; Yufan Ge; Muhammad Sanaullah Malik; Ping Li; Saeed ur Rahman; Yidong Zhang (Physiological and Molecular Plant Pathology, 2026)

Integrating emergy accounting with ecosystem-based coastal defence: An eco-coastal engineering framework for sustainability assessment of hybrid infrastructure - Junxue Zhang; Moran Yu; Hairuo Wang; Yan Gong; Haobing Wang; Xiaoting Zhai; Ashish T. Asutosh; Yingnan Li; Ge Song; Weidong Wu; Ziyi Men; Minghui Yang; et al. (Ocean Engineering, 2026)

Arc-continent collision between the Bainaimiao intra-oceanic arc and the North China Craton facilitated the Late Ordovician climatic cooling and glaciation - Yan Jing; Wen-chun Ge; Hao Yang; Yu Dong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Molecular to tissue-level perspective: Evaluating the toxicity and ecological risk of fluopyram to Eisenia fetida - Shuang Liu; Yannan Xue; Yan Ge; Guohao Huang; Jinhua Wang; Xiaoming Xia (Journal of Hazardous Materials, 2026)

A multifunctional hybrid delivery system of sodium alginate-based nanoparticles-hydrogel beads “double fence” effect for pea peptide - Guocong Ma; Mingwu Qiao; Dan Hai; Yan Ma; Ge Bai; Peijun Zhao; Xianqing Huang; Xinyu Sun; Lianjun Song (Food Chemistry, 2026)

Investigating Microbial Communities and Metabolic Dynamics in Jiupei from Cellars of Different Ages: An Integrated Amplicon and Metabolomic Analysis of Mianrou-Style Baijiu - Longyun Zhang; Chun Pu; Congzhi Zhang; Fengxue Guo; Jiaojiao Song; Xiangyang Ge; Yan Xu (Food Bioscience, 2026)

Heterologous expression and functional characterization of Bacillus subtilis natto MenA in Escherichia coli and its role in Vitamin K2 Biosynthesis - Said Nawab; Chuanchao Wu; Zhangbing Ge; Wei Tao; Yuqi Li; Yuexin Ma; Yaqing Zhao; Jie Song; Yi-Feng Jiang; Yan Liu (Food Bioscience, 2026)

Mitigating the deterioration of quality in frozen rice dough: effects of carboxymethyl chitosan across different freezing methods - Wangming Dong; Yan Wu; Jing Xie; Ting Hu; Ge Zhang; Qi Wei (Food Hydrocolloids, 2026)

Associations of Placental Oxidative Stress with Exposure to Gestational Air Pollution: Evidence from the UPSIDE Cohort - Emily A. Craig; Yan Lin; Yihui Ge; Xiangtian Wang; Otgondelger Enkhtaivan; Don K. Harrington; Richard K. Miller; Susan K. Murphy; Sally W. Thurston; Philip K. Hopke; Emily S. Barrett; Thomas G. O'Connor; et al. (Environmental Research, 2026)

Hypermobility induced by extensive grain fragmentation: Insights from the 1991 Touzhai rock avalanche - Yan Li; Wei Hu; Yi Ge; Heng Liang; Mauri McSaveney (Earth and Planetary Science Letters, 2026)

Solvent-gradient coordination design of LiNO3-based electrolytes for anode-free lithium metal batteries - Shifei Huang; Yuan Liu; Yao Lv; Guohuang Kang; Jiang Xu; Jia Cui; Yufeng Zhao; Wei Yan; Jiujun Zhang; Shanhai Ge (Chemical Engineering Journal, 2026)

The development of a constitutive promoter library for Cupriavidus necator to produce polyketides - Ziqi Jin; Xu Yan; Fang Yang; Ge Zhang; Guo-Qiang Chen (Chemical Engineering Journal, 2026)

ER stress promoted MAMs formation and ER-Mito Ca2+ transfer: implication for fluoride-induced hippocampal neuronal injury and cognitive deficits in mice - Siman Lin; LuYang Cao; Yuzhe Zhou; Shengdan Liu; Yue Yan; Qiwei Zhang; Quan Yuan; Yufei Gao; Ge Du; Jun Hu; Dongmei Wang; Hua Fan (Chemico-Biological Interactions, 2026)

Investigation of changes in microbial communities and metabolites for the nutrient re-utilization of fermented agricultural wastes in watermelon - Tong-Lu Wei; Yan-Ge Li; Mao-Song Pei; Hai-Nan Liu; Xue-Jie Zhu; Zhong-Hou Zhu; Da-Long Guo (Biomass and Bioenergy, 2026)

Risk factors for polymicrobial klebsiella pneumoniae bloodstream infection: a retrospective cohort study using the antimicrobial resistance monitoring database - Huian Ge; Jianhao Su; Gaoxiang Xu; Yanan Li; Zhikang Xiao; Jiaqing Yan; Yigeng Peng; Jianzhong Xu; Chen Qiu; Ri Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

Untargeted UHPLC-MS/MS metabolomic profiling reveals organ-specific accumulation of metabolites in Gerbera piloselloides (L.) Cass - Yan Li; Juan Xue; Yongjia Shu; Ge Liu; Huifang Chai (Natural Product Research, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

TMK1-mediated phosphorylation and destabilization of DA1 connects auxin signaling with seed size control in Arabidopsis - Anbin Wang; Leiying Zheng; Xindong Zhang; Weicheng Yang; Shichuang Yan; Wenyan Zhao; Li Yan; Tinghui Ge; Zhihai Chi; Xiahe Huang; Yongqiang Yu; Gang Gao; et al. (Molecular Plant, 2026)

Accelerated degradation of antiviral ribavirin by microalgae fuel cell (MFC), electricity generation and key metabolic process - Junhao Wang; Xinrui Qin; Jiajia Ge; Yongtao Cheng; Kang Li; Jun Liu; Kang Shan; Chuanyue Peng; Wenjing Yan; Juan Wang; Min Zuo; Ying Liu (Journal of Environmental Chemical Engineering, 2026)

Amylose content as a key factor in composite dough functionality and steamed bun quality: A multi-scale study on non-waxy and waxy broomcorn millet - Xinyao Yan; Xuechun Tian; Ge Fang; Zhanat Bauyrzhankyzy Duisembi; Le Du; Shaohui Ouyang (Journal of Cereal Science, 2026)

Quality grading of raw goat milk and microbiota-driven quality degradation during storage at 4°C and 10°C - Mengyuan Cao; Min Li; Yizhuo Yan; Yifan Wu; Li Su; Jinghan Dai; Cong Wang; Xin Lv; Yan Zhang; Wupeng Ge; Baowei Yang (International Dairy Journal, 2026)

The dual role of H2 in a hydrogen-rich atmosphere: mechanisms of coke dissolution loss inhibition and strength enhancement - Jialong Yao; An Li; Rong Ge; Jingchong Yan; Zhanku Li; Weidong Zhang; Zhicai Wang; Zhiping Lei; Shibiao Ren; Hengfu Shui (Fuel, 2026)

Co-evolution of the pangenome, mobile genetic elements, and antimicrobial resistance genes reveals the public health risks of the dominant Salmonella 4,[5],12:i:- ST34 clone - Jiawen Chen; Shuaicheng Wu; Laiyu Fu; Yan Li; Xiaoxiao Duan; Yanling Liu; Yichi Zhang; Xindong Ge; Yongda Zhao; Lili Guo (Food Research International, 2026)

Exploring the endogenous and exogenous key aroma-active components in three aroma types of black teas from different cultivars - Weixuan Li; Zhouling Zhong; Han Yan; Longyu Guo; Ge Chen; Zhi Lin; Haipeng Lv; Yue Zhang; Yin Zhu (Food Research International, 2026)

MgO-modified PtSn/Ce-DMSN as an efficient catalyst for oxidative dehydrogenation of propane with carbon dioxide - Chao Peng; Jiang Li; Han-Qing Ge; Meng Yan; Zhong-Wen Liu (Chemical Engineering Journal, 2026)

Unraveling the critical role of ClO• in the degradation of emerging organic contaminants by far-UVC/chlorine: Radical contribution assessment and influence of water matrix - Ping Li; Ge Zeng; Wenjun Zhang; Qiuling Lu; Haonan Lu; Kai Wang; Jun Ma; Yan Zhang; Tao Yang (Chemical Engineering Journal, 2026)

Association of Traditional and Novel Lipid Indicators With the Hemorrhagic Phenotype in Adult Moyamoya Disease: Implications for Phenotype Stratification - Weihong Huang; Haoyang Xiong; Wenjing Chen; Wei Liu; Peicong Ge; Yunhao Liu; Xuefeng Tang; Ziheng Yang; Zhongji Yan; Dong Zhang (Translational Stroke Research, 2026)

Advances in Alzheimer’s disease: mechanistic insights and therapeutic targets - Yu-Juan Jia; Yi-Jun Ge; Bowei Li; Ying Yang; Huaqiu Chen; Jie Liu; Jun-Hong Guo; Jin-Tai Yu; Ke-Qiang Ye; Jian-Zhi Wang; Weihong Song; Yan-Jiang Wang (Science China Life Sciences, 2026)

Primer-programmed circular template generation enables padlock-free rolling circle amplification for low-background CRISPR-based pathogen detection - Yemin Han; Haotian Yu; Manman Lv; Mengqing Cheng; Weihao Li; Houyang Ge; Song Gao; Lu Yin; Qinyu Ge; Xinping Xu; Yan Huang; Longhua Sun; et al. (Analytica Chimica Acta, 2026)

Regional flooding enhances N2O and CH4 emissions from agricultural fields: Evidence from a single extreme event across the North China Plain - Zhengkui Ge; Zhifeng Yan; Mike Peacock; Si-Liang Li; Xiaotang Ju; Pete Smith; Guirui Yu; Cong-Qiang Liu (Agricultural and Forest Meteorology, 2026)

Quercetin exerts radioprotective effects against radiation-induced intestinal injury with involvement of the PI3K-AKT/Caspase-3 axis - Qing Guo; Zhibing Tang; Zhenyu Hou; Ge Yan; Jiaxuan Wang; Man Zhang; Ruige Ma; Juan Wang; Qiong Feng; Zhen Wang; Chunlei Wang; Lin Zhao (Molecular and Cellular Biochemistry, 2026)

TRMT10A maintains lipid homeostasis independently of its tRNA m1G9 methyltransferase activity - Huihui Sun; Yu Wang; Shanpeng Liu; Yan Jin; Jianyang Ge; Bowen Zhang; Yongteng Wang; Weifeng Sun; Yun Bai; Yuyong Tao; Yi Lu; Ru-Juan Liu; et al. (Science China Life Sciences, 2026)

Intelligent Vessels Localization Based on Adaptive Correlation Information Filter Network in Complex Marine and Port Environments - Lei Yan; Wei Zeng; Zhixin Xia; Bo Meng; Junli Ge; Deming Kong (Journal of Marine Science and Engineering, 2026)
Accurate and robust localization is essential for intelligent vessels operating in complex marine and port environments. However, single-sensor localization is often affected by limited observation range, environmental occlusion, local interference, and sensor degradation. Although multi-sensor fusion can improve localization reliability, unknown cross-correlated measurement noise arising from shared disturbances, time synchronization errors, communication delays, and inconsistent fusion rates may degrade traditional information-filter-based fusion methods. To address this problem, this paper proposes an Adaptive Correlation Information Filter Network (ACIFNet) for multi-sensor fusion localization of intelligent vessels. ACIFNet preserves the recursive structure of the extended information filter and uses a Transformer-based network to learn adaptive information-domain fusion weights, thereby compensating for unknown inter-sensor correlations without explicitly estimating the full correlation covariance matrix. Experiments on constant-velocity, coordinated-turn (CV), and three-degree-of-freedom vessel motion models, together with a real-world restricted-waterway dataset, demonstrate that ACIFNet achieves higher localization accuracy and stability than Edge Incorporative Fusion (EIF)-inexact fusion, measurement fusion, and KalmanNet. In the CV and three-degree-of-freedom experiments, ACIFNet reduces the mean RMSE by 48.7%, 23.2%, and 26.1%, respectively, compared with KalmanNet. On the real-world dataset, ACIFNet achieves a mean position error of 9.90 m, an RMSE of 11.24 m, and a cross-track error of 8.72 m. These results show that ACIFNet effectively combines the interpretability of information filtering with the adaptive representation capability of neural networks for robust multi-sensor fusion localization under unknown cross-correlated measurement noises.

Unveiling the distance-to-shore gradient of construction land: shore spectrum analysis for sustainable management of Poyang Lake - Teng Ma; Wei Yan; Jiaheng Wang; Junfeng Ge; Hui Zou; Xuejun Duan (Environment, Development and Sustainability, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

PM2.5 exposure exacerbates cerebral infarction via HPG axis downregulation and pituitary lipid metabolism dysregulation in mice - Xin lv; Guanhui Pei; Lijuan Liu; Zhou zhou; Yicong Zhou; Binbin Wang; Chaoyue Meng; Ruomeng Chen; Qiang Yao; Ge Bai; Xuelin Wang; Minghan Zhao; et al. (NeuroToxicology, 2026)

Divergent soil microbial patterns despite similar TOC levels in Spartina alterniflora invasion and early-stage Scirpus mariqueter restoration - Wanli Hou; Hongdan Liu; Zhuangzhuang Xiang; Huikun Yan; Ge Li; Jie Bai (Estuarine, Coastal and Shelf Science, 2026)

Self-assembled thermoresponsive colloidal particles for smart windows and structural color ink displays - Die Yan; Yiyao Liu; Qi Feng; Boyu Zhao; Lili Yang; Dengteng Ge (Energy and Buildings, 2026)

Simulation of the shear fluidization behavior of high-water-content landslides using a two-phase dilatancy SPH model - Heng Liang; Wei Hu; Yi Ge; Yan Li (Engineering Geology, 2026)

Integrated physiological and molecular responses of Chlorella sorokiniana to high-sulfate starch processing wastewater: Balancing growth promotion and metabolic adaptation - Ruixin Yan; Shuang Qiu; Xiaofan Li; Ayesha Algade Amadu; Shijian Ge (Bioresource Technology, 2026)

A facile computational framework for predicting dynamic filtration performance of compressed coarse filter media using geometric compression and numerical simulation - Yuhai Yan; Junjie Zhang; Huimin Ge; Yunyan Chen; Zhibin Wang; Li Xi; Haibo Wu; Xiangyu Jin; Chen Huang; Yu Song (Building and Environment, 2026)

Stem Cell Therapy for Gestational Diabetes Mellitus: Opportunities and Gestational-Specific Dilemmas - Ge Wang; Yan Kang; Zhenya Fang; Xuan Yang (Stem Cell Reviews and Reports, 2026)

ATP-dependent binding cassette transporter ClABCI6 promotes the expression of citrus yellow vein clearing virus via inhibiting salicylic acid pathway - Yaqin Song; Wen Ge; Cuiyun Lei; Yijie Li; Yang Han; Jiedan Xiao; Xinghua Qiao; Shixue Hu; Yan Zhou; Binghai Lou (Journal of Plant Research, 2026)

Enhanced tropospheric delay retrieval using baseline-constrained multi-antenna shipborne GNSS with common ZTD parameter in the western Pacific - Zhitao Wang; Shuli Song; Maorong Ge; Yuze Yang; Zhifan Yan; Weili Zhou; Chao Huang; Xiangxiang He; Guoqiang Jiao; Zhu Wang (GPS Solutions, 2026)

Potential Causes of Anti‐Phase Summer Precipitation Variability Between the Middle and Lower Reaches of the Yangtze River - Yuwei Zhou; Ge Liu; Xiaolu Yan; Sulan Nan; Ting Zhang; Yinghan Sang; Xuefeng Han; Yuhan Feng; Hancheng Zou (International Journal of Climatology, 2026)
Summer precipitation in the middle and lower reaches of the Yangtze River generally shows synchronous variability and is thus extensively studied as a unified climatic region. However, out‐of‐phase variations occur between the middle and lower reaches in some years. This study investigates the mechanisms of the positive middle Yangtze River precipitation (MYRP)–negative lower Yangtze River precipitation (LYRP) pattern from the perspectives of atmospheric circulation and land‐ocean thermal anomalies. The results suggest that a non‐canonical Silk Road Pattern (SRP) teleconnection in the upper troposphere, coupled with a mid‐to‐lower tropospheric anomalous anticyclone over Northeast Asia and a weakened western Pacific subtropical high (WPSH), contributes to this precipitation pattern. Further analysis reveals that colder‐than‐normal land thermal anomalies in the Greater Caucasus Mountains and the northeastern Tibetan Plateau, as well as warmer‐than‐normal sea surface temperature anomalies (SSTAs) in the Sea of Japan, may help maintain the SRP‐like Rossby wave train (SLWT), therefore influencing the positive MYRP–negative LYRP pattern. Linear baroclinic model sensitivity experiments further support the identified thermal anomalies can excite and maintain the SLWT. Given that the SLWT differs to some extent from the classical SRP in both wave source and downstream structure, this study also proposes a SLWT index based on 200‐hPa vorticity anomalies. This index effectively captures both the spatial structure of the SLWT and its link with out‐of‐phase precipitation anomalies between the middle and lower reaches of the Yangtze River and may serve as a potential indicator for the occurrence probability of the positive MYRP–negative LYRP pattern. These findings may improve our understanding of regional precipitation mechanisms in the Yangtze River basin, thereby providing a scientific basis for improved disaster prevention and mitigation strategies.

Zircon–monazite geochronology and zircon Hf–O isotopes of Ediacaran–Cambrian paragneiss from the Mashan Complex, Jiamusi Block, NE China: implications for sedimentary–metamorphic–tectonic evolution - Guan-Ying Yu; Hao Yang; Jia-Hao Jing; Zheng Ji; Yan-Long Zhang; Jun-Hui Bi; Wen-Chun Ge (International Geology Review, 2026)

Highland Barley's future: Processing innovation empowers emerging opportunities in global health foods and sustainable agriculture - Xinlai Dou; Luman Sang; Liangxing Zhao; Yiqing Zhu; Shumin Shu; Yan Zhang; Jing Ou; Hongying Hua; Ge Li; Yong Xue; Qingyu Zhao; Chao Wang; et al. (Trends in Food Science & Technology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Precise perception of surface tackiness enabled by a soft single-sensing-element tactile sensor - Ying Yang; Mingwei Gu; Jia-Sen Xie; Xingyu Ma; Yan-Na Lu; Lin Zheng; Jinhui Gu; Junshuai Chen; Yunjie Lu; Denys Makarov; Jin Ge (Science Bulletin, 2026)

An ovarian follicle-based angiogenesis microphysiological system for high-efficiency screening of anti-angiogenic drugs - Xuebing Yang; Jing Liang; Nan Sun; Lu Mu; Jinfeng Xiong; Ge Wang; Kaiying Geng; Xie’an Feng; Yibo Wang; Shuo Zhang; Xueqiang Xu; Yan Zhang; et al. (Science Bulletin, 2026)

Integrative palynology and UPb zircon geochronology of the Jiufengshan Formation (upper Aptian, Dayangshu Basin, NE China): Evidence for early angiosperm expansion at mid-latitudes - Yan Zhang; Iván R. Barreiro; Chuan-biao Wan; Wen-chun Ge; Guo-chen Wang; Yun-fei Xue; Ti Li; Xin Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Petrogenesis and geodynamic significance of Late Cretaceous (ca. 85 Ma) ultramafic–mafic intrusive rocks in the southeastern Gangdese batholith, Southern Tibet - Yun-Peng Yu; Bao-Di Wang; Teng-Fei Ge; Yan-Yan Wei; Bao-Bao Cao; Jing-Zi He (Lithos, 2026)

Synergistic mechanism and operational limits of Fe0/Fe2+-mediated sulfur autotrophic denitrification for N/P removal† - Sijie Ge; Kexin Shang; Chuang Wang; Dan Zhao; Limei Yuan; Qingwu Yan; Junfeng Qu; Peng Gao; Chuanyi Zhang (Journal of Environmental Chemical Engineering, 2026)

Cellulose-guided interfacial engineering of Cu-MOF nanozyme on nylon/spandex fabric for synergistic UV shielding, O3 decomposition and ROS scavenging - Xiaomeng Li; Yaning Ma; Ruimeng Li; Yan Ge; Jiapeng Tang (Journal of Environmental Chemical Engineering, 2026)

Long-term scenario evolution, driver decomposition, and health-economic co-benefits assessment of PM2.5 and O3 pollution in China, 2020–2060 - Hanyu Zhang; Wenxing Shan; Kai Wang; Maofa Ge; Haozhen Du; Meilin Yan; Zhiliang Yao (Journal of Environmental Chemical Engineering, 2026)

T6SS-1 mediates cytosolic access and modulates immune responses in Pseudomonas plecoglossicida infection of Larimichthys crocea macrophages - Fei Ge; Mingming Zhang; Haoda Ye; Suming Zhou; Shenmei Pang; Xiaojun Yan; Zhen Tao (Fish & Shellfish Immunology, 2026)

Turning membrane fouling from inevitable to fully reversible via an electric-field repulsion-shield strategy - Yao Du; Jingyi Ren; Jinyi Wang; Jianfeng Zhang; Ziming Zheng; Haimeng Huang; Xue Yan; Lingzhi Cao; Tianmeng Zhang; Jefferson Zhe Liu; Mengni Ge; Xing Yang (Desalination, 2026)

Lightweight and eco-friendly methyl cellulose foams featuring moisture-induced form interlocking: A versatile alternative to conventional plastic foams - Rufei Ge; Longtai Wang; Yanzhen Lou; Yan Zhou; Foziljon Mamarayim Ugli Turakulov; Khaydar Ergashovich Yunusov; Abdumutolib Abdupatto Ugli Atakhanov; Jianbo Zhao; Guohua Jiang (Carbohydrate Polymers, 2026)

Effects of MMP8 inhibitors on chronic unpredictable mild stress-induced neuroinflammation and depressive-like behavior：exploring the underlying molecular mechanisms - Yan Ren; Weikang Chen; Jinhui Wang; Shasha Wu; Ting Linghu; Jinyin Ge; Ruiping Zhang (Psychopharmacology, 2026)

Reducing wheat grain Cd via harnessing indigenous microbiota in weakly alkaline soil - Chenghao Ge; Yixuan Wang; Wenyan Ma; Hong-Bo Li; Jingxia Guo; Hafiz Adeel Ahmad; Yan Gao; Dongmei Zhou (Plant and Soil, 2026)

Halotolerant plant growth-promoting bacteria Enterobacter sp. Av16 and Acinetobacter sp. Av23 enhance seed germination and seedling photosynthesis of Apocynum pictum under salt stress - Xue Wang; Li Jiang; Yao Ge; Yiping Zou; Qingsheng Cai; Yan Xia; Laiqing Lou (Journal of Zhejiang University-SCIENCE B, 2026)

Resampling native bee communities over 30 years showed stable trends along a tropical forest disturbance gradient - Qiaoyi Nong; Xiaojian Chen; Molin Hou; Da-Rong Yang; Michael C. Orr; Bai-Ge Miao; Cheng Wenda; Yan-Qiong Peng (Journal of Insect Conservation, 2026)

Clay membrane effects on solute transport through the aquitard of a leaky aquifer system - Xianmeng Meng; Ge Yan; Lintao Shen; Qu Wang; Maosheng Yin; Dengfeng Liu (Hydrogeology Journal, 2026)

River–Coast Connectivity Controls Ecosystem Services and Blue Carbon of Coastal Nature-Based Solutions: An Integrated Study Coupling Emergy–Carbon Footprint Accounting and Neural Network Modeling - Junxue Zhang; Yan Gong; Hairuo Wang; Ashish T. Asutosh; Ge Song; Weidong Wu; Xiaoting Zhai (Journal of Marine Science and Engineering, 2026)
This study develops an integrated framework combining emergy analysis, carbon footprint accounting, and long short-term memory neural network modeling to investigate the effects of nature-based solutions on coastal ecosystem services and blue carbon functions from the perspective of river–coast connectivity. Three transects along a connectivity gradient were established in the Yellow River Delta, a typical large river delta in temperate China, covering riparian zones, estuarine transition areas, intertidal wetlands, and seagrass beds, with multi-source data collected over three consecutive hydrological years. Emergy–carbon coupling analysis based on this case study indicates that the high-connectivity transect shows a higher emergy yield ratio and net carbon sink compared to the low-connectivity transect, with salt marshes being most sensitive to connectivity change. Threshold analysis, specific to this delta, identifies a three-phase response pattern of carbon burial rate with increasing sediment connectivity, and reveals that wave attenuation efficiency declines notably when hydrological connectivity falls below approximately 0.5, although this value may vary across different coastal settings. A higher sea level rise rate raises the critical connectivity level required to maintain carbon sink function. The long short-term memory neural network trained on observational data achieves better prediction accuracy for blue carbon accumulation rates than traditional statistical methods, and SHAP value analysis suggests the possible existence of synergistic effects among connectivity dimensions. Based on these findings, three optimization strategies including tiered restoration, a dynamic pathway, and spatial configuration are proposed as case-specific recommendations for the Yellow River Delta. Framework-based simulations indicate the potential for connectivity-informed strategy adjustments to improve restoration efficiency under local conditions. This study concludes that river–coast connectivity represents an important lever regulating the ecological benefits of nature-based solutions, but emphasizes that all quantitative thresholds and benefit magnitudes reported here are case-specific estimates that require recalibration when applied to other coastal systems.

A Galactose-Modified Light-Activatable Persulfurated Arene Fluorescent Probe for Targeted Imaging of Polarity and Viscosity in Liver Cancer Cells - Pan-Xin Ge; Yan Rong; Lu-Lu Sun; Yuqing Hu; Xianzhi Chai; Hai-Hao Han; Liangliang Zhu (Journal of Fluorescence, 2026)

Association Between Lead Exposure and Anthropometric Indicators in School-aged Children: A Longitudinal Study - Xiangju Wu; Yang Zhou; Linhong Li; Jieying Gao; Rongchang Xiao; Qian Yang; Meng Wu; Siyan Ye; Chengpeng Cui; Peng Lin; Ruifeng Luo; Ge Yan; et al. (Biological Trace Element Research, 2026)

Local administration of polymyxin B-conjugated Akkermansia muciniphila outer membrane vesicles attenuate asthma by suppressing M2 macrophage polarization - Chenchen Hou; Wenhui Sun; Lina Wang; Xiahui Ge; Qiyun Tu; Huaqi Guo; Tianyu Zhou; Lifeng Yan; Weining Xiong (Science China Life Sciences, 2026)

Hydrophobic high-frequency vibration collaborative strategy for reducing resistance and soil adhesion of tillage tools in lime concretion black soil - Kuan Qin; Ding Zhang; Biao Ma; Weidong Gao; Chengmao Cao; Xu Zhu; Junjie Lu; Wei Wang; Jun Ge; Qichun Feng; Huaizhi Liu; Siliang Liu; et al. (Soil and Tillage Research, 2026)

Multi-platform volatile profiling analysis was used to reveal the characteristics and influence mechanism of flavor metabolites in irradiated beef - Shuang Pang; Dandan Wu; Xinchen Jin; Yufan Tong; Suyang Weng; Ge Yan; Enxi Song; Ju Zhang; Xin Lü (Food Research International, 2026)

Covalent cross-linking of whey protein isolate-chlorogenic acid nanoparticles mediated by laccase: Structural, antioxidant and functional characteristics - Bingjie Xue; Jing Zhang; Sijia Yan; Yanhui Yang; Wupeng Ge; Lili Zhao (Food Hydrocolloids, 2026)

Hydrogen sulfide maintains banana postharvest quality by antagonizing ethylene and enhancing antioxidant properties in Musa nana Lour - Xue-Ting Cheng; Yan-Hong Li; Yun Ge; Zhuo Han; Yi-Ang Feng; Ying-Zhi Zhang; Kang-Di Hu; Gai-Fang Yao; Pedro García-Caparros; Hua Zhang (Food Control, 2026)

Genetic deletion of miR-200a/200b increases growth and feed conversion efficiency in yellow catfish - Xu Wang; Yan Xie; Qiaohong Lin; Yang Xiong; Ying Liu; Si Ge; Qiuen Tan; Zhipeng He; Youbo Jiang; Qingqing Han; Shuang Jin; Peipei Huang; et al. (Science China Life Sciences, 2026)

Correction to: Methyl jasmonate enhances carotenoid accumulation and lignin deposition in carrot taproot - Guang-Long Wang; Jia-Qi Wu; Yan-Xin Ge; Lin-Yan Jia; Cheng-Ling Zhou; Xu-Qin Ren; Ai-Sheng Xiong (Protoplasma, 2026)

Methyl jasmonate enhances carotenoid accumulation and lignin deposition in carrot taproot - Guang-Long Wang; Jia-Qi Wu; Yan-Xin Ge; Lin-Yan Jia; Cheng-Ling Zhou; Xu-Qin Ren; Ai-Sheng Xiong (Protoplasma, 2026)

Endoplasmic Reticulum Stress in the Keratinocytes Contributes to Chronic Itch by Activation of Lipocalin 2/MC4R/TRPV1 Pathway - Wei Ge; Yu Feng; Li Zhang; Qian-Liang Wang; Cheng-Wei Zhang; Zhi-Hong Wang; Guo-Kun Zhou; Shi-Yu Sun; Xiu-Hua Miao; Tong Liu; Bin Wu; Jun Yan (Neuroscience Bulletin, 2026)

The Complete Mitochondrial Genome of a Newly Recorded Chinese Species of Diglyphus sabulosus (Hymenoptera: Eulophidae) and Insights into Its Phylogenetic Position - Lu-Chao Fang; Zhi-Qiang Ge; Ou-Yan Xi; Ze-Lu Mu; Hong-Ying Hu (Biochemical Genetics, 2026)

DisenKGE-DDI: A Knowledge Graph Embedding Framework Based on Disentangled Graph Attention Networks for Drug–Drug Interaction Prediction - Huimin Luo; Linfei Hou; Chaokun Yan; Jianlin Wang; Junwei Luo; Ge Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Asynchronous Holocene moisture and precipitation variability in the Tibetan Plateau monsoon-westerlies transition zone - Tianlong Yan; Xiaomin Gao; Ge Shi; Chun Wang; Junjiang Dong; Qi Zhang; Xiaoru Zhang; Xiaoshuang Sun; Jinliang Liu; Can Zhang; Cheng Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Conserved sulfate removal pathway in microalgae: A cross-species investigation for high-sulfate wastewater treatment - Xiaofan Li; Shuang Qiu; Ruixin Yan; Wenju Shan; Shijian Ge (Journal of Environmental Management, 2026)

Integrating threshold effects into national park conservation planning: Synergies and trade-offs between biodiversity conservation and ecosystem services - Mengxiao Ge; Junze Liu; Yan Chen; Jun Qi (Journal of Environmental Management, 2026)

Characteristics, source apportionment, and secondary transformation of volatile organic compounds during different seasons at an urban site in southeast China - Xiaoming Liu; Jie Zhang; Zhengyu Lu; Qingzhi Ge; Shekou Wang; Donglin Chen; Mindong Chen; Yan Cui (Journal of Environmental Sciences, 2026)

Intranasal exposure to UV-irradiated polystyrene nanoplastics triggers vital organ inflammation and cognitive impairment - Huiqin Liu; Xidong Wu; Dan Luo; Luxuan Liu; Wuping Zhang; Yan Ge; Yaqi Peng; Chengshuai Liu; Chengyu Chen; Tao Liu (Journal of Environmental Sciences, 2026)

Precise pH control and synergistic interaction of raw materials improve the quality of stewed beef: multi-omics analysis of tenderization mechanisms and flavor restructuring - Yan Shen; Zezhu Du; Jinya Dong; Yuanfeng Chen; Huiqing Luo; Siyu Zhou; Cheng Gong; Shikuan Zhao; Zhiyu Li; Lihui Yu; Rong Geng; Xiaocui Du; et al. (Food Chemistry, 2026)

Linear spectral vibration and multi-modal vibration mitigation of pipeline systems using a multi-stable nonlinear energy sink - Yanbo Cao; Ge Yan; Yiming Cao; Dianlong Yu; Longqi Cai; Yu Wang; Yang Li; Wenming Zhang (Engineering Structures, 2026)

The role of co-ion transport in selectrodialysis for mono/divalent cation separation - Xixi Ma; Qian Chen; Lanlan Zhang; Shanshan Liu; Zixuan Wu; Rui Li; Zhiguo Dong; Weiwei Li; Jinfeng He; Chuanrun Li; Liang Ge; Haiyang Yan (Desalination, 2026)

Targeted and sustained release of pilose antler peptide from a thermosensitive injectable hydrogel for ischemic tissue repair - Wenjian Zhao; Nannan Xue; Zhengping Ge; Yan Wu; Ali Fathi; Simin Maleknia; Farshad Oveissi; Pei Liu; Jin-Ao Duan; Yiwei Wang (Chemical Engineering Journal, 2026)

Synergistic control of LixV2O5 with ordered-disordered hybrid rock-salt structure via chemical lithiation: Enhanced Li-ion battery performance - Wei He; Bei-Lei Yan; Wei-Wei Meng; Guang-Qiang Ma; Xue-Jun Zhu; Xue Hua-Mao; Lin Deng; Hong-Wei Ge; Tao Yang; Jun Wang (Chemical Engineering Journal, 2026)

Multi-omics characterization of benzo[a]pyrene toxicity networks identifies SERPINE1 and STK3 as prognostic biomarkers and therapeutic targets in head and neck squamous cell carcinoma - Yan Guo; Jiarui Zhang; Jingchun Ge; Liang Li; Ming Liu; Linli Tian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Slope aspect dominates over treeline position in structuring nitrogen-fixing microbial communities in Tibetan alpine ecotones - Jing-Ru Hao; Congcong Shen; Yan Li; Yuqiang Sang; Yuan Ge (Journal of Soils and Sediments, 2026)

Evaluation of clinical efficacy and safety of T-705 (Favipiravir) in the treatment of fever with thrombocytopenia syndrome: a propensity score matching study - Fei Zhao; Quanman Hu; Anmin Ge; Yan Hu; Yanyan Yang; Jundong Chen; Saiwei Lu; Yangfan Ou; Wenyao Su; Li Zhang; Shuaiyin Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Novel diffusion gradient in thin-films based on antibiofouling Ag/polydopamine membranes for measurement of antibiotics in natural waters - Jiaxing Xie; Fan Ge; Xinyi Yan; Suyu Ren; Yan Wang; Feng Tan (Analytica Chimica Acta, 2026)

Pyroptosis as a double-edged sword in colorectal cancer: Molecular mechanisms and therapeutic opportunities - Han-Xi Zhang; Wen-Jing Xu; Yi-Xin Jiang; Lu Li; Bai-Yu Chen; Meng-Yao Cheng; Meng-Yuan Hao; Hang-Shen Han; Hong-Jie Li; Yan-Ge Li; Dong-Dong Wu (Apoptosis, 2026)

Novel biodiversity and biogeography insights of filamentous Bangiales (Rhodophyta) from China - Yan-De Wang; Yin-Yin Deng; Cui-Cui Tian; Han-Ru Ge; Wei Zhou; Nan-Jing Ji; Li-En Yang (Algae, 2026)
The taxonomy of filamentous Bangiales was challenging due to its plastic and simple morphology. Molecular approaches play a significant role in revealing cryptic biodiversity and resolving phylogenetic relationships. Nonetheless, the biodiversity of filamentous Bangiales in many regions, including China, has not been thoroughly investigated yet using updated methods. In this study, we investigated the biodiversity of filamentous Bangiales in China, employing a more comprehensive and detailed sampling approach. The rbcL and 18S gene sequences (partial or complete) of 49 specimens collected from 37 sites were obtained. Phylogenetic analysis resolved these specimens into four clades, including Bangia, ‘Bangia’ 1, ‘Bangia’ 2, and Pseudoganglia. Seven putative species were delineated using empirical methods, including Automatic Barcode Gap Discovery (ABGD), General Mixed Yule Coalescent (GMYC), and Bayesian Poisson tree processes (bPTP), as well as genealogical analysis. Among them, four were species previously reported, two were cryptic species, and the other was a new record in China. The distribution of these molecularly delineated species was mapped along China’s coastline. Similar to the bladed Bangiales, antitropical, transoceanic, and thermal-gradient distribution patterns were also observed for filamentous Bangiales on a global scale. The ancestral region was retraced by incorporating species data from China into existing datasets using BioGeoBEARS with BAYAREALIKE + J as the best-supported model. Under this model, East Asia shows the highest marginal probability as the ancestral area for the crown clade, though uncertainty remains across alternative regions. A most parsimonious expansion scenario of Bangiales from east Gondwana to other regions of the world was proposed.

Recent advances of pretreatments and drying technologies in processing small berries: A comprehensive review - Yan Ge; Qiao-Yi Ma; Shan-Yu Wang; Arun S. Mujumdar; Xiaojun Huang; Hong-Wei Xiao; Zi-Liang Liu; Shaoping Nie (Trends in Food Science & Technology, 2026)

Priming effect on plant-derived mineral-associated organic C in paddy soil: a three-source partitioning study with a dual-13C approach - Yuhong Li; Jialing Wu; Qiong Liu; Jun Yuan; Falin Liu; Hongzhao Yuan; Kyle Mason-Jones; Yan Li; Jia Lu; Shaofeng Peng; Yongfu Li; Tida Ge (Soil Biology and Biochemistry, 2026)

Synchrony of prehistoric agricultural evolution and drought events in the North China Plain - Yanpeng Li; Shengrui Li; Hai Xu; Keliang Zhao; Guanhan Chen; Yaping Zhang; Jiacheng Ma; Junchi Liu; Yong Ge; Yan Zheng; Xinying Zhou; Xiaoqiang Li (Quaternary Science Reviews, 2026)

Bio-diesel quality characterization towards bio-jet fuel production using infrared spectroscopy and an interpretable machine learning framework - Chao Chen; Rui Liang; Yadong Ge; Ruodong Wang; Yanhui Men; Junyu Tao; Beibei Yan; Zhanjun Cheng; Xuebin Lv; Guanyi Chen (Journal of Environmental Management, 2026)

Study on the mechanism of 3D printing HIPE gels stabilized by soybean protein isolate/bacterial cellulose co-assemblies through simulating the animal adipose tissue structure - Chong Wang; Jiaxin Zhao; Jiaoqiong Liu; Xincheng Ge; Yan Sunhui; Guanghong Zhou; Chao Ding; Xinbo Zhuang (Food Hydrocolloids, 2026)

Electroreduction of nitrate to hydroxylamine over regenerable facet dependent bismuth nanosheet catalyst - Liwen Wang; Bingqing Ge; Xiaoxia Hou; Ningze Gao; Chenjia Liang; Xianghao Wang; Yan Zhu; Weiping Ding (Chemical Engineering Journal, 2026)

Cytoplasmic-nuclear remote suppression of c-MYC induces cell cycle arrest and enhances radiotherapy sensitivity in liver cancer via biohybrid platelets - Lin Xiao; Fei Ge; Qinyu Ji; Rui Ji; Yan Wang; Shaoqing Ju; Ming Cui; Donglin Xia; Rongrong Jing (Chemical Engineering Journal, 2026)

Damage observation-informed seismic vulnerability assessment of stainless steel-reinforced concrete bridge piers - Xiao Ge; Jian-Cheng Dai; Dong-Sheng Wang; Jing-Jing Zhang; Yu-He Zou; Yan-Hui Liu (Bulletin of Earthquake Engineering, 2026)

Extraction of Phyllanthus emblica L. flavonoids by ultrasound-assisted enzymatic hydrolysis method and antioxidant stress effects - Xianghong Xiong; Shengcheng Mi; Xiaojie Xu; Dan Ge; Wu Yan; Qi Lu; Minghua Zhu; Yihong Bao (Natural Product Research, 2026)

A novel approach to fat reduction: integrating traditional Chinese medicine with a dissolving MNs - Chengzhe Wang; Feifei Liu; Jieqian Ge; Shuang Zhao; Xiaotian Ma; Shuang Yi; Zixiang Ma; Yan Zhao; Jian Zhuang (Drug Delivery and Translational Research, 2026)

Pathogenicity of Porcine reproductive and respiratory syndrome virus in the reproductive system of female piglets: Pathological damage to the uterine horns and developmental arrest - Yi-Xin Yan; Ying Guan; Lei Zhao; Han-Yu Li; Tong Xu; Li-Na Shao; Si-Yuan Lai; Yi Qing; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; et al. (Veterinary Microbiology, 2026)

A multi-strategy multi-population cooperative optimization algorithm for drinking water pollution source identification - Han Wang; Qinghua Wu; Yang Ge; Zhijun Ren; Xuesong Yan (Swarm and Evolutionary Computation, 2026)

New Pachyportax fossils from the Late Miocene Shuitangba locality, Yunnan, revealing the early Bovini evolution and radiation - Ding-Ge Guo; Sayyed Ghyour Abbas; Qi-Gao Jiangzuo; Chun-Xiao Li; Yan-Wu Yang; Jia-Yong Cao; Bin Zou; Shi-Qi Wang; Xue-Ping Ji (Palaeoworld, 2026)

Nonnegligible migration of rubber-derived chemicals from road surface to adjacent greenbelt soil - Zhen-Yu Ge; Hai-Yan Zhang; Xue-E Li; Yue-Hong Liu; Li-Ni Wei; Xiang-Ning Liang; Yan-Feng Lv; Tuan-Tuan Wang; Sai Wang; Jian-Liang Zhao (Journal of Hazardous Materials, 2026)

Dual-function Ag2O/Zn-hemin MOF composites for radioactive iodide: performance and mechanism studies for removal and efficient visual detection - Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Man-Li He; Kai Chen; Yan Jiao; Peng Wang; Chun-Hui Gong; Yi Yang (Environmental Research, 2026)

A novel partitioned anaerobic membrane bioreactor integrated with ferromagnetic biochar for complex pesticide wastewater: Mass balance, membrane fouling mitigation, energy footprint, and life cycle assessment - Yifan Wang; Liwen Jiang; Dongxue Hu; Shiming Cui; Bei Jiang; Hui Ge; Shuya Zhuang; Jitao Yan; Zihan Wang; Pengcheng Zhang; Zhaobo Chen (Environmental Research, 2026)

Chemical characterization of dissolved organic matter in a hurricane-impacted estuary: linking chromophores, lignin phenols, amino acids and mass spectrometry-based compositions - Mohammad Al Mukaimi; Huda Alaskar; Ge Yan; Karl Kaiser (Estuarine, Coastal and Shelf Science, 2026)

Constructing dual-resistant nanofiltration membranes with superior antifouling and chlorine tolerance through a synergistic modification approach - Fanduo Meng; Yong Wang; Shuai Gong; Feiyue Ge; Wenxin Yan; Xiaozhen Lu; Liping Qiu; Feihong Wang; Daliang Xu; Xuewu Zhu (Desalination, 2026)

Structural strategies to overcome limitations of solid-liquid charge separation, recombination, and transport for renewable electricity generation - Chi Kit Ao; Junan Jiang; Chengyu Zhang; Yuwen Ge; Yan Jiang; Siowling Soh (Chemical Engineering Journal, 2026)

Enhanced thermoelectric and mechanical properties of copper sulfides achieved via natural mineral engineering - Tian-Yu Yang; Xi Yan; Chong-Yu Wang; Zhen-Hua Ge; Yi-Xin Zhang; Jing Feng (Chemical Engineering Journal, 2026)

How the aspect ratio of a rectangular heat source influences convective flow structures: Implications on city-scale heat and pollutants dispersion - Xiaoliang Teng; Yan Zhang; Jindong Wu; Yifan Fan; Jian Ge (Building and Environment, 2026)

Multifaceted Underground Space Detection Techniques for Smart City Development: A Combined Approach in Hangzhou, China - Bofan Yu; Huaixue Xing; Weiya Ge; Jiaxing Yan; Yun-an Li (Natural Resources Research, 2026)

CMSS1 promoted CXCL8-CXCR1/2 pathway to accelerate the invasion and immune escape of triple-negative breast cancer - Dequan Ding; Min Li; Xue Guo; Ge Wu; Yan Zhang (Journal of Molecular Histology, 2026)

Pseudonocardia mahuensis sp. nov., Isolated from Sediment of Mahu Lake in China - Chaolan Liu; Liwei Zhou; Zhuoxin Du; Jianghua Li; Lufeng Dan; Yan Ge; Guoqing Zhuang; Yidong Guo (Current Microbiology, 2026)

Effects of landscape fragmentation on floodplain fishes as revealed by species–habitat networks - Chen Zhang; Jorge García‐Girón; Ziyu Yang; Ziyu Liu; Shuxin Li; Wenhui You; Yihao Ge; Xin Gao; Yunzhi Yan (Conservation Biology, 2026)
How species interact with habitat patches is influenced primarily by habitat configuration (e.g., connectivity) and species’ functional traits. As levels of fragmentation increase, identifying the intricate connections between these components is crucial for biodiversity conservation. We used the species–habitat network (SHN) approach to identify the links between fish species and lakes in a highly fragmented floodplain; to determine lakes and fish species that are key to maintaining landscape SHN organization; and to examine the impact of habitat configuration and species functional traits on fish responses to loss of lateral hydrological connectivity (LHC). Low metacommunity functional connectivity, lack of robustness, and high modularity (i.e., strong within group interactions) and nestedness indicated low resistance of fish communities to long‐lasting landscape fragmentation, highlighting the importance of large lakes connected by rivers and fishes that migrate between rivers and lakes to maintaining the SHN organization in floodplain ecosystems. The strong association between maximum body length and fish contribution to this network organization indicated that large fish species are potentially more likely to establish interactions at the landscape scale. Trophic level was the main factor controlling the roles of migrating fishes in SHN organization. Based on species’ interactions with habitat patches, we identified and mapped the sites and species responsible for the main features of the SHN structure. Our approach offers new directions for conserving and restoring fragmented floodplains by integrating LHC and fish functional traits to inform targeted conservation priorities.

Rapid starch degradation characterized by the related gene expression and key enzymes resulted in an optimum comprehensive quality of sugar, acid, and firmness in postharvest apples - Lingyu Qiu; Niu Ye; Yang Zhao; Mengke Cao; Miaomiao Ge; Xiaolin Ren; Yan Tang; Huiling Ma (Postharvest Biology and Technology, 2026)

Naringenin as a bioactive preservative: Coordinated suppression of ethylene biosynthesis and cell wall disassembly delays apple senescence during storage - Ming-Fei Qiao; Peng-Liang Han; Meng-Meng Wei; Zhao-Peng Nie; Song Zhang; Wen-Yan Wang; Hai-Bo Wang; Tian-Ge Chu; Ze Chen; Quan Sun; Da-Gang Hu (Postharvest Biology and Technology, 2026)

Integrative mechanisms, dissolved oxygen control, and the optimal energy window for one–stage aerobic nitrogen and phosphorus removal via heterotrophic nitrification–aerobic denitrification (HN–AD) - Jiale Han; Xiaoyu Wang; Xinjiao Dong; Qi Fang; Zimiao Yan; Yaru Li; Shimei Ge (Journal of Water Process Engineering, 2026)

Defect-rich carbon induced built-in electric fields within molybdenum-based metal-organic framework catalysts for enhanced activity and stability in oxidative desulfurization - Juncong Zou; Yang Yan; Shanying He; Chengjun Ge; Dexin Wang; Chunping Yang (Journal of Hazardous Materials, 2026)

Drought exacerbates biodiversity-loss-induced soil organic matter decline by altering soil fungal assemblages - Yan Li; Jiang Wang; Congcong Shen; Yuan Ge (Journal of Environmental Management, 2026)

Impact of temperature on the biogenic volatile organic compound (BVOC) emissions in China: A review - Yiming Yang; Fengbin Sun; Yusheng Chen; Shiyue Yang; Yuan Dai; Yiming Qin; Ning Zhang; Zhifeng Shu; Han Yan; Xinlei Ge; Junfeng Wang (Journal of Environmental Sciences, 2026)

A novel method for remote sensing phycocyanin leveraging optical classification and an integrated machine learning algorithm - Shizhuo Liu; Chong Fang; Kaishan Song; Ge Liu; Zhidan Wen; Yingxin Shang; Sijia Li; Hui Tao; Zhaojiang Yan; Lili Lyu; Yunfeng Lyu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Bioaerosols from outdoor wastewater treatment facilities: dispersal behavior, exposure risks and protection strategies - Jingyun Ge; Tong Gao; Huili Li; Zhongcai Lun; Changren Yan; Caixia Li; Yanjie Wang; Lin Li (International Journal of Hygiene and Environmental Health, 2026)

From origin tracing, processing, to quality regulation: Molecular mechanism advances in medicinal foods research by integrating multi-omics tools - Jian-Hang Cai; Guan-Dong Fang; Yan Zhang; Jie Song; Jia-Yi Weng; Xue-Mei Ge; Issoufou Amadou; Xiang-Rong Cheng (Food Bioscience, 2026)

Smart, tumor-targeted, and responsive intracellular delivery engineering (STRIDE) nanoplatform: co-delivery of siGLI1 and cisplatin prodrug to overcome lung adenocarcinoma chemoresistance - Ge Chen; Mengyang Liu; Yanan Sun; Shifei Zhang; Qingyi Liu; Yuxiang Liang; Kexin Cong; Meng Yan; Zhigan Zhang; Jinjiang Deng; Zongyu Wang; Ziqiang Li; et al. (Chemical Engineering Journal, 2026)

Covalent organic framework-mediated Nafion superhydrophobic coating for stabilizing the anode of aqueous zinc-ion batteries - Ling Zhong; Yimeng Yan; Zhixuan Ye; Xinxiang Zhang; Wenbin Yang; Jiaxian Zheng; Xiangfeng Lin; Linxin Zhang; Ge Zhou; Huiping Lin; Zhanhui Yuan (Chemical Engineering Journal, 2026)

Innovative NFC-based flexible sensing system for wireless and battery-free detection of H2S: A game-changer in real-time fresh food freshness evaluation - Ning Shi; Yan Tong; Boyang Xu; Xiaohu Ge; Yueqiang Cao; Yu Han; Yunda Chen; Anxin Luo; Xiaochan Wang; Gang Liu; Xiande Zhao; Guo Zhao (Chemical Engineering Journal, 2026)

Corrigendum to “Dendrobium officinale polysaccharide promotes M1 polarization of TAMs to inhibit tumor growth by targeting TLR2” [Carbohydrate Polymers 292 (2022) 119683] - Hong-Yan Wang; Ji-Chun Ge; Feng-Yun Zhang; Xue-Qiang Zha; Jian Liu; Qiang-Ming Li; Jian-Ping Luo (Carbohydrate Polymers, 2026)

Influence of Grouting Pipe Lifting Rate on Vacuum Preloading Performance for Dredged Sludge - Zhou Changchen; Jin Fangyi; Xu Li; Li Dawei; Ni Junfeng; Yan Shuaixin; Xu Mintao; Han Song; Ge Bin; Wu Yehu; Zhang Ye (Geotechnical and Geological Engineering, 2026)

Optical and biomarker indicators reveal contrasting saltmarsh and riverine contributions of terrigenous dissolved organic carbon - Joshua P. Harringmeyer; Karl Kaiser; Ge Yan; Matthew W. Weiser; Xiaohui Zhu; Nilotpal Ghosh; Cédric G. Fichot (Limnology and Oceanography, 2026)
Dissolved organic carbon (DOC) in the coastal ocean originates from multiple sources that differ in composition and reactivity, influencing their fates in the ocean. The diffuse export of coastal marsh‐derived DOC remains poorly quantified, creating uncertainties in ocean carbon budgets. A major challenge is identifying marsh‐derived DOC within heterogeneous mixtures in coastal waters. Here, we introduce a new multivariate framework to partition terrigenous DOC (tDOC) into saltmarsh‐derived and riverine fractions in nearshore and coastal waters, focusing on the northern Gulf of Mexico. The approach integrates ratios of cinnamyl (C), vanillyl (V), and p ‐hydroxyphenyl (P) dissolved lignin phenols (C/V and P/V) with salinity and other compositional indicators of tDOC (spectral slope coefficient, S 275–295 , and carbon‐normalized yield of lignin phenols carbon, TDLP 9 ‐C) to quantify DOC contributions from riverine, marsh, and marine sources. Implementation of the source framework revealed that nearshore tDOC was dominated by riverine inputs near the Mississippi and Atchafalaya river deltas, whereas saltmarsh‐derived tDOC was prevalent near the marsh‐dominated Terrebonne Bay. Offshore, tDOC comprised a small but non‐negligible fraction (

The role of amino acid signaling in pathogenesis of chronic kidney disease - Siya Yan; Xiangqi Zhang; Ruizhen Bu; Ge Li; Yang Wang; Meifang Cheng; Qian Chen; Yuzheng Wu; Yi Zhang; Dan Wang; Tao Wang (Molecular and Cellular Biochemistry, 2025)

Nitrogen transformation and N2O production pathways under arsenic and cadmium stress in Chongming Island, China - Yinghui Jiang; Guoyu Yin; Minghua Nie; Caixia Yan; Mingjun Ding; Hua Zhang; Mei Lei; Yong Ge (Marine Pollution Bulletin, 2025)

Impacts of climate change and land use changes on heat island effect in the Guangdong-Hong Kong-Macao Greater Bay Area under the SSP-RCP framework - Xin Yan; Alex Hay-Man Ng; Xun Liu; Qianqian Zhou; Linlin Ge (Sustainable Cities and Society, 2025)

Effects of organic fertilizer substitution for chemical fertilizer on tea yield and quality: A meta-analysis focusing on alkali-hydrolyzable nitrogen dynamics - Shaobo Zhang; Hongbin Zhang; Lan Zhang; Zhengzhen Li; Yihu Mao; Liping Zhang; Shibei Ge; Qiang Hu; Chao Chen; Wenyan Han; Peng Yan; Xin Li (Soil and Tillage Research, 2025)

A novel deep learning system for STEMI prognostic prediction from multi-sequence cardiac magnetic resonance - Yifan Chen; Meng Jiang; Chao Xia; Hang Zhao; Panpan Ke; Sheng Chen; Heng Ge; Keran Li; Xu Wang; Yufei Wang; Yezi Chai; Qiming Liu; et al. (Science Bulletin, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Low frequency polarized electric field inhibits enzymatic browning in fresh-cut taro via dual regulation of carbohydrate metabolism and ROS scavenging systems - Jie Zhu; Tianyu Ge; Linyu Nian; Yan Liu; Youyi Miao; Suilou Wang; Chongjiang Cao (Postharvest Biology and Technology, 2025)

Harnessing machine learning for energy optimization and intelligent process control in wastewater treatment - Yibo Du; Tianlong Lei; Jie Jin; Boyu Chen; Xuanbei Wu; Nuan Yang; Yihong Ge; Yan Wang; Qifeng Tan; Dingrui Fan; Yunhui Lei; Ling Yao (Journal of Water Process Engineering, 2025)

The impact of extreme weather event on off-farm employment: Evidence from rural China - Shaohua Wang; Haixia Wu; Yan Ge (Journal of Rural Studies, 2025)

Conventional microplastics pose higher short-term risks to crop growth than biodegradable alternatives: Evidences from a two-year field trial - Yan Liu; Juncong Chu; Lang Cheng; Zhengjun Yan; Yue Wang; Junyong Ge; Huadong Zang; Zhaohai Zeng; Yadong Yang (Journal of Cleaner Production, 2025)

Prediction and analysis of polyvinylidene fluoride membrane pyrolysis reaction based on machine learning framework - Hong Su; Yadong Ge; Xiaohua Wang; Lan Mu; Beibei Yan; Guanyi Chen (Journal of Environmental Chemical Engineering, 2025)

Inconsistent capacity of potential HONO sources to enhance secondary pollutants: Evidence from WRF-Chem modeling - Jingwei Zhang; Haiyan Ran; Yu Qu; Chaofan Lian; Weigang Wang; Yusheng Zhang; Feixue Zheng; Xiaolong Fan; Dawei Lu; Chao Yan; Kaspar R. Daellenbach; Zhiqiang Ma; et al. (Journal of Environmental Sciences, 2025)

Metal-organic frames (MOFs) effects on the microwave ignition of ADN-based liquid propellant - Yan Ge; Jian Cheng; Ruiqi Shen (Fuel, 2025)

Influence of microbial and functional metabolites on the aroma of wines from different areas in Ningxia, China - Yue Liu; Zhouli Wang; Xiang Chen; Xiaoshuang Liu; Yang Luo; Yue Yan; Jianrong Kai; Danqing Zhao; Jing Zhang; Caihong Li; Qian Ge (Food Research International, 2025)

Combining functional fucoidan with zein to enhance the adhesion and differentiation of myoblast cells - Wanli Xiong; Yi Zhou; Miaomiao Chai; Yawen Chen; Wenjing Dai; Lu Wang; Chengxin Ge; Wen-song Tan; Yan Zhou (Food Research International, 2025)

Machine learning intelligently selects feature values to construct a sensor array based on tri-functional Mn-doped covalent organic polymer nanozymes for identifying flavonoid compounds - Guo-Qi Zhang; Wen-Cai Jiang; Xiao-Mei Li; Ren-Jie Li; Yi Feng; Ri-Ge Li Nai; Hui-Lin Cheng; Zhi-Bo Hou; Xiao-Jun Luo; Yan Zhao (Food Chemistry, 2025)

Prenatal air pollution exposure and placental vasculature development among participants of the UPSIDE cohort study - Shivram Kumar; Carolyn M. Salafia; Ruchit Shah; Theresa Girardi; Richard K. Miller; Sally W. Thurston; Philip K. Hopke; David Skrill; Jessica Brunner; Donald Harrington; Yihui Ge; Yan Lin; et al. (Environmental Research, 2025)

Entropy-controlled velocity-dependent behavior of landslide clayey soil across a wide velocity range - Wei Hu; Yangshuai Zheng; Yi Ge; Li Zhou; Yan Li; Xiaoping Jia (Earth and Planetary Science Letters, 2025)

CuFe2O4@T-COF nanosphere-mediated biosensing platform based on DNA walker signal amplification strategy for ultrasensitive HPV detection - Zhen Yu; Yan Zhang; Dongquan Leng; Tingting Wu; Si-Jia Ge; Dawei Fan; Hongmin Ma; Yu Du; Qin Wei (Chemical Engineering Journal, 2025)

Superposition modification strategy for enhances the kinetics and air stability of P2-Na0.62MnO2 - Jiang Zhu; Xun Yuan; Xingguo Liu; Yan Cheng; Dongjing Liu; Hailang Liu; Zhiguo Peng; Chaobo Deng; Qilin Tong; Jiali Tong; Yunchen Ge; Shengkui Zhong; et al. (Chemical Engineering Journal, 2025)

Effects on soil structures by root growth in the Loess Plateau, China - Rongqi Li; Hanruo Wang; Yilin Yan; Chao Han; Yulong Zhao; Yuanhao Liu; Shangyu Shi; Wenyan Ge; Fei Wang (CATENA, 2025)

The prediction and optimization of biomass compatibility ratios by machine learning for enhancing methane production in anaerobic co-digestion - Yadong Ge; Zaixin Li; Zhuang Yuan; Zhi Wang; Beibei Yan; Junyu Tao; Shengquan Zhou; Guanyi Chen (Bioresource Technology, 2025)

Metabolomics Reveals Reasons for the Efficacy of Acupuncture in Migraine Patients: The Role of Anaerobic Glycolysis and Mitochondrial Citrate in Migraine Relief - Zishan Gao; Xianzhong Yan; Rui Wang-Sattler; Marcela Covic; Guang Yu; Feifei Ge; Jia Lin; Qin Chen; Juan Liu; Sapna Sharma; Sophie Molnos; Brigitte Kuehnel; et al. (Phenomics, 2025)
Acupuncture is used worldwide to treat migraine, but its scientific mechanism remains unclear. Here, we report a 1 H NMR metabolomics study involving 40 migraine patients and 10 healthy individuals randomly receiving acupuncture or sham acupuncture, followed by machine learning techniques and functional analysis. We found that acupuncture at acupoints particularly enhanced anaerobic glycolysis and modified mitochondrial function by adjusting the levels of plasma pyruvic acid ( p = 0.012), lactic acid ( p = 0.031) and citrate ( p = 0.00079) at a Bonferroni-corrected level of significance compared to the pre-treatment level of these three metabolites in migraine patients. Therefore, acupuncture supplies energy to migraine patients and relieves migraine attacks. In contrast, we observed that sham acupuncture may partially supply energy to migraine patients through lipid metabolism by changing the levels of plasma lipid ( p = 0.0012), glycerine ( p = 0.021), and pyruvic acid ( p = 0.047) at a Bonferroni-corrected level of significance. The functional network analysis further indicates this different way of supplying energy contributes to the different effects of acupuncture and sham acupuncture. Our findings reveal novel metabolic evidence for the specific effect of acupuncture in relation to sham acupuncture. This metabolic evidence could enlighten a brand new direction into acupuncture analgesia mechanism, which in turn would pose fresh challenges for future acupuncture research.

Genome-wide survey and expression analysis of JAZ genes in watermelon (Citrullus lanatus) - Yan-Ge Li; Jing Zhang; Xiu-Xiu Cai; Le-Ping Fan; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Molecular Biology Reports, 2025)

P2RX1 in neutrophils mediates JAK/STAT signaling pathway to regulate malignant phenotype of gastric Cancer cells - Yan Zhang; Fenglin Zhang; Zhi Liu; Min Li; Ge Wu; Hui Li (Molecular Genetics and Genomics, 2025)

Enhancing Laterite’s Mechanical Properties and Reducing Water Sensitivity with Glycerol Monostearate - Kun-Yu Fu; Yan-Ge Chen; Ying-Zhen Ji; Qi-Ya Wang (Geotechnical and Geological Engineering, 2025)

PM2.5 and NO2 exposure during pregnancy and measures of fetal size and attained size at birth - Nafisa Nawal Islam; Sally W. Thurston; Donald Harrington; Yihui Ge; Samuel Weisenthal; Jessica Brunner; Richard K. Miller; Philip K. Hopke; Yan Lin; Emily S. Barrett; Thomas G. O’Connor; Junfeng Zhang; et al. (Air Quality, Atmosphere & Health, 2025)

The Association of Cadmium Exposure and Anthropometrics in School-Age Children: A Longitudinal Study - Meng Wu; Linhong Li; Tianwenjing Huang; Jieying Gao; Peng Gan; Shudan Liu; Dan Wu; Siyan Ye; Chengpeng Cui; Longjie Li; Ge Yan; Qin Liu (Biological Trace Element Research, 2025)

Numerical Analysis of a Vertical Axis Wind Turbine with Racetrack Trajectory - Sixiong Ge; Yan Yan; Zhecheng Lou; Jie Xu; Zhehao Sheng; Jiahuan Cui (Journal of Marine Science and Engineering, 2025)
This study presents a comprehensive numerical and theoretical analysis comparing the aerodynamic performance of a racetrack trajectory vertical axis wind turbine with a baseline VAWT. The racetrack trajectory comprises two parallel straight segments connected by semicircular arcs. However, two critical research gaps remain: the aerodynamic performance of this non-axisymmetric rotor, especially its sensitivity to inflow direction, is not well understood, and a computationally efficient theoretical model for its rapid design is lacking. Using unsteady Reynolds-Averaged Navier–Stokes (URANS) simulations to systematically quantify this sensitivity, and developing an adapted double multiple streamtube (DMST) model, the performance of both turbines is evaluated across tip speed ratios (TSRs) of 1.5–4 and inflow angles β = 0–90°. Results indicate that the racetrack turbine achieves a peak power coefficient of 0.49 at TSR = 2.5 and β = 90°, 16.7% higher than the baseline VAWT. Its performance is highly sensitive to inflow direction, whereas the baseline operates more uniformly across angles. Flow field and wake analyses reveal that the racetrack turbine exhibits faster wake recovery and lower turbulence intensity downstream under optimal inflow. This study demonstrates the potential of racetrack turbines for enhanced directional efficiency in marine wind conditions and validates the adapted DMST model as a reliable tool for preliminary design.

ESG Scores and financial performance are making energy companies be in a dilemma: evidence from China - Fang-rong Ren; Hui-yi Chen; Xi-ting Yang; Xin-ge Guan; Xiao-yan Liu (Environment, Development and Sustainability, 2025)

A novel mycotoxin-degrading enzyme complex can biodegrade AFB1, DON, and ZEN co-contamination in both in vitro and in vivo experiments - Yan-Qi Ning; Zhe Peng; Yu Zhang; Alainaa Refaie; Jing-Hui Ge; Li-Jia Guo; Wen-Jie Yang; Lv-Hui Sun (Toxicon, 2025)

Efficient degradation mechanism of fomesafen by earthworms and gut degrading bacteria synthetic community - Yan Ge; Aoqi Yang; Yongkang Dong; Siqi Wang; Rui Xu; Dongxing Zhou (Pesticide Biochemistry and Physiology, 2025)

The fungicide jinggangmycin stimulates fecundity of Nilaparvata lugens Stål via ILP/Foxo signaling - Xudong Zhao; Yuting Ding; Zhirou Duan; Di Deng; Zhiyue Mao; Yan Zhu; Xiaoxi Fan; Guohui Yu; Linquan Ge (Pesticide Biochemistry and Physiology, 2025)

Alkaloids from the tubers of Pinellia pedatisecta - Xu Chen; Yan-gang Cao; Feng-xiao Hao; Yan-ling Liu; Fang-ge Chi; Ying Niu; Di Lu; Bing-xian Zhao; Lan Chen; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2025)

Norsesquiterpenes from the stems and leaves of Pinellia pedatisecta Schott - Xu Chen; Yan-gang Cao; Fang-Ge Chi; Yan-ling Liu; Kai-li Ye; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2025)

Flash roasting for phase transformation of α-spodumene coupled with sulfuric acid pressure leaching to enhance lithium extraction - Dongqi Song; Wei Chen; Qingkang Yan; Yu Liu; Ge Kuang; Hui Guo; Guosheng Li; Yijun Cao (Minerals Engineering, 2025)

Downscaling multilayer soil moisture using parameterized depth profiles associated with environmental factors - Mo Zhang; Yong Ge; Yuxin Ma; Yan Jin; Yingying Chen; Shaomin Liu (Journal of Hydrology, 2025)

Petrogenesis and factors controlling tungsten mineralization of Late Mesozoic granites from Xianxia intrusion and Zhuxiling tungsten deposit in Jiangnan tungsten belt, China - Likai Ge; Jun Yan; Qiaoqin Xie; Sujuan Zhou; Liu Yang; Quanzhong Li; Jiancheng Xie (Journal of Geochemical Exploration, 2025)

Temperature-mediated shift from competitive to facilitative interactions between lactic acid bacteria and bacillus species in daqu fermentation: Insights from metagenomics, dual RNA-seq, and coculture analysis - Liming Wu; Meiyu Yan; Xinlei Huang; Hui Liao; Daixiu Bao; Yitong Ge; Shuaijun Wang; Xiaole Xia (International Journal of Food Microbiology, 2025)

Distribution characteristics of black carbon in Taihu Lake sediments and their effects on microorganisms - Yan Li; Hang Su; Ke Liu; Chengjun Ge; Qingkun Wang; Xinyu Cheng; Jiang Jiang (Environmental Research, 2025)

Experimental study, finite element simulation and theoretical analysis on punching shear capacity of steel-ECC composite slabs - Youzhu Lin; Di Yao; Ge Gao; Tianfei Gu; Ming Sun; Jiachuan Yan (Engineering Structures, 2025)

Dual-stage reverse-dialysis-engineered cartilage-biomimetic hydrogels: Highly resilient anti-swelling double-layer architectures - Zheng-Feng Zhang; Mei-Yan Ling; Xiao-Rui Ge; Jia-Ying Chen; Bei Zhang; Xiao-Hui Yao; Peng Song; Wei-Guo Zhao; Dong-Yang Zhang; Jun Wang (Chemical Engineering Journal, 2025)

Damaged mitochondria targeted copper doped carbon dots as a fluorescent probe hitchhike on circulated neutrophils for precise treatment of ischemic stroke - Ge Zhang; Yan Sun; Fang Li; Yong Liu; Mengdi Sun; Mingzhu Song; Ruizhen Lv; Jia Dong; Yijie Shi; Liang Zhao (Chemical Engineering Journal, 2025)

Biomimetic priming of hMSC aggregates with cadherin-IL-1β synergistic microparticles enhances immune homeostasis in inflammatory bowel disease - Mengyuan Qian; Min Ge; Shanshan Liu; Xin Wen; Ning Liu; Qianqian Wang; Jiaxu Cao; Xiuyan Jiang; Yan Zhang; Jun Yang; Lingyun Sun (Chemical Engineering Journal, 2025)

Bimetallic copper-bismuth microtubular electrodes with tunable interfaces for efficient electrochemical reduction of CO2 to formate - Beibei Ma; Hesamoddin Rabiee; Guoliang Chen; Yizhu Kuang; Tianjiu Zhu; Penghui Yan; Lei Ge; Zhonghua Zhu (Chemical Engineering Journal, 2025)

Fs–LA–ICP–MS U–Pb dating of fluorite and its prospect for geological application - Yan-Wen Tang; Na Liu; Jun-Jie Han; Yan Liu; Wan-Ting Ge; Jian-Feng Gao; Ting-Guang Lan (Chemical Geology, 2025)

Mechanisms of thermal, acid, desiccation and osmotic tolerance of Cronobacter spp. - Yanfei Yan; Mengyuan Cao; Jiaqi Ma; Jia Suo; Xiaobao Bai; Wupeng Ge; Xin Lü; Qiang Zhang; Jia Chen; Shenghui Cui; Baowei Yang (Critical Reviews in Food Science and Nutrition, 2025)

Chemical constituents from the tubers of Pinellia pedatisecta Schott - Fang-Ge Chi; Xu Chen; Yan-Gang Cao; Yan-Ling Liu; Di Lu; Ying Niu; Bing-Xian Zhao; Lan Chen; Yi-Xin Zhao; Xiao-Ke Zheng; Wei-Sheng Feng (Natural Product Research, 2025)

The Identification and Synthesis of New Sea Cucumber Peptides Leveraging Peptidomics Technology, along with their Anti-Parkinson’s Disease Efficacy - Jiawei Liu; Yusheng Shi; Lingling Jin; Baixue Sun; Ruonan Wang; Guangbo Ge; Guanghao Zhu; Xiaolin Cui; Jie Zhao; Yan Zhang; Sheng Li (Journal of Neuroimmune Pharmacology, 2025)

Microbial metabolisms determine soil priming effect induced by organic inputs - Yingyi Fu; Wanling Liu; Zhiyi Chen; Marc Redmile-Gordon; Chao Liang; Caixian Tang; Georg Guggenberger; Shaobin Yan; Liming Yin; Jingjing Peng; Lukas Van Zwieten; Peng Wang; et al. (Soil Biology and Biochemistry, 2025)

A technique for synthesis of δ-MnO2 with which spent coffee ground biochar was loaded for eliminating the risk of lead exposure in soil - Yan Zhou; Gaoyuan Gu; Jianing Zhang; Ruijie Ge; Chong Peng; Yun Li; Shuyi Yang; Tao E. (Process Safety and Environmental Protection, 2025)

Paleoecology and paleoclimate across the Early Cretaceous Xing'anling Group: New palynological and radiometric data from the Hailar Basin (NE China) - Yan Zhang; Iván R. Barreiro; Chuan-biao Wan; Yue-wu Sun; Wen-chun Ge; Yun-fei Xue; Ti Li; Xin Zhang; Chun-yang Bu; Hao Zhu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Spatiotemporal evolution and factors influencing energy system resilience in China under the dual carbon target - Lingna Liu; Siyu Yao; Jianping Ge; Tongrong Fu; Yong Yan (Journal of Cleaner Production, 2025)

Corrigendum to “Microwave ultra-narrow band antenna sensor based on TiO2/MXene for room-temperature acetone detection” [J. Environ. Chem. Eng. 13 (5) (2025) 118803] - Jie Wei; En-Kang Wu; Ji-Hao Zhang; Zhen Zhang; Xiao-Cong Tang; Tian Qiang; Yongwoo Jang; Xiao-Feng Gu; Meng Zhao; Svetlana von Gratowski; Jun-Ge Liang; Ming-Yang Yan; et al. (Journal of Environmental Chemical Engineering, 2025)

Antibacterial effect of electrolysis combined with ZnO nanoparticles treatment on heterotrophic bacteria in simulated water - Ziyu Yan; Xuhui Wang; Dengjia Yuan; Min Xu; Junwei Wang; Honghua Ge; Xinjing Meng; Yuzeng Zhao (Journal of Environmental Chemical Engineering, 2025)

Microwave ultra-narrow band antenna sensor based on TiO2/MXene for room-temperature acetone detection - Jie Wei; En-Kang Wu; Ji-Hao Zhang; Zhen Zhang; Xiao-Cong Tang; Tian Qiang; Yong-Woo Jang; Xiao-Feng Gu; Meng Zhao; Svetlana von Gratowski; Jun-Ge Liang; Ming-Yang Yan; et al. (Journal of Environmental Chemical Engineering, 2025)

An ultra-sensitive photoelectrochemical aptasensor based on magnolia leaf-derived biochar for Cu2 + in crop soils and agricultural water - Yuhang Ge; Yuting Yan; Pengcheng Yan; Hanping Mao; Lizhi Li; Xiaoxue Du; Qirui Wang; Henan Li (Journal of Environmental Chemical Engineering, 2025)

SiO2 nanofiber and graphene oxide assisted fabrication of silica aerogels with novel interpenetration networks for efficient oil adsorption and photothermal evaporation - Meng-Jie Chang; Ge Bai; Jun Liu; Qiu-Yu Hu; Shu-Yi Hu; Yan Yin; Shi-Shun Cao (Journal of Environmental Chemical Engineering, 2025)

Asynchronous modes of paleofire occurrence in eastern monsoonal China since the LGM - Menglin Song; John Dodson; Scott Mooney; Ge Shi; Hong Yan (Global and Planetary Change, 2025)

Residue and metabolism of imidacloprid in cherry radish using a 14C study: Implications for food safety - Yan Chen; Deyang Kong; Lei Huang; Jing Xu; Haiyan Wang; Feng Ge (Food Chemistry, 2025)

A magnetically levitated platform with multi-directional quasi-zero stiffness for low-frequency vibration protection - Wenhao Qi; Tianyu Zhao; Qiuhua Gao; Jiajia Lu; Fanchi Zeng; Ge Yan; Wenming Zhang (Engineering Structures, 2025)

Fracture evolution and anchoring mechanisms in discontinuous rock masses with irregular joints: Discrete element study using a novel damage constitutive model - Yin-Ge Zhu; Yue Wu; Cheng-Hao Han; Wei-Guo Qiao; Feng Jiang; Ji-Xian Dong; Shuai Zhang; Yan-Zhi Li (Computers and Geotechnics, 2025)

High-performance room-temperature phosphorescence materials based on arylboronic acids activated by a dual hydrogen-bonded network - Weiguang Liu; Fengyan Ge; Peibo Du; Xin Yan; Haixia Jiang (Chemical Engineering Journal, 2025)

Ion directional migration-induced ionic bonding boosting anchoring of low-friction hydrogels to Ti6Al4V for artificial joints - Kai Chen; Hongkun Liu; Xiaodong Yan; Qin Chen; Ziqiang Zhu; Haiyan Feng; Xinyue Zhang; Cunao Feng; Li Xiang; Xiaowei Li; Dekun Zhang; Shirong Ge (Chemical Engineering Journal, 2025)

Red blood cell-mimetic hollow covalent organic framework with oxygen-replenishing and cavitation-amplified for enhanced sonodynamic therapy of periodontitis - Yang Zhou; Qiyuan Pan; Ruolin Wang; Yan Ge; Xiao Zhang; Yifan Guo; Rongyin Sun; Xianglong Liu; Sainan Liu; Min Liu; Jun Lin (Chemical Engineering Journal, 2025)

Corrigendum to “Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices” [Chem. Eng. J. 510 (2025) 161390/CEJ 161390] - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

An ingenious structural design of NiCu-MOF bar-like nanosheet array: harnessing synergistic effects to attain exceptional ammonia oxidation performance - Guang-Lan Li; Yu-Hui Shi; Ri-Yang Huang; Tian-Ge Ma; Qian Zhuo; Ling Xu; Fei Jiang; Yu-Kun Zhai; Yong-Hou Xiao; Hong-Jiang Li; Yang Yan; Yun Zhao (Chemical Engineering Journal, 2025)

Specialized sunbird pollination in Colquhounia elegans (Lamiaceae): limited hovering and distinctive nectar properties - Yang Huang; Mei-Ying Huang; Yao Ning; Chang-Qiu Liu; Wen-Yan Ge; Xiao-Zhen Zhu (Plant Systematics and Evolution, 2025)

Targeting cuproptosis in liver cancer: Molecular mechanisms and therapeutic implications - Yun-Fei Zhou; Yi-Wen Zhu; Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Yan-Ge Li; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Multiscale adaptive fusion network for joint classification of hyperspectral and LiDAR data - Haizhu Pan; Weiwei Zhao; Haimiao Ge; Hui Yan; Cuiping Shi (International Journal of Remote Sensing, 2025)

Comparative analysis of phytoplankton community structure and stability in the Arabian Sea and Bay of Bengal using eDNA metabarcoding - Changwen Li; Ge Xiao; Han Long; Tongxi Ai; Fenghua Tang; Jianfeng Ju; Shenglong Yang; Yan Pi; Lei Gao; Lingbo Ma; Wei Fan; Ming Zhao; et al. (Marine Environmental Research, 2025)

Nitrogen doping enhances PMS activation by MnFe2O4-NBC through generating active sites and establishing an internal electric field - Xiaoni Lin; Qiang Ge; Xianbo Zhou; Yan Wang; Congyun Zhu; Kuanyong Liu; Jinquan Wan (Journal of Water Process Engineering, 2025)

Activation of peroxymonosulfate for enhanced antibiotic removal using OVs-Co3O4/Fe2O3: Synergistic modulation of heterostructure and oxygen vacancy - Chaoyun Wang; Jialiang Zhou; He Wang; Jingjie Ge; Qun Yan (Journal of Hazardous Materials, 2025)

Edge nucleation and bridging effect synergistically in-situ sealed multiple heavy metals in soils - Gu Gaoyuan; Zhang Jianing; Zhou Yan; Ge Ruijie; Li Wenhui; Peng Chong; Wang Yuanfei; Bi Changlong; Yang Shuyi; E Tao (Journal of Hazardous Materials, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

Efficient extraction of platinum with benzo-18-crown-6 in a potassium halide based system - Chao Yao; Tao Ge; Liang Xu; Yan Sun; Ao Cai; Cheng Yang; Yongpan Tian; Zhuo Zhao (Journal of Environmental Management, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

The research progress of Ganoderma as a medicinal and edible product - Meilin Wang; Ding Li; Xu Gao; Xinze Wang; Li Zhang; Jiaxin Ding; Ke'er Xuan; Ge Wang; Yan Bai; Jian Gong (Food Bioscience, 2025)

Role of circular RNAs in formaldehyde-induced lung Injury: Insights into expression and regulatory pathways - Pan Ge; Xiang Zhang; Yan-qi Yang; Jia-ming Xie; Mo-qi Lv; Ying Sun; Ya-zhao Li; Yuan-yuan Geng; Jian Zhang; Dang-xia Zhou (Food and Chemical Toxicology, 2025)

Oral administration of nanozyme-armed probiotic Escherichia coli Nissle 1917 with ROS scavenging for inflammatory bowel disease therapy - Tiantian Cui; Bing Li; Zhaoyang Lou; Kai Yang; Kaijin Yan; Danhong Ding; Hong Ge (Chemical Engineering Journal, 2025)

Properties of rich-Nae effect and reversible oxygen redox with a complete solid-solution sodium-storage behavior - Wei Zhao; Shao-Hua Luo; Yicheng Lin; Guodong Hao; Rui Huang; Pengyu Li; Ge Wang; Jun Cong; Shengxun Yan; Lixiong Qian (Chemical Engineering Journal, 2025)

Preliminary Inventory and Assessment of the Geological Heritage of the Origin of Chinese Lingbi Stone - Weilun Kong; Yunhuai Li; Kongliang Li; Jun Chen; Degao Wang; Mo Chen; Yan Peng; Lijun Chen; Linghong Ge; Huiju Wu; Jifei Hu (Geoheritage, 2025)

Effect of the new fixed-time artificial insemination technology based on novel hormone preparations in gilts - Kexiong Liu; Hanbing Zhang; Xiaoling Xu; Zheng Huang; Feng Ji; Yusheng Qin; Linli Xiao; Shiwen Chen; Miaomiao Yan; Peng Zhao; Suozi Ge; Jiani Shu; et al. (Animal Reproduction Science, 2025)

Optimal Fluoride Concentration in Drinking Water for Preventing Dental Fluorosis and Caries in 8–12-Year-Old Children in Qingdao, China: A Restricted Cubic Spline and Spatial Epidemiological Analysis Following Rural Safe Drinking Water Interventions in Endemic Fluorosis Region - Xiaojuan Dou; Xiaoyi Liu; Shitao Liu; Changxun Ge; Shirui Yan; Di Wu; Xinyue Meng; Xinxiao Li; Junrui Pei; Fengying Ji (Biological Trace Element Research, 2025)

Symmetrical response of plant diversity but asymmetrical response of biomass production to rainfall reduction and addition in global grasslands - Ge Li; Xu-Long Zhang; Josep Peñuelas; Jordi Sardans; Ying Zhao; Yan Yu; Jian-Sheng Ye (Plant and Soil, 2025)

Two undescribed compounds from Aspergillus Niger , an endophytic fungus isolated from Camellia flavida - Siyuan Ma; Li Ge; Hongyu Lu; Jianhua Yan; Kedi Yang (Natural Product Research, 2025)

Isolation and characterization of a marine strain: Bacillus inaquosorum, and its feeding effects on Sebastes schlegelii as feed additive - Xin-Kun Zhu; Ren-Ge Hu; Wei Cong; Yuan-Huan Kang; Li-Yan Wang; Tao Yang; Shu Li (Aquaculture, 2025)

Advanced performance and operational strategies of partitioned anaerobic membrane bioreactor combined with ferromagnetic biochar for pesticide wastewater treatment at low-temperature and insufficient hydraulic load - Yifan Wang; Liwen Jiang; Dongxue Hu; Bei Jiang; Hui Ge; Shiming Cui; Shuya Zhuang; Jitao Yan; Zihan Wang; Pengcheng Zhang; Zhibo Liang; Zhaobo Chen (Water Research, 2025)

A new strategy for removing insecticide etoxazole from soil using a combination of a novel Paracoccus versutus Y4 and a fungal mycelium carrier - Man Xu; Xue Luo; Xin-Li Yan; Xiao-Yu Cai; Lin-Lin Wang; Feng Ge; Hong-Wei Wang (Journal of Hazardous Materials, 2025)

Sparingly-soluble CaCO3 promotes plant growth and arsenic accumulation in As-hyperaccumulator Pteris vittata: Oxidative stress and gene expression in As metabolisms - Yu-Fei Yang; Shu-Fen Xiao; Chun-Yan Hu; Qian-Yu Zhou; Chen-Jing Liu; Song-Ge Deng; Lena Q. Ma (Journal of Hazardous Materials, 2025)

Weathering and recycling controls on rare earth element behavior: A comparative study on granitic, basaltic and aeolian red soil crusts - Long Han; Bin Lü; Chaoqiang Li; Jiao Yang; Wenjing Ge; Jianlei Gao; Xingxing Wang; Yan Zheng (Geochimica et Cosmochimica Acta, 2025)

Transcriptome analysis reveals the molecular mechanisms of the 8-day infection cycle of Ecytonucleospora hepatopenaei in Litopenaeus vannamei and the host's molecular responses - Yan Rong; Yi Qiao; Tingyue Liu; Xiaohui Cao; Ge Jiang; Jie Cheng; Huiwen Jiang; Xianping Fan; Hui Shen (Fungal Biology, 2025)

Use of stable isotopic signatures and fatty acid profiles to authenticate Chinese mitten crab (Eriocheir sinensis) reared in ponds and rice fields - Cui Han; Yujing Xiao; Zhongqi Dai; Lei Feng; Yan Shi; Xiaojie Liu; Jiachun Ge; Jiaxin Yang (Food Control, 2025)

Electrochemical degradation of toluene-2,4-diamine by graphene oxide-modified Ti/Sb-SnO2/α-PbO2/β-PbO2 anode: Performance and mechanism - Shuaishuai Man; Jun Zhang; Hebin Bao; Yifan Ge; Youcun Bai; Xinyu Liu; Ziyang Li; Liwei Qiu; Zhenzhen Zhao; Qun Yan (Environmental Research, 2025)

Village ponds are hotspots of CO2 and CH4 emissions regulated by biological communities - Zhengkui Ge; Zhifeng Yan; Mike Peacock; Baoxuan Chang; Yunyun Zhang; Wenxin Wu; Si-Liang Li; David Bastviken; Cong-Qiang Liu (Environmental Pollution, 2025)

Study on the separation of nitric acid and acetic acid using multi-stage electrodialysis - Xiao Ge; Baole Li; Xiang Meng; Tiansheng He; Tianchi Li; Qi Yang; Zheng Wei; Taihong Yan; Zhongwei Yuan (Desalination, 2025)

Relationship between internal void ratio and morphological parameters of carbonate sand - Yan Qian; Yuedong Wu; Yuzhe Ren; Yi Pik Cheng; Abraham C.F. Chiu; Jian Liu; Tiange Ge (Computers and Geotechnics, 2025)

Fixed-point cleaved bioinspired nanosystem via promoting LAT1-mediated BBB penetration for spatiotemporal therapy in TMZ resistant glioblastoma - Xiaofei Gu; Ji Liu; Hongguang Xiang; Ruixi Liao; Yizhi Ge; Davaadagva Damdinjav; Buyankhishig Dorjsuren; Tianjiao Hao; Daquan Chen; Yu Tian; Yan Shen (Chemical Engineering Journal, 2025)

Rare earth ions-reinforced polycationic gel polymer electrolytes for enhancing ionic conductivity and zinc anode interface stability in flexible zinc-air batteries - Hang Zhang; Jianrong Liang; Ziran You; Ying Gao; Yachu Song; Junjie Ge; Yanhao Duan; Xingchen Yan; Da Lei; Chuanling Si; Zhengzheng Li (Chemical Engineering Journal, 2025)

Prolonged drought from winter to spring affected the phenology, growth, and physiology of differently pretreated Pinus sylvestris var. mongolica seedlings - Fang Zheng; Hui Qian; Yan Liu; Yu-Lan Ge; Bao Di; Jouni Kilpeläinen; Ai-Fang Wang (Trees, 2025)
Key message Continuing drought from winter to spring delayed the spring bud phenology of seedlings, and seedlings experiencing colder winter previously were less influenced by the severe drought. Abstract Water availability at the beginning of the growth phase, and even before it, is decisive in the phenology and annual cycle of forest trees, consequently affecting carbon sequestration and forest ecosystem balance. This is a novel experimental study on the effects of continuous drought throughout winter and early spring on tree performance. Two groups of Pinus sylvestris var. mongolica seedlings were overwintered in a Chinese solar greenhouse (BIG seedlings) and a plastic tunnel (SMALL seedlings). The seedlings were subjected to continuing droughts from winter to an extra 0 (control), 15 (D15), 30 (D30) and 45 days without irrigation (D45) after soil thawing next spring. Bud phenology, tree growth and physiology were examined. Bud phenological development, tree aboveground growth and root biomass growth were delayed in treatments D30 and D45 in both seedling types. SMALL seedlings had earlier bud phenology and were less influenced by drought than BIG seedlings. The drought-induced changes in spring phenology were associated with higher ABA and lower GA3 concentrations of needles. The phenology and growth differences between the seedling types might relate to soluble sugar concentrations of roots, needle chlorophyll content, needle chlorophyll fluorescence and acclimated morphological changes, such as root-shoot ratio. We suggest that in forest management, a big seedling size does not guarantee growth success, but attention should be paid to the proper conditions in overwintering and storing of the seedlings prior planting. Prolonged drought throughout winter and early spring should be avoided especially before planting the seedlings in an area prone to drought.

The synergistic impact of cadmium and the wheat rhizosphere on the soil bacterial community in alkaline cropland in Northern China - Wenjing Ge; Fukun Gao; Jianlei Gao; Junxiang Ding; Long Han; Jing Wang; Tengyun Zhang; Hongli Li; Yixin Yan (Journal of Soils and Sediments, 2025)

Human Health Impact from Nonferrous Metal Mining: Exposure Risk with Hair as Biomarkers and the Associated Influencing Factors - Xueming Zheng; Feng He; Xiaoping Li; He Shen; Danqian Shi; Qishang Zhou; Shuang Zhang; Tunyang Geng; Yueheng Jiang; Pengyuan Jin; Xuelian Kui; Huimin Liu; et al. (Exposure and Health, 2025)

Deep plowing enhanced soil nematode communities and soil quality in dryland wheat fields on the Loess Plateau of China - Yuejing Qiao; Duo Gao; Yaqi Fan; Lijing Zhang; Qiuyan Yan; Laichun Guo; Junyong Ge; Tingmiao Huang (Agriculture, Ecosystems & Environment, 2025)

Two undescribed coumarins from Hansenia weberbaueriana - Yixiao Pan; Mengdan Liu; Yunjie Hu; Chenyi Yan; Dale Guo; Ge Kuang (Natural Product Research, 2025)

Did the bumper sticker piss you off? The mediating roles of blame judgement and negative emotion between slogans and aggressive driving behaviour - Jiayan Yu; Yan Ge; Xuchi Luo; Weina Qu (Travel Behaviour and Society, 2025)

Genetic mapping of quantitative trait loci conferring resistance to race 4 of Xanthomonas campestris pv. campestris in cabbage (Brassica oleracea var. capitata) - Qingguo Sun; Liang Yan; Changjun Ge; Jinlan Li; Junfen Dai; Hao Ding (Physiological and Molecular Plant Pathology, 2025)

Experimental study on the hydrodynamic behavior of a floating Fishery–Photovoltaic complementary structure - Sida Xie; Chao Ma; Zhan Zhang; Yun-Peng Zhao; Jia-Qing Shu; Xiao-Feng Ge; Yan-Qian Sun (Ocean Engineering, 2025)

Tectono-stratigraphic evolution of multiphase rifts in a hangingwall dip-slope setting: A case study in Eocene western slope, Xihu Sag of East China Sea Shelf Basin - Xuesong Zhou; Xiaoming Zhao; Jiawang Ge; Massine Bouchakour; Guofeng Yin; Jianwei Wang; Shumei Yan; Xian Liu (Marine and Petroleum Geology, 2025)

Ultra-sensitive, versatile and portable detection of hydrazine in eco-environmental systems using a smartphone-integrated ratiometric fluorescent sensor - Xiao-Hong Li; Meng-Zhao Li; Xiao-Yan Yang; Tian-Yan Wang; Yin-Heng Luo; WMWW Kandegama; Jing-Yi Li; Ge-Fei Hao; Chun-Rong Liu (Journal of Hazardous Materials, 2025)

Evolution of velocity and temperature profiles in very dense granular flows: Insights from ring-shear experiments - Yi Ge; Wei Hu; Gonghui Wang; Yan Li; Li Zhou; Yangshuai Zheng (Engineering Geology, 2025)

YOLO-CWD: A novel model for crop and weed detection based on improved YOLOv8 - Chaoran Ma; Ge Chi; Xueping Ju; Junqiang Zhang; Changxiang Yan (Crop Protection, 2025)

Integrated transcriptomic and metabolomic analysis reveals molecular mechanisms of infectious myonecrosis virus (IMNV) pathogenesis in Litopenaeus vannamei muscle tissue - Yan Rong; Yi Qiao; Xiaohui Cao; Ge Jiang; Jie Cheng; Huiwen Jiang; Hui Shen (Aquaculture, 2025)

Heat-triggered CRISPR/Cas12a microspheres for one-pot assays - Siying Xie; Shan Shao; Jin Wang; Jing Qu; Ying Cai; Xingyan Lai; Nan Min; Lidan Zhang; Yan Shi; Tingdong Li; Xiaomin Zhang; Bo Peng; et al. (Science Bulletin, 2025)

Diketopiperazine and purine alkaloids from the tubers of Pinellia pedatisecta Schott and their protective activities against Aβ25-35-induced PC-12 cell injury - Xu Chen; Yan-gang Cao; Feng-xiao Hao; Yan-ling Liu; Fang-ge Chi; Ying Niu; Di Lu; Bing-xian Zhao; Lan Chen; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2025)

Self-assembly of algal-bacterial granules induced by bacterial N-acyl-homoserine lactone variation in response to high-strength pyridine - Xinying Hou; Dan Chen; Yan Li; Xiaoyu Zhang; Shijian Ge; Xinbai Jiang; Jinyou Shen (Journal of Hazardous Materials, 2025)

Construction of γ-Fe2O3 based colorimetric sensing arrays through the phase transformation induced by rare-earth doping for the detection of antibiotics in water environments - Minghui Li; Jiayi Huang; Ruyue Deng; Yongkang Yan; Wei Zhang; Danhua Ge; Xiaojun Chen (Journal of Environmental Chemical Engineering, 2025)

One-step controllable synthesis of N-doped porous carbon derived from ZIF-8 for efficient capacitive deionization - Pin Hou; Jiaqi Yan; Xiaoyu Yang; Ridha Djellabi; Xinrui Ge; Xinyu Sun; Jianli Jia; Jianbing Wang (Journal of Environmental Chemical Engineering, 2025)

Edible starch-based films modified by fruit and vegetable juices: Preparation, performance evaluation and seasoning bag design - Xinyu Sun; Guocong Ma; Xiaoling Tian; Dan Hai; Yan Ma; Ge Bai; Lianjun Song; Qinghua Yang; Xianqing Huang (Food Packaging and Shelf Life, 2025)

pH/GSH-Driven inside-out nanoreactor initiating copper(I)-precursor chelation-promoted bioorthogonal therapy - Zhexiang Wang; Xinyi Li; Rui Lv; Ruochen Guo; Qinglei Shu; Tianjin Ge; Jun Yan; Zhihao Zhao; Guanghui Wang; Jian Liu (Chemical Engineering Journal, 2025)

Breaking activity-selectivity trade-off by fabricating Pdδ+-SnOx dual sites for direct synthesis of H2O2 aqueous solution - Ruilin Liu; Yueshuai Wang; Yong Yan; Yue Lu; Ge Chen (Chemical Engineering Journal, 2025)

Glymphatic Impairment Associated with Neurocognitive Dysfunction in Moyamoya Disease - Chaofan Zeng; Yuanren Zhai; Peicong Ge; Chenglong Liu; Xiaofan Yu; Wei Liu; Junsheng Li; Qiheng He; Xingju Liu; Xun Ye; Qian Zhang; Rong Wang; et al. (Translational Stroke Research, 2025)

Explainable machine learning-based land subsidence susceptibility mapping: from feature importance to individual model contributions in ensembled system - Bofan Yu; Huaixue Xing; Weiya Ge; Jiaxing Yan; Yun-an Li (Earth Science Informatics, 2025)

Monitoring phycocyanin in global inland waters by remote sensing: Progress and future developments - Chong Fang; Kaishan Song; Zhaojiang Yan; Ge Liu (Water Research, 2025)

The role of ATG7-mediated ferroptosis in formaldehyde-induced ovarian injury in rats - Kun Mao; Hao-zhe Yan; Jia-qi Yang; Zi-xin Yin; Xin-qi Gao; Hao-fu Liu; Heng Su; Yuan-yuan Geng; Pan Ge; Dang-xia Zhou (Reproductive Toxicology, 2025)

Lead seasonality: Affect children’s blood lead levels and implication for lead exposure prevention - Jie Dong; Xiaoping Li; Yu Zhang; Xueming Zheng; Shuang Zhang; Qishang Zhou; Feng He; Danqian Shi; Yueheng Jiang; He Shen; Xu Zhang; Ge Ma; et al. (Journal of Hazardous Materials, 2025)

The influence mechanism of environmental factors on DGT adsorbing sulfonamides and the migration between water and sediment - Peng Zhang; Jingfeng Yan; Hao Ji; Linke Ge; Yanying Li (Journal of Environmental Sciences, 2025)

Hysteretic behavior of resilient hinged wall enhanced with FRP bars - Yan Zhang; Longhe Xu; Xingsi Xie; Ge Zhang (Engineering Structures, 2025)

Experimental and simulation study on the performance of corrugated plate enhanced solar chimney power plant combined with distillation system - Lu Zuo; Chenkai Xiao; Ziyang Yan; Zinan Guo; Long Huang; Yunting Ge (Desalination, 2025)

Lanthanum-mediated enhancement of low temperature hydrogenation activity and stability in nickel catalyst supported by MOFs - Zhiyuan Liu; Yan Gao; Changan Wang; Yuanjie Zhang; Hongyi Gao; Ping Yang; Siqi Liu; Juan Chen; Zhimeng Liu; Jingjing Wang; Xinmeng Xu; Ge Wang (Chemical Engineering Journal, 2025)

Integrated learning framework for enhanced specific surface area, pore size, and pore volume prediction of biochar - Chao Chen; Yongjie Hu; Yadong Ge; Junyu Tao; Beibei Yan; Zhanjun Cheng; Xuebin Lv; Xiaoqiang Cui; Guanyi Chen (Bioresource Technology, 2025)

Non-invasive Modulation of Deep Brain Nuclei by Temporal Interference Stimulation - Long Li; Hao Bai; Linyan Wu; Liang Zheng; Liang Huang; Yang Li; Wenlong Zhang; Jue Wang; Shunnan Ge; Yan Qu; Tian Liu (Neuroscience Bulletin, 2025)

Crosstalk Between Mitochondrial DNA and Immune Response: Focus on Autism Spectrum Disorder - Wenxuan Qu; Ge Yan; Yajuan Du; Xinyang Zhou; Chutian Huang; Bei Li; Junmei Zhou; Qian Li (Molecular Neurobiology, 2025)

Anti-hypoxia polyacetylenes and sesquiterpenoids from Codonopsis pilosula (Franch.) Nannf - Zhuo-Yang Cheng; Jun-Ge Jin; Meng Yan; Xin-Yue Chen; Jian-Kuan Li; Jian-Ping Gao; Jiang-Tao Zhou (Natural Product Research, 2025)

Associations between air pollutants and emergency ambulance dispatches for all-cause and nervous system disease in China Qingdao: a time-stratified case-crossover study - Yang Yu; Bingling Wang; Lu Pan; Nan Ge; Xiaocheng Gu; Yuan Fang; Hua Zhang; Jianjun Zhang; Yan Ma; Haiping Duan (Environmental Monitoring and Assessment, 2025)

Revisiting urban heat island effects in China: Multi-satellite evidence from the ESA-CCI land surface temperature product - Xing Li; Xiao Li; Hedi Ma; Juan Zhou; Fei Ge; Wanxin Zhang; Yan Yan; Yijing Zhou (Sustainable Cities and Society, 2025)

Efficient preparation of potassium humate from waste vegetable leaves: Development of a Cu2O@HAK catalyst and innovative application of hydrothermal method - Jiamin Qi; Jiliang Zheng; Yatang Dai; Bo Yang; Haohao Bian; Xinyu Chen; Shunyu Yin; Xiuling Yan; Xiaoyan He; Hongguang Zhao; Yanjie Ren; Changchun Ge; et al. (Journal of Environmental Chemical Engineering, 2025)

Improvement of electrochemical water softening treatment using activated carbon plates in high hardness and low alkalinity water: Enhancing the electrochemical treatment effect while reducing the corrosiveness of the water - Junwei Wang; Xuhui Wang; Dengjia Yuan; Min Xu; Ziyu Yan; Honghua Ge (Journal of Environmental Chemical Engineering, 2025)

Gelling properties and formation mechanism of blueberry pomace polysaccharide gels induced by calcium ions - Yuanfei Ge; Yan Zhang; Ting Peng; Liuqing Yang; Xiaomin Li; Chuyan Wang (Food Chemistry, 2025)

Chemical characterization and classification of vegetable oils using DESI-MS coupled with a neural network - Yiwei Cui; Liangcun Zhu; Yan Li; Kai Ge; Weibo Lu; Lijun Ge; Kang Chen; Jing Xue; Feiyang Zheng; Shuncong Dai; Huafei Pan; Jingjing Liang; et al. (Food Chemistry, 2025)

Aquatic photochemistry for different dissociation forms of cephalosporin antibiotics: Degradation kinetics, products and photo-modified toxicity - Linke Ge; Yadi Guo; Qing Xie; Yan Yang; Peng Zhang; Jiahong Wang; Yunqing Zhu (Environmental Pollution, 2025)

A novel anaerobic membrane bioreactor with magnetotactic bacteria for organic sulfur pesticide wastewater treatment: Improvement of enzyme activities, refractory pollutants removal and methane yield - Shiming Cui; Dongxue Hu; Zhaobo Chen; Yifan Wang; Jitao Yan; Shuya Zhuang; Bei Jiang; Hui Ge; Zihan Wang; Pengcheng Zhang (Chemical Engineering Journal, 2025)

Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Myeloid-derived suppressor cells alleviate adverse ventricular remodeling after acute myocardial infarction - Yan-Ge Wang; Ding-Hang Wang; Wen-Hui Wei; Xin Xiong; Jing-Jing Wu; Zhan-Ying Han; Long-Xian Cheng (Molecular and Cellular Biochemistry, 2025)

Development of potential intron polymorphic (PIP) markers in melon (Cucumis melo L.) - Rui Sun; Yan-Ge Li; Ding-Ding Zuo; Meng-Ling Zheng; Jing Zhang; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Rational design of a near-infrared fluorescent probe for rapid monitoring of carboxylesterase in live cells and drug-induced liver injury mice - Weitao Xing; Kaili Yang; Yonglong Zhu; Xinyi Li; Yan Zhang; Linxia Guo; Jing-Yuan Ge; Yang Bai; Zhongyan Chen (Analytica Chimica Acta, 2025)

Overexpression of PIK3CG in Cancer Cells Promotes Lung Cancer Cell Migration and Metastasis Through Enhanced MMPs Expression and Neutrophil Recruitment and Activation - Jinpeng Sun; Zhenshan Zhang; Binghui Xia; Tianyu Yao; Fengyue Ge; Fengmei Yan (Biochemical Genetics, 2025)

PLAGL2-STAU1-NCOA4 axis enhances gastric cancer peritoneal metastasis by resisting ferroptosis via ferritinophagy - Shansong Huang; Peicheng Ji; Peng Xu; Kanghui Liu; Han Ge; Zhengyuan Yan; Quan Cheng; Jialun Lv; Diancai Zhang (Apoptosis, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

STC2 regulates the proliferation, migration and glycolysis of glioma cells through modulating ITGB2 - Zefeng Wei; Dengfeng Ge; Jie Bu; Xuenan Wang; Tao Zhong; Xiaoxiao Gongye; Bin Zhang; Feng Yan; Chunyan He; Runhan Guo; Jiayi Li; Zhenzhen Jin (Metabolic Brain Disease, 2025)

Chinese chestnut did not induce negative plant soil feedback during centuries of growth - Xu Cheng; Zhichun Yan; Qian Li; Lucas Schmitz; Jundi Yan; Yueyang Ge; Yanping Lan; Yaceng Zhao; Yiyang Wang; Guangdong Li; Yang Liu; Martinus Schneijderberg; et al. (Science of The Total Environment, 2025)

RNA interference targeting β-N-acetylhexosaminidase genes impairs molting and development of Tetranychus urticae - Ming Liu; Qianwen Wang; Bin Lai; Yan Chen; Rongchumu Ge; Shuo Yan; Chunya Bu (Pesticide Biochemistry and Physiology, 2025)

Trends and emerging hotspots in RNAi-based arthropod pest control: A comprehensive bibliometric analysis - Wenbin Liu; Xinyu Wang; Anmo Zhou; Junyu Zhang; Xinyu Ge; Bernard Moussian; Chuncai Yan; Shaobo Gao; Yiwen Wang (Journal of Insect Physiology, 2025)

Environmental DNA metabarcoding: Current applications and future prospects for freshwater fish monitoring - Shuaishuai Liu; Juan Chen; Ge Cui; Bo Zhang; Bingcheng Yan; Qihao Nie (Journal of Environmental Management, 2025)

Interactions between the co-contamination system of oxcarbazepine-polypropylene microplastics and Chlorella sp. FACHB-9: Toxic effects and biodegradation - Hao Zhang; Baoming Liu; Fengjie Sun; Ziqi Zhang; Yifan Kong; Xiang Liu; Yulin Cui; Yuyang Ma; Yuyong Wu; Jianhua Fan; Baosheng Ge; Yan Cheng; et al. (Journal of Environmental Management, 2025)

Interactive effects of air pollutants and viral exposure on daily influenza hospital visits in Mongolia - Yihui Ge; Yan Lin; Oyu Tsogtbayar; Ser-Od Khuyagaa; Eelin Khurelbaatar; Jargalsaikhan Galsuren; Lauren Prox; Shiyu Zhang; Robert M. Tighe; Gregory C. Gray; Junfeng Zhang; Daramragchaa Ulziimaa; et al. (Environmental Research, 2025)

Heterogeneous Fenton-like catalysts of tetranitro iron phthalocyanine@Fe3O4@fly ash composites for fast decomposition of environmental contaminants - Dapeng Li; Peng Zhang; Yang Jin; Qing Li; Xinyuan Li; Ruirui Chang; Ruoxi Ma; Lin Yan; Suxiang Ge; Juntao Ma (Waste Disposal & Sustainable Energy, 2025)
Using fly ash (FA) solid wastes as economical carriers to construct Fenton-like catalytic composites with additional functions is more practical than the use of a single catalyst. Understanding the structure and properties of catalysts and carriers is vital to improve performance. Tetranitro iron phthalocyanine (TNFePc) is a highly active molecular catalyst, whose immobilization and Fenton-like heterogeneous catalysis remain unclear. In this study, magnetically recyclable composites of TNFePc@Fe 3 O 4 @FA were successfully fabricated. Further, Fe 3 O 4 nanocrystals decorated on FA surfaces could be used as special functional layer for composite recycling and simultaneous in situ TNFePc synthesis. Peroxides of H 2 O 2 , KHSO 5 , and tert-butyl hydrogen could be effectively activated by composites and transformed into highly reactive radicals. Moreover, molecular oxygen could be activated as well. Model pollutants, methylene blue and oxytetracycline, could be synergistically degraded by the radical oxidation of superoxide, hydroxyl, alkoxy, and sulfate radicals and non-radical oxidation of high-valent iron-oxo species of TNPcFe IV =O. To the best of our knowledge, this is the first design of FA-based composites with dual function, Fenton-like heterogeneous catalysis and magnetic recyclability, for environmental decontamination. Graphical abstract

Correction to: Scorpion Venom Heat-Resistant Peptide is Neuroprotective Against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2025)

The Cytidine N-Acetyltransferase NAT10 Promotes Thalamus Hemorrhage-Induced Central Poststroke Pain by Stabilizing Fn14 Expression in Thalamic Neurons - Tianfeng Huang; Yang Zhang; Yan Niu; Yinggang Xiao; Yali Ge; Ju Gao (Molecular Neurobiology, 2025)
The recognition of RNA N4-acetylcytidine (ac4C) modification as a significant type of gene regulation is growing; nevertheless, whether ac4C modification or the N-acetyltransferase 10 protein (NAT10, the only ac4C “writer” that is presently known) participates in thalamus hemorrhage (TH)-induced central poststroke pain (CPSP) is unknown. Here, we observed NAT10 was primarily located in the neuronal nuclei of the thalamus of mice, with Fn14 and p65. An increase of NAT10 mRNA and protein expression levels in the ipsilateral thalamus was observed from days 1 to 14 after TH. Inhibition of NAT10 by several different approaches attenuated Fn14 and p65 upregulation of TH mice, as well as tissue injury in the thalamus on the ipsilateral side, and the development and maintenance of contralateral nociceptive hypersensitivities. NAT10 overexpression increased Fn14 and p65 expression and elicited nociceptive hypersensitivities in naïve mice. Our findings suggest that ac4C modification and NAT10 participate in TH-induced CPSP by activating the NF-κB pathway through upregulating Fn14 in thalamic neurons. NAT10 could serve as a promising new target for CPSP treatment.

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

Analysis of near-fault ground motions in the February 2023 Kahramanmaras, Türkiye, earthquake sequence - Zhiwang Chang; Haoran Wu; Wanheng Li; Zhenxu Yan; Longqiang Peng; Ge Zhu (Bulletin of Earthquake Engineering, 2025)

Investigation on neutronics changes in tungsten granular blockage accident on VENUS-II light water reactor - Liang Chen; Wei Jiang; Zhao-Dong Xia; Fei Ma; Rui Yu; Hai-Yan Meng; Qi Zhou; Hong-Lin Ge; Yan-Bin Zhang; Xue-Ying Zhang (Annals of Nuclear Energy, 2025)

A new palynological assemblage of the Nantun Formation in the Huhehu Sag, Hailar Basin, NE China: Implications for paleoenvironments - Yan Zhang; Yun-fei Xue; Chuan-biao Wan; Wen-chun Ge (Cretaceous Research, 2025)

First report of alfalfa mosaic virus infecting Potentilla anserina L. in China - Miaomiao He; Zhengnan Li; Mengze Guo; Ge Yan; Fenghua Cheng; Jian Wang; Junqiao Li (Journal of Plant Pathology, 2025)

Improving the mechanical properties of magnesium oxychloride cement by incorporating oyster shell powder - Zhi-hai He; Bin Wang; Jin-yan Shi; Xin-ge Wu; Hong-yu Tao; Ahmed Salah Jamal (Sustainable Chemistry and Pharmacy, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Moxifloxacin plus Cordyceps polysaccharide ameliorate intestinal barrier damage due to abdominal infection via anti-inflammation and immune regulation under simulated microgravity - Hong-Yun Nie; Jun Ge; Kai-Ge Liu; Yuan Yue; Hao Li; Hai-Guan Lin; Tao Zhang; Hong-Feng Yan; Bing-Xin Xu; Hong-Wei Sun; Jian-Wu Yang; Shao-Yan Si; et al. (Life Sciences in Space Research, 2025)

Using machine learning to predict soil lead relative bioavailability - Shuang Zhang; Xiaoping Li; Tunyang Geng; Yu Zhang; Weixi Zhang; Xueming Zheng; He Sheng; Yueheng Jiang; Pengyuan Jin; Xuelian Kui; Huimin Liu; Ge Ma; et al. (Journal of Hazardous Materials, 2025)

Preparation of wood formaldehyde-free adhesive by concentrated water delignification black liquor - Ting Zhang; Jianli Tan; Yongqi Li; Yexuan Tang; Yan He; Yuanyuan Ge; Xuemin Cui (Journal of Cleaner Production, 2025)

The in-vitro digestibility of instant noodles: Interplay of texture, microstructure and starch structure - Caili Li; Zeping Shao; Jin Wang; Hongying Hua; Ge Li; Yan Zhang; Shuo Wang (Food Research International, 2025)

Enhancing whipped cream anti-freeze properties: A dual plant system with aquafaba and mung bean protein - Yan Zhan; Lai Wei; Tianai Ge; Da Chen; Li Wang; Jiang Jiang (Food Hydrocolloids, 2025)

lafK contributes the regulation of swarming motility of Pseudomonas plecoglossicida and bacterial-host interaction - Li He; Meiqin Mao; Hui Ge; Jiaonan Zhang; Jiaolin Zhang; Qingpi Yan (Fish & Shellfish Immunology, 2025)

Associations of preconception air pollution exposure with growth trajectory in young children: A prospective cohort study - Jiawen Liao; Weili Yan; Yi Zhang; Kiros Berhane; Wu Chen; Zhenchun Yang; Chenyu Qiu; Yihui Ge; Zhipeng Bai; Bin Han; Jia Xu; Yong-hui Jiang; et al. (Environmental Research, 2025)

Integrating Ni2P crystalline-NiFeBP amorphous heterojunction nanosheets on hierarchical nickel foam for superior overall water splitting - Guang-Lan Li; Fei Deng; Tian-Ge Ma; Yu-Hui Shi; Junyan Liu; Yang Yan; Qing Mao; Junjiang Bao (Chemical Engineering Journal, 2025)

Influences of urban shape on city-scale heat and pollutants dispersion under calm and moderate background wind condition - Yan Zhang; Yifan Fan; Jian Ge (Building and Environment, 2025)

Electrostatic repellent dispersion method for green and cost-effective aqueous radiative cooling paint - Jipeng Fei; Di Han; Kai Zhou; See Wee Koh; Junyu Ge; Jun Yan Tan; Bing Feng Ng; Zhong Chen; Lili Cai; Hong Li (Building and Environment, 2025)

Controlled oxidative decomposition of rice husk to induce formation of hierarchically meso-macroporous carbon foams with unprecedented porosity - Hao Wu; Jun Yang; Ge Yang; Pingping Wu; Wei Xing; Peng Bai; Zifeng Yan (Biomass and Bioenergy, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Mechanism of acclimation to chronic intermittent hypoxia in the gills of largemouth bass (Micropterus salmoides) - Qiao Liu; Hong Wang; Jiayu Ge; Lipeng Guo; Rabia Tahir; Jie Luo; Kuo He; Haoxiao Yan; Xin Zhang; Quanquan Cao; Zhang Cheng; Liulan Zhao; et al. (Fish Physiology and Biochemistry, 2025)

Counting wheat heads using a simulation model - Xiaoyong Sun; Tianyou Jiang; Jiming Hu; Zuojie Song; Yuheng Ge; Yongzhen Wang; Xu Liu; Jianhao Bing; Jinshan Li; Ziyu Zhou; Zhongzhen Tang; Yan Zhao; et al. (Computers and Electronics in Agriculture, 2025)

Fomesafen induced ecotoxicological responses, bioaccumulation, and implications for soil ecosystems remediation in three ecotypes earthworms - Yan Ge; Siqi Wang; Siqi Miao; Dongxing Zhou (Pesticide Biochemistry and Physiology, 2025)

A comprehensive study on the flow field of cylindrical cavitation nozzle jet under different turbulence models - Yan Xu; Jiajun Tian; Zunce Wang; Jinglong Zhang; Sen Li; Yuejuan Yan; Mingming Ge (Ocean Engineering, 2025)

Phylogenomic analyses shed new light on the spatiotemporal evolution of global larches: Implications for the dynamics of boreal forests - Xiu-Fei Qiu; Yan-Yan Liu; Ge Wu; Cong-Hui Xu; Xin-Quan Liu; Xiao-Yan Xiang; Xiao-Xin Wei; Xiao-Quan Wang (Molecular Phylogenetics and Evolution, 2025)

Isolation and identification of novel hemp seed protein-derived pancreatic lipase inhibitory peptides - Zhenghai Zhang; Jingyi Ge; Lianhui Wei; Jie Shi; Yanru Ji; Xiangyu Xing; Yu Shi; Yan Dong (Food Bioscience, 2025)

Ingenious microfluidic-microwave integrated biosensor for cell sorting and concentration detection of mixed white blood cells and yeasts solution - Yuan-Bo Li; Yan-Xiong Wang; Sen Yang; Qian-Long Chen; Zhong-Hao Li; Jun-Ge Liang; Qi-Gao Fan; Yan-Feng Jiang; Xiaoman Zhou; Tian Qiang (Chemical Engineering Journal, 2025)

Photothermal-thermoelectric synergy coupling localized surface plasmon resonance for enhanced flexible photoelectrochemical sensor performance - Mengqi Chen; Hui Tian; Ling Qi; Yuying Zhang; Hongmei Yang; Shenguang Ge; Lina Zhang; Yan Zhang; Lin Li; Kang Cui; Jinghua Yu (Chemical Engineering Journal, 2025)

7-Hydroxycoumarin and its conjugated metabolites interact with organic anion transporters 1 and 3 in vitro and in vivo - Lijun Luo; Yongchun Chang; Weilin Zhang; Xiao Liu; Junpu Ge; Jieyi Chen; Yan Li; Dan Zhang; Li Sheng (Chemico-Biological Interactions, 2025)

Risk assessment of mold growth on engineered bamboo and its application - Shuqin Chen; Yinyan Lv; Chuqiao Chen; Jingtao Xu; Yan Xiao; Jian Ge (Building and Environment, 2025)

Dissecting the cell microenvironment of ovarian endometrioma through single-cell RNA sequencing - Jiangpeng Wu; Siyu Xia; Wenting Ye; Yan Sun; Jing Cai; Fubing Yu; Haiping Wen; Xiuwei Yi; Taikang Li; Mingwei Chen; Jiayun Chen; Ge Song; et al. (Science China Life Sciences, 2025)

An overview on the legacy and risks of Polychlorinated Biphenyls (PCBs) and Organochlorinated Pesticides (OCPs) in the polar regions - Peng Zhang; Jing Wang; Andrew Sweetman; Linke Ge; Rongguang Xing; Hao Ji; Jingfeng Yan; Qian Xiao; Yaqing Cui; Hongrui Ma; Sisi Xu (Marine Pollution Bulletin, 2024)

Endoplasmic reticulum stress and Ca2+ dysregulation in response to ammonia nitrogen exposure could be alleviated by dietary fermented mulberry leaf meal in Megalobrama amblycephala - Wenqiang Jiang; Linjie Qian; Qiaoqiao Mu; Yan Lin; Siyue Lu; Zhengyan Gu; Huaishun Shen; Xianping Ge; Linghong Miao (Aquaculture, 2024)

Analysis on pollutants removal and sludge characteristics of a novel two-phase anaerobic/aerobic/integrated deoxygenated and anoxic reactor associated with membrane process for treating pesticide wastewater - Shuya Zhuang; Zhaobo Chen; Zhibo Liang; Dongxue Hu; Hui Ge; Bei Jiang; Jian Dong; Fei Han; Jitao Yan; Yifan Wang; Shiming Cui (Science of The Total Environment, 2024)

Trace antibiotic exposure affects murine gut microbiota and metabolism - Chengfei Wang; Liang Zhao; Jian Xu; Xiaowei Li; Saiwa Liu; JingJing Du; Xixi Jia; Zhinan Wang; Lirui Ge; Zuhao Yan; Xi Xia (Science of The Total Environment, 2024)

Late Paleozoic–Early Mesozoic subduction history of Mudanjiang Ocean: New insights from greenschist in the Heilongjiang Complex, NE China - Simiao Wang; Yu Dong; Junhui Bi; Yan Jing; Wenchun Ge; Hao Yang; Jielu Yu; Zheng Ji (Lithos, 2024)

Association between pyrrolizidine alkaloids exposure and risk of abnormal serum indices—Insights from a descriptive cross-sectional study in Yunnan Province - Xiaoxiang Sun; Zhengyuan Xie; Zheng He; Yisheng He; Zigao Zhao; Xuerong Yan; Xiangjing Song; Zijie Chen; Tao Wang; Quanrui Yue; Yiming Chen; Hanfeng Ye; et al. (Journal of Hazardous Materials, 2024)

Bisulfite enhances p-nitrophenol degradation by zero-valent iron under oxic conditions: Combination of indirect reduction by superoxide radical and direct reduction - Guang-En Yuan; Yan-Ge Ma; Kangning Huangfu; Yunbei Li; Xin Zhang; Fenglin Yang (Journal of Environmental Chemical Engineering, 2024)

Use of proteomics to elucidate characteristics of Cronobacter sakazakii under mild heat stress - Yanfei Yan; Mengyuan Cao; Jiaqi Ma; Jia Suo; Xiaobao Bai; Wupeng Ge; Xin Lv; Qiang Zhang; Jia Chen; Shenghui Cui; Baowei Yang (International Journal of Food Microbiology, 2024)

Association of ambient temperature and diurnal temperature range with the outcome of in vitro fertilization in women from Hubei, China: A retrospective cohort study - Guan Cheng; Rui Qu; Ge Song; Xing Li; Feng Zhang; Jingxuan Wang; Wenzhu Li; Jiahui Wen; Yanfei Xiao; Yiqiu Wei; Weiqian Zhang; Xiaofang Yi; et al. (Environmental Research, 2024)

A novel and cost-effective biological denitrification associated with membrane process for treating pesticide wastewater: Excellent nitrogen removal effect and higher environment benefits - Shuya Zhuang; Dongxue Hu; Zhaobo Chen; Zhibo Liang; Junzhe Song; Hui Ge; Bei Jiang; Jian Dong; Fei Han; Jitao Yan; Yifan Wang; Shiming Cui (Desalination, 2024)

Rational design of hierarchical defect-rich NiSe2/Se-NiCuOx heterostructures: Modulating electronic structure for exceptional ammonia oxidation performance - Guang-Lan Li; Tian-Ge Ma; Yu-Hui Shi; Fei Deng; Ri-Yang Huang; Yang Yan; Qing Mao; Yushan Li; Yonghou Xiao (Chemical Engineering Journal, 2024)

Pulsed electrocatalysis: A dynamical route for tailoring electrocatalytic properties from fundamentals to applications - Yan Wang; Haoyu Ge; Yixiang Luo; Xianjun Zhu; Longlu Wang; Dafeng Yan (Chemical Engineering Journal, 2024)

Study on the reactions of n-pentanal and n-hexanal with Br atoms: Kinetics, gas-phase products, and SOA formation - Cici Fan; Huijie Yan; Weigang Wang; Zheng Sun; Maofa Ge (Atmospheric Environment, 2024)

Differential proteomic profiles of exosomes in pediatric and adult adamantinomatous craniopharyngioma cyst fluid - Yiguang Chen; Ziyu Wang; Qin Huang; Yaming Wang; Feng Yan; Sishi Xiang; Lixin Xu; Yongjian Chen; Xiaohai Liu; Ge Chen; Mingchu Li; Yiqiang Zhou (Molecular Biology Reports, 2024)

Assessment of genetic diversity of Camellia yuhsienensis based on leaf structure and inter simple sequence repeat (ISSR) markers - Yuling Zou; Xiaoning Ge; Chao Yan; Qiuping Zhong; Danyang Chen; Zexin Chen; Yaqi Yuan; Hongyan Guo; Youcheng Zhou; Jinfeng Wang; Linqing Cao (Genetic Resources and Crop Evolution, 2024)

CMPK2 Promotes CD4+ T Cell Activation and Apoptosis through Modulation of Mitochondrial Dysfunction in Systemic Lupus Erythematosus - Ya-Nan Tan; Ge-Ge Jiang; Xiang-Wen Meng; Zhi-Yuan Lu; Yan-Ma; Jin Li; Nan-Xiang; Xiao-Ge Sun; Qian Wang; Xue Wang; Xiao-Yi Jia; Min Zhang (Cell Biochemistry and Biophysics, 2024)

Extended Bouc-Wen model identification using shaking table test data of ageing RC bridge piers - Xiao Ge; Yan-Hui Liu; Yu-Qing Yang; Nicholas A. Alexander; Mohammad M. Kashani (Bulletin of Earthquake Engineering, 2024)

Efficient RNA interference method by feeding in Brachionus plicatilis (Rotifera) - Yu Zhang; Dongqi Kan; Yang Zhou; Hairong Lian; Lingling Ge; Jing Shen; Zhongqi Dai; Yan Shi; Cui Han; Xiaojie Liu; Jiaxin Yang (Biotechnology Letters, 2024)

Microbial Diversity Losses Constrain the Capacity of Soils to Mitigate Climate Change - Yan Li; Jianlei Wang; Congcong Shen; Guiyao Zhou; Manuel Delgado‐Baquerizo; Yuan Ge (Global Change Biology, 2024)
Soil microbes may adapt to climate warming, potentially reducing the warming‐induced increase in microbial carbon emissions such as carbon dioxide, and thereby helping to mitigate climate change. Yet, soil microbes are subjected to various global change stresses (e.g., warming, drought, flooding, and land‐use changes), altering their biodiversity, which challenges microbial adaptation to climate change. Here, we created microbial diversity gradients in microcosms at two different temperatures using soils from a 2000‐km field survey. We found that reduced microbial diversity weakens the thermal adaptation of soil microbial respiration and can further enhance the microbial respiratory temperature sensitivity over time. Our analyses further revealed that the negative impact of microbial diversity losses is linked to the decline of keystone microbial taxa, which can adapt to temperature changes and are crucial for the community's ability to compensate for the temperature‐driven effects on soil respiration in the long term. Taken together, our study provides new insights into the key role of microbial diversity in driving the thermal response of soil heterotrophic respiration, suggesting that any global change‐driven shifts in microbial diversity can have critical consequences for the future of carbon stocks.

Sexual differentiation and juvenile hermaphroditism in silver pomfrets: Direction, process, and dietary factors - Yaya Li; Mingzhe Yuan; Peng Shi; Keyan Cai; Jiabao Hu; Man Zhang; Youyi Zhang; Yuanbo Li; Mengke Tang; Zukang Feng; Chunlai Qin; Wei Ge; et al. (Aquaculture, 2024)

Harnessing the plant microbiome for environmental sustainability: From ecological foundations to novel applications - Jing-Ru Hao; Yan Li; Yuan Ge (Science of The Total Environment, 2024)

Electronic textiles for thermal and moisture management - Yan Gao; Yang Li; Xiao Chen; Ge Wang (Science Bulletin, 2024)

Unveiling the pathogenic and multidrug-resistant profiles of Vibrio alfacsensis: A potential identified threat in turbot (Scophthalmus maximus) aquaculture - Ren-Ge Hu; Lei Yang; Li-Yan Wang; Yu-Lin Yang; Hong-Jin Li; Bin-Tong Yang; Yuan-Huan Kang; Zhen-Lin Liang; Wei Cong (Journal of Hazardous Materials, 2024)

Effect of fatty acid composition on the volatile compounds of pasteurized milk during low-temperature storage - Haixia Yan; Wei Huang; Xin Zhao; Chao Ge; Yixiao Shen; Ling Liu (Food Research International, 2024)

Transcriptome and metabolome analyses reveal the effects of formula and breast milk on the growth and development of human small intestinal organoids - Xianli Wang; Yiming Zhong; Chengdong Zheng; Chenxuan Huang; Haiyang Yao; Zimo Guo; Yilun Wu; Zening Wang; Zhengyang Wu; Ruihong Ge; Wei Cheng; Yuanyuan Yan; et al. (Food Research International, 2024)

Global hydroclimate perturbations during the Toarcian oceanic anoxic event - David B. Kemp; Zhong Han; Xiumian Hu; Wenhan Chen; Simin Jin; Kentaro Izumi; Qing Yan; Viktória Baranyi; Xin Jin; Jacopo Dal Corso; Yuzhu Ge (Earth-Science Reviews, 2024)

Carboxyl carbon nanotubes strengthened tailorable chitosan imprinted polymers for selective adsorption of dibenzothiophene in hydrogenated diesel - Ge Niu; Yan Huang; Mingqing Hua; Peiwen Wu; Jingyu Li; Chunman Jia; Yanhong Chao; Zhichang Liu; Wenshuai Zhu (Chemical Engineering Journal, 2024)

Attachment processes of negative flashes with multiple return strokes to a tall tower observed at close distances - Yan Gao; Mingli Chen; Zilong Qin; Zongxu Qiu; Shaoyang Wang; Ge Zhang; Qi Qi; Ya-ping Du (Atmospheric Research, 2024)

Anaerobic degradation of pesticide wastewater: Improving sludge characteristics and reducing membrane fouling with combined tandem UASB+membrane system with high velocity settlers - Jitao Yan; Zhaobo Chen; Dongxue Hu; Hui Ge; Bei Jiang; Jian Dong; Fei Han; Shuya Zhuang; Zhibo Liang; Yifan Wang; Shiming Cui (Water Research, 2024)

Reduction in polycyclic aromatic hydrocarbon exposure in Beijing following China’s clean air actions - Yan Lin; Xiaodi Shi; Xinghua Qiu; Xing Jiang; Jinming Liu; Peiwen Zhong; Yihui Ge; Chi-Hong Tseng; Junfeng (Jim) Zhang; Tong Zhu; Jesus A Araujo; Yifang Zhu (Science Bulletin, 2024)

Interpretable machine learning approaches for damage identification in drilling risers - Zheng-guang Ge; Xingkun Zhou; Yan Li; Xiantao Zhang; Wenhua Li (Ocean Engineering, 2024)

Natural variation in photosynthetic electron transport of wheat flag leaves in response to dark-induced senescence - Cheng Yang; Zishan Zhang; Yuan Yuan; Deqi Zhang; Haiyang Jin; Ying Li; Simeng Du; Xiangdong Li; Baoting Fang; Fang Wei; Ge Yan (Journal of Photochemistry and Photobiology B: Biology, 2024)

A γ-Fe2O3/thiophene-sulfur-doped graphene nanozymes-based colorimetric sensor for visual and quantitative determination of chlorpyrifos - Yuting Yan; Yuhang Ge; Hanping Mao; Qirui Wang; Qinglin Li; Henan Li (Journal of Environmental Chemical Engineering, 2024)

Dietary supplementation with quercetin alleviates fescue toxisis-induced cardiovascular toxicity by modulating detoxification enzymes through the AHR/NRF2/ABCC1 signaling pathways - Jing Ge; Sarah Layne Shelby; Yongjie Wang; Palika Dias Morse; Ken Coffey; J. Lannett Edwards; Tuoyu Geng; Jinlong Li; Yan Huang (Food Bioscience, 2024)

Value-added resource recovery through forward osmosis promoted by pH-responsive biscarboxyimidazolium materials - Xiangfang Liu; Fengrong Qiu; Yan Yu; Yongqian Shi; Zhihong Zheng; Jingyun Zhang; Qingchun Ge (Desalination, 2024)

Injectable NGF-loaded double crosslinked collagen/hyaluronic acid hydrogels for irregular bone defect repair via neuro-guided osteogenic process - Qingsong Jiang; Liaomin Zhou; Yi Yang; Hu Long; Liming Ge; Defu Li; Changdao Mu; Wenli Lai; Zhilang Xu; Yan Wang (Chemical Engineering Journal, 2024)

A hollow mesoporous iron oxide nanoparticle to strengthen Fenton reaction and weaken antioxidant defense systems for high efficacy tumor ferroptosis therapy - Jing Yang; Jiaoyang Zhu; Bin Ren; Haobin Cai; Zongheng Li; Qingdeng Fan; Wei Xiong; Jie Feng; Chenggong Yan; Ge Wen; Yan Li; Chaomin Chen; et al. (Chemical Engineering Journal, 2024)

Global risk dynamics of Borrelia miyamotoi in the context of climate change - Tian Tang; Hong‐Han Ge; Tian Ma; Meng‐meng Hao; Shuai Chen; Chen‐Long Lv; Yun‐Bo Qiu; Yan‐He Wang; Yao Tian; Jin‐Jin Chen; Shuai Yuan; Qian Wang; et al. (Environmental Microbiology, 2024)
The impact of Borrelia miyamotoi on human health, facilitated by the expanding geographical distribution and increasing population of Ixodes ticks, remains obscure in the context of global climate change. We employed multiple models to evaluate the effect of global climate change on the risk of B. miyamotoi worldwide across various scenarios. The habitat suitability index of four primary vector tick species for B. miyamotoi , including Ixodes persulcatus , Ixodes ricinus, Ixodes pacificus and Ixodes scapularis , was projected using a boosted regression tree model, considering multiple shared socio‐economic pathway scenarios over various time periods. The modelling analysis reveals that, apart from I. scapularis , future global warming will result in a northward shift in the other three vector tick species and a gradual reduction in suitable habitats. Random forest models indicate consistent changes in B. miyamotoi and its primary tick species, with potential risk areas shrinking and shifting northward, particularly in the eastern USA, northeastern and northern Europe and northeast Asia. These findings highlight the urgent need for enhanced active surveillance of B. miyamotoi infection in primary vector tick species across projected potential risk areas. The effect of climate change on B. miyamotoi distribution might have significant implications for public health decision‐making regarding tick‐borne pathogens.

Genome wide association analysis reveals the genetic sites of heat resistance in largemouth bass (Micropterus salmoides) - Xiang Li; Yan Zhou; Taigang Liu; Shouwen Jiang; Ruoxi Li; Yuteng Ge; Yaohui Wang; Hanqing Tu; Jun Huang; Xinpeng Zhu; Qianghua Xu; Liangbiao Chen (Aquaculture, 2024)

The impact of low-carbon transition of energy sectors on regional water use in China - Feng Wang; Zhenzi Ge; Xu Yan; Wei Zhang; Ke Jiang; Beiming Cai (Sustainable Production and Consumption, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Semi-arid rather than arid regions of China deserve the priority in drought mitigation efforts - Xin Lan; Zhiyong Liu; Yang Ge; Yu Yan; Zhenyan She; Linyin Cheng; Xiaohong Chen (Journal of Hydrology, 2024)

Paospora carinifang n. gen., n. sp. (Microsporidia: Spragueidae), a parasite of the ridgetail white prawn, Palaemon carinicauda - Yuan Wang; Ying Na; Yan-qing Huang; Jun-fang Zhou; Shou-hu Li; Quan-lin Liu; Le-tian Li; Yuan-ge Chen; Wei Tian; Hai Chi; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2024)

Beta-blocker drives the conjugative transfer of multidrug resistance genes in pure and complex biological systems - Qian Wu; Ge-Ge Wu; Kai-Nan Pan; Xue-Ping Wang; Hong-Yan Li; Zhe Tian; Ren-Cun Jin; Nian-Si Fan (Journal of Hazardous Materials, 2024)

The novel hydrolase IpcH initiates the degradation of isoprocarb in a newly isolated strain Rhodococcus sp. D-6 - Qian Zhu; Hongfei Liu; Kaihua Pan; Wanhe Zhu; Yihui Qiao; Qian Li; Junqiang Hu; Mingliang Zhang; Jiguo Qiu; Xin Yan; Jing Ge; Qing Hong (Journal of Hazardous Materials, 2024)

In situ U–Pb dating of garnet, vesuvianite, and scheelite from the Nanyangtian tungsten deposit reveals an Early Cretaceous W mineralization event in Southeast Yunnan, China - Xiao-Yu Zhao; Ming-Guo Deng; Wen-Chang Li; Yan-Wen Tang; Ding-Cai Zhang; Sheng-Kang Han; Wen-Bo Song; Qing-Ge Zhang; Jing-Wei Xu (Gondwana Research, 2024)

Systemic oxidative stress levels during the course of pregnancy: Associations with exposure to air pollutants - Xiangtian Wang; Yan Lin; Yihui Ge; Emily Craig; Xiaodong Liu; Richard K. Miller; Sally W. Thurston; Jessica Brunner; Emily S. Barrett; Thomas G. O'Connor; David Q. Rich; Junfeng (Jim) Zhang (Environmental Pollution, 2024)

“Fireworks” ignition and combustion of metal nanoparticles: Based on the rapid conversion and transmission of microwave energy by energetic ionic liquids - Jian Cheng; Yan Ge; Jianbing Xu; Yinghua Ye; Ruiqi Shen (Chemical Engineering Journal, 2024)

Optimization of ethylene thiourea, cyanide, and heavy metals removal and gas production enhancement in organosulfur pesticide wastewater using ferromagnetic biochar in anaerobic membrane bioreactor - Yifan Wang; Zhaobo Chen; Dongxue Hu; Liwen Jiang; Shiming Cui; Shuya Zhuang; Jitao Yan; Jian Dong; Fei Han; Bei Jiang; Hui Ge; Zhibo Liang (Chemical Engineering Journal, 2024)

MiR-483-3p promotes dental pulp stem cells osteogenic differentiation via the MAPK signaling pathway by targeting ARRB2 - Xin Yu; Juan Ge; Huimin Xie; Jialu Qian; Wenqian Xia; Qinghua Wang; Xiaorong Zhou; Yan Zhou (In Vitro Cellular & Developmental Biology - Animal, 2024)

Dynamic Response of Roadbed Soil Under Various Dynamic Load Waveforms - Xin-Sheng Zhang; Yan-Ge Chen; Chang-Biao He; Zhen Li; Lei Liao; Yun Cheng; Yin-Lei Sun (Geotechnical and Geological Engineering, 2024)

Deciphering morphology patterns of environmental microfibers: Insights into source apportionment - Ruoqun Yan; Jiangpeng Li; Jiawei Li; Yang Liu; Zhe Xu; Xinyu Ge; Xiao Lu; Krishna Kumar Yadav; Ahmad J. Obaidullah; Yuanyuan Tang (Water Research, 2024)

Spatio-temporal pattern analysis of coastal zone in Nansha based on remote sensing technology - Jun Huang; Xiaojuan Liu; Yan Lin; Lipeng Ge (Remote Sensing Applications: Society and Environment, 2024)

Geochronology and Sr-Nd-Pb-Hf-O isotopes of Neoproterozoic orthogneisses in the Jiamusi Block, NE China: Implications for tectonic origin and secular crustal evolution - Xin Ding; Hao Yang; Zheng Ji; Yan-Long Zhang; Hao-Ran Wu; Yu Dong; Guan-Ying Yu; Wen-Chun Ge (Precambrian Research, 2024)

Time-dependent non-uniform corrosion of concrete structures under marine environments considering the vertical variation of exposure conditions - Qifang Liu; Yiquan Chen; Yan Ge; Qingrong Xiong; Jinliang Ma; Yukang Wang; Fengling Zhang (Ocean Engineering, 2024)

Complete genome sequence of a novel Pseudomonas sp. IT1137 isolated from Antarctic intertidal sediment showing potential for alkane degradation at low temperatures - Hui-Yan Ge; Yi-He Zhang; Yong-Qiang Hu; Wei Han; Yu Du; Ting Hu; Yin-Xin Zeng (Marine Genomics, 2024)

The chitinase genes TuCht4 and TuCht10 are indispensable for molting and survival of Tetranychus urticae - Ming Liu; Rongchumu Ge; Lihong Song; Yan Chen; Shuo Yan; Chunya Bu (Insect Biochemistry and Molecular Biology, 2024)

Flow patterns and heat transfer of an idealized square city in non-uniform heat flux and different background wind conditions - Xiaoliang Teng; Yan Zhang; Yifan Fan; Jian Ge (Building and Environment, 2024)

Mass cytometry revealed the circulating immune cell landscape across different Suzuki stages of Moyamoya disease - Chenglong Liu; Peicong Ge; Bojian Zhang; Liujia Chan; Yuheng Pang; Chuming Tao; Junsheng Li; Qiheng He; Wei Liu; Siqi Mou; Zhiyao Zheng; Zhikang Zhao; et al. (Immunologic Research, 2024)
Moyamoya disease (MMD) is a cerebrovascular disorder marked by progressive arterial narrowing, categorized into six stages known as Suzuki stages based on angiographic features. Growing evidence indicates a pivotal role of systemic immune and inflammatory responses in the initiation and advancement of MMD. This study employs high-dimensional mass cytometry to reveal the immunophenotypic characteristics of peripheral blood immune cells (PBMCs) at various Suzuki stages, offering insights into the progression of MMD. PBMC samples from eight patients with early-stage MMD (Suzuki stages II and III) and eight patients with later-stage MMD (Suzuki stages IV, V, and VI) were analyzed using high-dimensional mass cytometry to evaluate the frequency and phenotype of immune cell subtypes. We identified 15 cell clusters and found that the immunological features of early-stage MMD and later-stage MMD are composed of cluster variations. In this study, we confirmed that, compared to later-stage MMD, the early-stage MMD group exhibits an increase in non-classical monocytes. As the Suzuki stage level increases, the proportions of plasmacytoid DCs and monocyte-derived DCs decrease. Furthermore, T cells, monocytes, DCs, and PMN-MDSCs in the early-stage MMD group show activation of the canonical NF-κB signaling pathway. We summarized and compared the similarities and differences between early-stage MMD patients and later-stage MMD patients. There is a potential role of circulating immune dysfunction and inflammatory responses in the onset and development of MMD.

Correction to: The connection between six common air pollution particles and adult brain tumors: a meta-analysis of 26,217,930 individuals - Lu-Ting Shen; Meng-Wei Ge; Fei-Hong Hu; Yi-Jie Jia; Wen Tang; Wan-Qing Zhang; Dan-Yan Zhao; Wang-Qin Shen; Hong-Lin Chen (Environmental Science and Pollution Research, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Phthalic acid esters: Are they a big concern for rivers flowing into reservoir with ecological facilities? - Huan-yu Tao; Jianghong Shi; Jiawei Zhang; Hui Ge; Xiaowei Liu; Xiao-yan Li (Water Research, 2024)

Colorimetric aptasensor utilizing MOF-235 with exceptional peroxidase-like activity for the detection of oxytetracycline residues in raw milk - Long Wang; Xia Lu; Yan Zhang; Yuxin Wang; Yi Ding; Mengjia Liu; Shangchen Fu; Wupeng Ge (Food Chemistry, 2024)

Membraneless organelles assembled by AuNPs-enzyme integration in non-photosynthetic bacteria: Achieving high specificity and selectivity for solar hydrogen production - Hui Li; Xiaoxuan Yu; Yaqi Wu; Cong Li; Zhengwei Xu; Wang Liu; Shuheng Chen; Hongcheng Sun; Yan Ge; Zhenhui Qi; Junqiu Liu (Chemical Engineering Journal, 2024)

Developmental toxicity and mechanism of dibutyl phthalate and alternative diisobutyl phthalate in the early life stages of zebrafish (Danio rerio) - Huan-Yu Tao; Jianghong Shi; Jiawei Zhang; Hui Ge; Mengtao Zhang; Xiao-Yan Li (Aquatic Toxicology, 2024)

Ablated Sonic Hedgehog Signaling in the Dentate Gyrus of the Dorsal and Ventral Hippocampus Impairs Hippocampal-Dependent Memory Tasks and Emotion in a Rat Model of Depression - Yan Luo; Yan Wang; Feng Qiu; Guanghan Hou; Jian Liu; Hui Yang; Mei Wu; Xuanqi Dong; Dongwei Guo; Ziyan Zhong; Xi Zhang; Jinwen Ge; et al. (Molecular Neurobiology, 2024)

Adaptation of a prey population to increasing predation risks - Ling Pan; Han Zhu; Yan Wang; Bao-Chun Shi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen; Yi-Long Xi (Hydrobiologia, 2024)

Seismic effectiveness evaluation and optimized design of tie up method for securing museum collections - Meng Wang; Yi Yan; Weiguo Yang; Pei Liu; Jiaqi Ge; Botao Ma (Earthquake Engineering and Engineering Vibration, 2024)

Revealing the heterogeneity of periodic visiting patterns across different ages and spaces using a flexible detection method: A case study of Beijing - Zidong Fang; Tao Pei; Ci Song; Xiaorui Yan; Le Liu; Sihui Guo; Yaxi Liu; Yong Peng; Dasheng Ge; Jie Chen (Applied Geography, 2024)

Water addition but not reduction alters plant biomass–diversity relationship - Yan Yu; Josep Peñuelas; Jordi Sardans; Jiu‐ying Pei; Ge Li; Guo‐lin Liu; Jian‐Sheng Ye (Global Change Biology, 2024)
The relationship between plant aboveground biomass and diversity typically follows a unimodal pattern, showing a positive correlation in resource‐poor habitats and a negative correlation in resource‐rich environments. Precipitation is a crucial resource for both plant biomass and diversity in terrestrial ecosystems. However, the impact of precipitation changes on the relationship between plant biomass and diversity remains unclear. We conduct a water addition field experiment in a semiarid grassland and identify a unimodal relationship between plant biomass and species richness under ambient conditions. Water addition delays the declining phase of this unimodal curve and shift it upward compared to ambient conditions. Our meta‐analysis of water addition experiments conducted across major biomes worldwide (grassland, shrubland, desert, and forest) supports this finding, while water reduction does not alter the biomass–diversity relationship. Water addition increases biomass in all climate but only increases species richness in arid and semiarid climate. Similarly, water reduction decreases biomass in all climate but only reduces species richness in arid and semiarid climate. Species richness in dry subhumid and humid climate does not change significantly. Furthermore, our field experiment shows that water addition increases plant diversity while decreasing soil inorganic nitrogen levels. The increase in one resource, such as water, leads to the scarcity of another, such as nutrient, thus postponing the declining phase of the plant biomass–diversity relationship typically observed in resource‐rich habitats. Our research contributes to predicting the plant biomass–diversity relationship under changing precipitation conditions and highlights the complex interplay between water availability, nutrient level, and plant diversity.

Performance of a novel up-flow electrocatalytic hydrolysis acidification reactor (UEHAR) coupled with anoxic/oxic system for treating coking wastewater - Jian Dong; Zhaobo Chen; Fei Han; Dongxue Hu; Hui Ge; Bei Jiang; Jitao Yan; Shuya Zhuang; Yifan Wang; Shiming Cui; Zhibo Liang (Water Research, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Carbohydrate and fatty acid metabolisms are involved in delaying senescence of ‘Zaosu’ pear fruit following caffeic acid treatment - Canying Li; Yan Guo; Hengping Xu; Miao Wang; Yonghong Ge (Postharvest Biology and Technology, 2024)

Review of chemical looping technology for energy conservation and utilization: CO2 capture and energy cascade utilization - Jinbiao Yan; Sha Wang; Bin Hu; Huarong Zhang; Lipei Qiu; Weijun Liu; Yun Guo; Jun Shen; Bin Chen; Xiang Ge; Cong Shi (Journal of Environmental Chemical Engineering, 2024)

Impact of manufacturing processes on glycerolipid and polar lipid composition and ultrastructure in infant formula - Qian Liu; Yan Liu; Junying Zhao; Weicang Qiao; Juncai Hou; Yaling Wang; Minghui Zhang; Ge Jia; Yan Liu; Xiaofei Fan; Ziqi Li; Haidong Jia; et al. (Food Chemistry, 2024)

Integrating untargeted and pseudotargeted metabolomics and network analysis reveals the interventional effects of red yeast rice on rat serum metabolites - Ge Xun; Yingxuan Li; Yifan Zhang; Song Li; Yanhua Gao; Yujuan Chen; Ding Zhang; Hongyang Ni; Fangfang Liu; Yan Fu; Xu Wang; Qiao Wang (Food Bioscience, 2024)

Regulation of myogenic differentiation of myoblasts by groove structure for the design of cell culture meat scaffolds - Yawen Chen; Wenjing Dai; Wanli Xiong; Yi Zhou; Ziying Chen; Chengxin Ge; Yan Zhou (Food Bioscience, 2024)

Highly efficient non-doped organic light emitting diodes based on phenanthreneimidazole derivatives with hot exciton mechanism - Shuyuan Ge; Chunya Du; Zhuang Cheng; Yaxue Wang; Zijun Feng; Zhenyu Yan; Yin Hu; Ping Lu (Chemical Engineering Journal, 2024)

The novel probiotic preparation based on Lactobacillus spp. mixture on the intestinal bacterial community structure of Cherry Valley duck - Shuiqin Shi; Mengrui Ge; Yan Xiong; Yixun Zhang; Wenhui Li; Zhimuzi Liu; Jianfen Wang; Enhui He; Liming Wang; Duoqi Zhou (World Journal of Microbiology and Biotechnology, 2024)

Glutamic Acid-Enhanced Phosphate Fertilizer Increases Phosphorus Availability in Fluvo-Aquic Soil via Phosphamide (O = P-N) Formation, Decreasing Phosphate Fixation and Increasing Soil Microbial Diversity - Yingqiang Zhang; Shuiqin Zhang; Bingqiang Zhao; Yanting Li; Meng Xu; Yan’ge Yan; Jianyuan Jing; Liang Yuan (Journal of Soil Science and Plant Nutrition, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

Genetic differences among populations of Gynura procumbens (Lour.) Merr - Jiangfan Yu; Xinjian Tan; Dunyuan Huang; Qiuping Zhong; Ping Gu; Youcheng Zhou; Linqing Cao; Liyun Wang; Xirui Wan; Chuansong Chen; Yaqi Yuan; Hongyan Guo; et al. (Genetic Resources and Crop Evolution, 2024)

Efficient analysis of metabolites of industrial additives in cerebrospinal fluids - Ruihe Jin; Jun Shi; Jing Yang; Ge Yin; Chunjie Xia; Xiongwei Wang; Min Liu; Yan Wu (Environmental Chemistry Letters, 2024)

Draconibacterium aestuarii sp.nov., a Glycolipid-Producing Bacterium Isolated from Tidal Flat Sediment and Emended Description of the Genus Draconibacterium - Jia-Yan Wang; Sha-Sha Qiu; Yue Su; Wei-Yu Pan; Tao Wang; Wen-Wu Zhang; Ge-Yi Fu; Min Wu (Current Microbiology, 2024)

The First Genome-Wide Survey of Shortbelly Eel (Dysomma anguillare Barnard, 1923) to Provide Genomic Characteristics, Microsatellite Markers and Complete Mitogenome Information - Tian-yan Yang; Zi-yan Zhu; Yu-ping Liu; Si-ge Wang (Biochemical Genetics, 2024)

Environmental adaptation, growth performance and nutrient content of the clam Cyclina sinensis from different geographic locations - Shiyu Yan; Qing Xia; Zhenquan Cui; Guoliang Ren; Xiaoying Li; Hongxing Ge; Meimei Liu; Zhiguo Dong (Frontiers in Marine Science, 2024)
The clam Cyclina sinensis is an economically important marine species in China. However, overfishing, habitat destruction, and inbreeding have led to the destruction of genetic resources. In this study, five natural populations [Dandong (DD), Dongying (DY), Tianjin (TJ), Wenzhou (WZ), and Yancheng (YC)] from different geographical locations were relocated and cultured homogeneously to study their potential for translocation and environmental adaptation by observing growth performance and nutrient content. There were significant differences in the growth rates of shell length (SL), shell height (SH), and shell width (SW) among the five populations ( P<0.05 ). The DD, TJ, and YC populations exhibited the highest SL and SH growth rates, whereas these were lowest in the WZ population. The survival rate was highest in the YC population and lowest in the WZ population, which was significantly lower than the other four populations ( P<0.05 ). The DD population exhibited superior plumpness and glycogen content, and the overall glycogen content in male C. sinensis was higher compared with that in females ( P<0.05 ). All populations displayed a high total amino acid content and the essential amino acid/Total Amino Acid (EAA/TAA) and Non-essential amino acid/Total Amino Acid (NEAA/TAA) ratios in the soft tissue of all five populations aligned with the FAO/WHO ideal protein evaluation standards. Despite the same aquaculture environment, however, the nutrient composition of C. sinensis sampled from different populations varied significantly ( P<0.05 ).Therefore, ex situ conservation did not eliminate nutritional differences between the different populations of C. sinensis. These findings highlight the importance of considering environmental and ecological factors in the nutritional assessment and cultivation of shellfish. In addition, C. sinensis from sampling sites closer to the transplantation sites had higher survival rates and growth rates, and the gonadal development of all populations showed adaption to the local environment, resulting in synchronization of the reproductive period.

The effect of artificial light at night (ALAN) on the characteristics of diapause of Aedes albopictus - Qing Liu; Heng-Duan Zhang; Dan Xing; Jing-Wen Xie; Yu-Tong Du; Ming Wang; Zi-Ge Yin; Nan Jia; Chun-Xiao Li; Teng Zhao; Yu-Ting Jiang; Yan-De Dong; et al. (Science of The Total Environment, 2024)

The effects of microgravity on stem cells and the new insights it brings to tissue engineering and regenerative medicine - Hong-Yun Nie; Jun Ge; Kai-Ge Liu; Yuan Yue; Hao Li; Hai-Guan Lin; Hong-Feng Yan; Tao Zhang; Hong-Wei Sun; Jian-Wu Yang; Jin-Lian Zhou; Yan Cui (Life Sciences in Space Research, 2024)

Exploring the aqueous photodegradation of three ionisable macrolide antibiotics: Kinetics, intermediates and photoinduced toxicity - Linke Ge; Nannan Cui; Crispin Halsall; Yan Yang; Shengkai Cao; Peng Zhang (Journal of Water Process Engineering, 2024)

Study on spray characteristics of micro-nano bubble premixed fuel - Rong Xuan; Liang Guo; Ningning Cai; Wanchen Sun; Yuying Yan; Hao Zhang; Yanling Chen; Han Wang; Junfeng Zhang; Youxin Ge (Fuel, 2024)

Fhb7-GST catalyzed glutathionylation effectively detoxifies the trichothecene family - Bingqian Hou; Dawei Wang; Fangfang Yan; Xinxin Cheng; Yongchang Xu; Xuepeng Xi; Wenyang Ge; Silong Sun; Peisen Su; Lanfei Zhao; Zhongfan Lyu; Yongchao Hao; et al. (Food Chemistry, 2024)

Enzymatic synthesis of Vaccinium blue using vaccinoside as a bifunctional precursor - Jianqin Zhou; Ziyan Qi; Ling Yi; Yang Zhang; Zhaowei Yan; Jian Zhang; Fei Ge; Yali Li; Jiangyun Liu (Food Chemistry, 2024)

Upcycling crab shell waste into biochar for treatment of palm oil mill effluent via microwave pyrolysis and activation - Yan Yang; Shin Ying Foong; Yifeng He; Rock Keey Liew; Nyuk Ling Ma; Peter Nai Yuh Yek; Shengbo Ge; Mu. Naushad; Su Shiung Lam (Environmental Research, 2024)

Acute exposure to seasonal PM2.5 induces toxicological responses in A549 cells cultured at the air-liquid interface mediated by oxidative stress and endoplasmic reticulum stress - Wankang Chen; Pengxiang Ge; Zhenyu Lu; Xiaoming Liu; Maoyu Cao; Zhansheng Yan; Mindong Chen (Environmental Research, 2024)

Self-powered three-dimensional one-piece flexible pressure sensing system for human motion information aquisition - Lu Chen; Bao Shi; Wei Zhang; XinYing Liu; Ge Fang; LiXia Jia; RuoSi Yan (Chemical Engineering Journal, 2024)

Resveratrol-loaded sulfated Hericium erinaceus β-glucan-chitosan nanoparticles: Preparation, characterization and synergistic anti-inflammatory effects - Zhong Zhang; Meili Ge; Di Wu; Wen Li; Wanchao Chen; Peng Liu; Haiyun Zhang; Yan Yang (Carbohydrate Polymers, 2024)

A hybrid approach of anaerobic digestion model no. 1 and machine learning to model and optimize continuous anaerobic digestion processes - Yadong Ge; Junyu Tao; Zhi Wang; Lan Mu; Wei Guo; Zhanjun Cheng; Beibei Yan; Yan Shi; Hong Su; Guanyi Chen (Biomass and Bioenergy, 2024)

Assessing the Gumbel-Logistic Model’s performance in modeling long-term rainfall series in a high-latitude plain region - Yu-Ge Wang; Jian Kong; Ling Lan; Ling Zhong; Xie-Kang Wang; Xu-Feng Yan (Theoretical and Applied Climatology, 2024)

Anti-epileptic and Neuroprotective Effects of Ultra-low Dose NADPH Oxidase Inhibitor Dextromethorphan on Kainic Acid-induced Chronic Temporal Lobe Epilepsy in Rats - Jing-Jing Yang; Ying-Xin Liu; Yan-Fang Wang; Bi-Ying Ge; Ying Wang; Qing-Shan Wang; Sheng Li; Jian-Jie Zhang; Ling-Ling Jin; Jau-Shyong Hong; Sheng-Ming Yin; Jie Zhao (Neuroscience Bulletin, 2024)

Exploring the release mechanism of micro/nanoplastics from different layers of masks in water: towards reduction of plastic contamination in masks - Wei Ge; Hao Liang; Ping Gao; Yan Li; Ningning Song; Juan Wu; Chao Chai (Environmental Science and Pollution Research, 2024)

Measuring canopy morphology of saltmarsh plant patches using UAV-based LiDAR data - Qiuxin Hong; Zhenpeng Ge; Xinkai Wang; Yan Li; Xiaoming Xia; Yining Chen (Frontiers in Marine Science, 2024)
Plant patches play a crucial role in understanding the biogeomorphology of saltmarshes. Although two-dimensional optical remote sensing has long been applied to the study of saltmarsh plant patches, studies focusing on the canopy features at a patch-scale remain limited. Therefore, a simple and efficient method is needed to capture three-dimensional patch features and their relationship to habitat. This study utilized UAV-based LiDAR to obtain three-dimensional patch features of the native species S. mariqueter and the invasive species S. alterniflora in Andong Shoal, Hangzhou Bay, and examine the relationship between patch distribution and geomorphological characteristics. A workflow was established to overcome the inability of low-cost LiDAR sensor to penetrate dense vegetation, resulting in no ground return. Results showed that S. alterniflora patches were smaller in size but taller in canopy height than S. mariqueter patches. Regarding morphological patterns of patch canopy, S. alterniflora exhibited single-arch patterns (29%) and double-arch patterns (16%), whereas S. mariqueter exhibited only single-arch patterns (83%). The presence of double-arch patches suggested the development of fairy circles, indicating that the invasive S. alterniflora exhibits greater ecological resilience compared to the native S. mariqueter. Furthermore, this study explored the ecological niches of the two species in the pioneer zone of Andong Shoal. The ecological niches for S. alterniflora were 2.00-2.25 m, whereas that for S. mariqueter were 1.85-2.00 m and 2.25-2.40 m. Distance from the tidal creeks significantly moderated the number and area of patches for both species. This study demonstrated that UAV-based LiDAR technology can provide high-quality three-dimensional information about the pioneer zone of saltmarsh, thus helping to understand biogeomorphological processes in this region.

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

Activation of the calcium signaling, mitogen-activated protein kinase cascade and phenylpropane metabolism contributes to the induction of disease resistance in pear fruit upon phenylalanine treatment - Canying Li; Miao Wang; Yan Guo; Shuran Zhang; Hengping Xu; Yonghong Ge (Postharvest Biology and Technology, 2024)

Enhancement of disease resistance against Alternaria alternata in winter jujube fruit by phenyllactic acid through regulating Ca2+ signaling transduction and mitogen-activated protein kinase cascades - Hengping Xu; Canying Li; Miao Wang; Yan Guo; Shuran Zhang; Yonghong Ge (Postharvest Biology and Technology, 2024)

Synthesis and antifungal activity of 2,4-diacetylphloroglucinol analogues - Xi-Long Guo; Chun-Yan Zhao; Cui-Ping Zhang; Yi Zhu; Qing-Rong Wu; Yuan-Qing Zhou; Ya-Hong Fei; Fang Ge; Wei Shi (Phytochemistry Letters, 2024)

Corrigendum to “Cross-species analysis of transcriptome emphasizes a critical role of TNF-α in mediating MAP2K7/AKT2 signaling in zearalenone-induced apoptosis” [J Hazard Mater 459 (2023) 132226] - Fa-Li Zhang; Ke-Xin Zhu; Jing-Ya Wang; Min Zhang; Jia-Mao Yan; Qing-Chun Liu; Xiao-Yuan Zhang; Jia-Chen Guo; Xuan Liu; Qi-cheng Sun; Wei Ge; Lan Li; et al. (Journal of Hazardous Materials, 2024)

Characterization and prediction modeling of membrane distillation enhanced disc solar still - Lu Zuo; Chenkai Xiao; Ziyang Yan; Long Huang; Zinan Guo; Yunting Ge (Journal of Cleaner Production, 2024)

The dynamic carbon footprint modeling for laser direct metal deposition based on processing states - Haiying Wei; Ge Yan; Wen Liu; Yingying Zhang (Journal of Cleaner Production, 2024)

Advanced multifunctional Co/N co-doped carbon foam-based phase change materials for wearable thermal management - Yang Li; Xuemei Diao; Peicheng Li; Panpan Liu; Yan Gao; Zhiyong Zhao; Xiao Chen; Ge Wang (Chemical Engineering Journal, 2024)

Heterologous expression of taxane genes confers resistance to fall armyworm in Nicotiana benthamiana - Zhenlu Xu; Yaohua Zhai; Huimin Chang; Da Yan; Pengliang Ge; Guangming Ren; Lijun Zhang; Ye Yuan; Ruoyan Wang; Wentao Li; Fuguang Li; Maozhi Ren; et al. (Plant Cell Reports, 2024)

STAT4-Mediated Klotho Up-Regulation Contributes to the Brain Ischemic Tolerance by Cerebral Ischemic Preconditioning via Inhibiting Neuronal Pyroptosis - Xi-Yun Liu; Ling-Yan Zhang; Xiao-Yu Wang; Shi-chao Li; Yu-Yan Hu; Jing-Ge Zhang; Xiao-Hui Xian; Wen-Bin Li; Min Zhang (Molecular Neurobiology, 2024)

The Role of Astrocytic Mitochondria in the Pathogenesis of Brain Ischemia - Ling-Yan Zhang; Yu-Yan Hu; Xi-Yun Liu; Xiao-Yu Wang; Shi-Chao Li; Jing-Ge Zhang; Xiao-Hui Xian; Wen-Bin Li; Min Zhang (Molecular Neurobiology, 2024)

Toxicological responses of A549 and HCE-T cells exposed to fine particulate matter at the air–liquid interface - Wankang Chen; Pengxiang Ge; Minjun Deng; Xiaoming Liu; Zhenyu Lu; Zhansheng Yan; Mindong Chen; Junfeng Wang (Environmental Science and Pollution Research, 2024)
Fine particulate matter (PM 2.5 ) can enter the human body in various ways and have adverse effects on human health. Human lungs and eyes are exposed to the air for a long time and are the first to be exposed to PM 2.5 . The “liquid immersion exposure method” has some limitations that prevent it from fully reflecting the toxic effects of particulate matter on the human body. In this study, the collected PM 2.5 samples were chemically analyzed. An air–liquid interface (ALI) model with a high correlation to the in vivo environment was established based on human lung epithelial cells (A549) and immortalized human corneal epithelial cells (HCE-T). The VITROCELL Cloud 12 system was used to distribute PM 2.5 on the cells evenly. After exposure for 6 h and 24 h, cell viability, apoptosis rate, reactive oxygen species (ROS) level, expression of inflammatory factors, and deoxyribonucleic acid (DNA) damage were measured. The results demonstrated significant dose- and time-dependent effects of PM 2.5 on cell viability, cell apoptosis, ROS generation, and DNA damage at the ALI, while the inflammatory factors showed dose-dependent effects only. It should be noted that even short exposure to low doses of PM 2.5 can cause cell DNA double-strand breaks and increased expression of γ-H2AX, indicating significant genotoxicity of PM 2.5 . Increased abundance of ROS in cells plays a crucial role in the cytotoxicity induced by PM 2.5 exposure These findings emphasize the significant cellular damage and genotoxicity that may result from short-term exposure to low levels of PM 2.5 .

Iron-modified biochar inhibiting Cd uptake in rice by Cd co-deposition with Fe oxides in the rice rhizosphere - Fengfeng Sui; Zhongjun Xue; Kangle Shao; Zikang Hao; Haochuan Ge; Liqiang Cui; Guixiang Quan; Jinlong Yan (Environmental Science and Pollution Research, 2024)

Ecological performance of an integrated ex-situ rice-fish co-culture system - Qiao Liu; Leji Zhang; Yi Yang; Jiacen Zou; Yipeng Yang; Jiayu Ge; Haoxiao Yan; Kuo He; Changjun Yang; Rabia Tahir; Liulan Zhao; Song Yang (Aquaculture, 2024)

Heterogeneous reactions significantly contribute to the atmospheric formation of nitrated aromatic compounds during the haze episode in urban Beijing - Zhen Cheng; Xinghua Qiu; Ailin Li; Qianqian Chai; Xiaodi Shi; Yanli Ge; Theodore K. Koenig; Yan Zheng; Shiyi Chen; Min Hu; Chunxiang Ye; Rico K.Y. Cheung; et al. (Science of The Total Environment, 2024)

Investigation on the budget of peroxyacetyl nitrate (PAN) in the Yangtze River Delta: Unravelling local photochemistry and regional impact - Tao Xu; Wei Nie; Zheng Xu; Chao Yan; Yuliang Liu; Qiaozhi Zha; Ruoxian Wang; Yuanyuan Li; Lei Wang; Dafeng Ge; Liangduo Chen; Ximeng Qi; et al. (Science of The Total Environment, 2024)

Review of waste plastics treatment and utilization: Efficient conversion and high value utilization - Bin Hu; Sha Wang; Jinbiao Yan; Huarong Zhang; Lipei Qiu; Weijun Liu; Yun Guo; Jun Shen; Bin Chen; Cong Shi; Xiang Ge (Process Safety and Environmental Protection, 2024)

Postharvest caffeic acid dipping enhances disease resistance and storage capacity of ‘Zaosu’ pear fruit via regulating phenylpropane metabolism - Yan Guo; Canying Li; Miao Wang; Hengping Xu; Shuran Zhang; Jiaqi Liu; Yueruxin Jin; Yonghong Ge (Postharvest Biology and Technology, 2024)

The promoting effect of electron beam irradiation on enzymatic saccharification and alcohol fermentation of sorghum meal: Related mechanisms - Mengting Yan; Chenyang Sun; Jiangtao Yu; Junqing Bai; Huishan Shen; Xiuyun Zhang; Yifan Lu; Zhuangzhuang Sun; Xiangzhen Ge; Wei Liang; Jie Zeng; Haiyan Gao; et al. (Journal of Cereal Science, 2024)

Tumoral/exosomal PD-L1 silencing reinforces mild photothermal therapy by relieving systemic and local immunosuppression - Huan Ye; Jing Yan; Chenglong Ge; Fan Wu; Junliang Zhu; Mengyuan Yin; Lucheng Xie; Zhuchao Zhou; Lichen Yin (Chemical Engineering Journal, 2024)

Modeling computer sight based on DEM data to detect terrain breaks caused by gully erosion on the loess Plateau - Ge Yan; Guoan Tang; Jun Chen; Fayuan Li; Xin Yang; Liyang Xiong; Dingyang Lu (CATENA, 2024)

Simulation and optimization of co-pyrolysis biochar using data enhanced interpretable machine learning and particle swarm algorithm - Chao Chen; Rui Liang; Junxia Wang; Yadong Ge; Junyu Tao; Beibei Yan; Guanyi Chen (Biomass and Bioenergy, 2024)

Link between the atmospheric thermal condition over the Tibetan–Iranian Plateaus and Eurasian–African climate through the Asian westerly jet stream - Sulan Nan; Ge Liu; Yan Bao; Dan Chen (Theoretical and Applied Climatology, 2024)

OsGEX3 affects anther development and improves osmotic stress tolerance in rice - Han Bao; Yuchao Cui; Li Ge; Yan Li; Xiaorong Xu; Ming Tang; Yin Yi; Liang Chen (Planta, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

How low-velocity non-Darcian flow in low-permeability media controls the leakage characteristics of a leaky aquifer system - Xianmeng Meng; Ge Yan; Lintao Shen; Maosheng Yin; Dengfeng Liu (Hydrogeology Journal, 2024)

Characterization of CM-Dil-labeled Muse cells in culture and in skin wounds in rats - Yan-yun Cao; Jing Ning; Ru-zhi Zhang; Kang Ge; Ting-ting Huang (Cell and Tissue Banking, 2024)

Improvement of non-specific immunity, intestinal health and microbiota of crucian carp (Carassius auratus) juvenile with dietary supplementation of Bacillus coagulans BC1 - Ren-Ge Hu; Bin-Tong Yang; Zi-Yan Zheng; Zhen-Lin Liang; Yuan-Huan Kang; Wei Cong (Aquaculture, 2024)

Soil nutrient conditions alter viral lifestyle strategy and potential function in phosphorous and nitrogen metabolisms - Xing Huang; Zhichao Zhou; Haiyang Liu; Yiqun Li; Tida Ge; Xianjin Tang; Yan He; Bin Ma; Jianming Xu; Karthik Anantharaman; Yong Li (Soil Biology and Biochemistry, 2024)

Long-term MNNG exposure promotes gastric carcinogenesis by activating METTL3/m6A/miR1184 axis-mediated epithelial-mesenchymal transition - Tong Liu; Yan-lu Feng; Rui-ying Wang; Sheng Yang; Yi-ling Ge; Tian-yi Zhang; Jie Li; Cheng-yun Li; Ye Ruan; Bin Luo; Ge-yu Liang (Science of The Total Environment, 2024)

Measurement of perfluoroalkyl substances in drinking water sources by DGT sampler with a novel fluorinated graphite binding gel - Fan Dong; Fan Ge; Xinting Zhao; Daming Sun; Suyu Ren; Yan Wang; Feng Tan (Science of The Total Environment, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Stress distribution and roof subsidence of surrounding strata considering in situ coal conversion and CO2 mineralization backfilling: Photoelastic experiments using 3D-printed models of mining faces and goafs - Yang Ju; Xiaodong Nie; Yan Zhu; Kai Wang; Hongwei Zhou; Shirong Ge (Science of The Total Environment, 2024)

Application of carboxymethyl cellulose sodium (CMCNa) in maize–wheat cropping system (MWCS) in coastal saline-alkali soil - Ge Li; Yuyang Shan; Weibo Nie; Yan Sun; Lijun Su; Weiyi Mu; Zhi Qu; Ting Yang; Quanjiu Wang (Science of The Total Environment, 2024)

Nonlinear effect of NOx concentration decrease on secondary aerosol formation in the Beijing-Tianjin-Hebei region: Evidence from smog chamber experiments and field observations - Junling Li; Tianzeng Chen; Hao Zhang; Yongcheng Jia; Yangxi Chu; Yongxin Yan; Haijie Zhang; Yanqin Ren; Hong Li; Jingnan Hu; Weigang Wang; Biwu Chu; et al. (Science of The Total Environment, 2024)

Simulated microgravity altered the gene expression profiles and inhibited the proliferation of Kupffer cells in the early phase by downregulating LMO2 and EZH2 - Jun Ge; Yuan Yue; Hong-Yun Nie; Kai-Ge Liu; Hao Li; Hai-Guan Lin; Tao Zhang; Hong-Feng Yan; Hong-Wei Sun; Jian-Wu Yang; Jin-Lian Zhou; Yan Cui (Life Sciences in Space Research, 2024)

Changes in quality characteristics and metabolites composition of wheat under different storage temperatures - Yan Zhao; Ge Han; Yanfei Li; Haoxin Lv (Journal of Stored Products Research, 2024)

Room-temperature photooxidation of low-concentration coalbed methane to methanol over CuO /D-WO3 combined with gas-solid-liquid interface: From pollutant to clean fuel - Juan Yang; Ge Zhang; Jun Dai; Qi Wang; Liqing Rong; Yan Wang (Journal of Cleaner Production, 2024)

Upcycling MSWI fly ash into green binders via flue gas-enhanced wet carbonation - Miao Lu; Weizhe Ge; Yan Xia; Chen Sun; Xiaoqing Lin; Daniel C.W. Tsang; Tung-Chai Ling; Yanjun Hu; Lei Wang; Jianhua Yan (Journal of Cleaner Production, 2024)

Improving on mapping long-term surface water with a novel framework based on the Landsat imagery series - Ling Lan; Yu-Ge Wang; Hao-Shuang Chen; Xu-Rui Gao; Xie-Kang Wang; Xu-Feng Yan (Journal of Environmental Management, 2024)

Optically stimulated luminescence dating of Paleolithic sites reveals population shifts in North China during the last glacial period - Junyi Ge; Xiao Sun; Yan Li; Chunxue Wang; Lishuang Sheng; Ke Hu; Jiequn Hua; Xiaoling Zhang; Faxiang Huan; Shixia Yang; John W. Olsen; Xing Gao; et al. (Global and Planetary Change, 2024)

Unraveling the electrical energy loss in silver nanowire electrodes for flexible and Large-Area organic solar cells - Hao Ren; Wei-Shuo Chen; Jing-De Chen; Jin-Peng Yang; Ye-Fan Zhang; Hong-Yi Hou; Shuo Tian; Heng-Ru Ge; Yan-Qing Li; Jian-Xin Tang (Chemical Engineering Journal, 2024)

Advanced graphitic carbon nitride-based membranes for ionic resource recovery - Mengni Ge; Qin Chen; Yan Zhao; Jianfeng Zhang; Bart Van der Bruggen; Raf Dewil (Chemical Engineering Journal, 2024)

Optimizing slope unit-based landslide susceptibility mapping using the priority-flood flow direction algorithm - Ge Yan; Dingyang Lu; Sijin Li; Shouyun Liang; Liyang Xiong; Guoan Tang (CATENA, 2024)

Stay in touch with the endoplasmic reticulum - Sha Sun; Gan Zhao; Mingkang Jia; Qing Jiang; Shulin Li; Haibin Wang; Wenjing Li; Yunyun Wang; Xin Bian; Yan G. Zhao; Xun Huang; Ge Yang; et al. (Science China Life Sciences, 2024)

Stronger effects of biodiversity loss and compositional change on forest biomass dynamics at larger spatial scales - Jia-Jia Liu; Yi Zheng; Lu Jin; Wan-Hui Ye; Ju-Yu Lian; Kevin S. Burgess; Hai-Fei Yan; Xue-Jun Ge; Jiang-Xiao Qiu (European Journal of Forest Research, 2024)

Morphological and phylogenetic analyses reveal a new species of Anthracophyllum (Omphalotaceae, Agaricales) in Zhejiang Province, China - Wen-Juan Yang; Miao Xu; Jing Zhang; Fan Zhou; Zhi-Fang Le; Wen-Jun Tong; Hai-Yan Song; Zhuo-Han Jin; Qiu-Ge Cheng; Jian-Ping Zhou; Yang Gao; Zhi-Jun Zhai; et al. (Archives of Microbiology, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Insights into the influence and mechanism of biomass substrate and thermal conversion conditions on FeN doped biochar as a persulfate activator for sulfamethoxazole removal - Yining Lin; Qiang Ge; Jinquan Wan; Yan Wang; Congyun Zhu (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Phenyllactic acid maintains the storage quality of ‘Zaosu’ pears by regulating respiration and energy metabolism - Shuran Zhang; Canying Li; Miao Wang; Hengping Xu; Yan Guo; Yonghong Ge (Postharvest Biology and Technology, 2024)

Efficient extraction of platinum(IV) using tertiary-amine groups functionalized thiacalix[4]arene as extractant - Tao Ge; Xiaowei Zhou; Liang Xu; Yan Sun; Cheng Yang; Yongpan Tian; Zhuo Zhao (Minerals Engineering, 2024)

Temporal variations in reactive oxygen species in biofilms of submerged macrophytes: The key role of microbial metabolism mediated by oxygen fluctuations - Zuhan Ge; Zihang Ma; Wenjie Hong; Kexuan Liu; Shuwen Yan; Weihua Song; Jibiao Zhang (Journal of Hazardous Materials, 2024)

Kinetic and mechanism of the reaction between Cl and several mono-methyl branched alkanes - Yan Chen; Weigang Wang; Junling Li; Li Zhou; Bo Shi; Cici Fan; Ke Wang; Hao Zhang; Hong Li; Maofa Ge (Journal of Environmental Sciences, 2024)

Fructooligosaccharides and fructans from Platycodon grandiflorum: Structural characterization, lung-oriented guidance and targetability - Jun Liang; Wen-Fei Wang; Yi Zhang; Yan-Qun Chai; Ya-Ge Li; Si-Liang Jiang; Xin-Hua Zhu; Yu-Li Guo; Zhen Wei; Xi-Zhe Sun; Hai-Xue Kuang; Yong-Gang Xia (Carbohydrate Polymers, 2024)

Hydrometeorological-modeling-based analysis and risk assessment of a torrential rainfall flash flood in a data deficient area in Wenchuan County, Sichuan Province, China - En-Ze Jin; Yu-Ge Wang; Ze-Xing Xu; Xu-Feng Yan; Xie-Kang Wang (Stochastic Environmental Research and Risk Assessment, 2024)

Effects of nutrients and light in aquatic habitat on the growth of Hydrocotyle vulgaris when expanded from terrestrial to aquatic habitat - Zhi-Huan Chen; Rui Zhang; Jun-Cai Xin; Zi-Han Qian; Shu-Jie Wang; Shang-Yan Qiu; Xue-Ge He; Chao Si (Aquatic Botany, 2024)

Griseofulvin enantiomers and bromine-containing griseofulvin derivatives with antifungal activity produced by the mangrove endophytic fungus Nigrospora sp. QQYB1 - Ge Zou; Wencong Yang; Tao Chen; Zhaoming Liu; Yan Chen; Taobo Li; Gulab Said; Bing Sun; Bo Wang; Zhigang She (Marine Life Science & Technology, 2023)

Designing sustainable logistics networks for classified municipal solid wastes collection and transferring with multi-compartment vehicles - Yuxin Hong; Weiyang Yan; Qian Ge (Sustainable Cities and Society, 2023)

Lysosomal dysfunction in carbon black-induced lung disorders - Mingtong Gao; Xiao Ge; Yun Li; Gege Zheng; Jun Cai; Jiani Yao; Tianyi Wang; Yichang Gao; Yuchen Yan; Yinming Chen; Yang Pan; Po Hu (Science of The Total Environment, 2023)

Trade-offs between ligninase and cellulase and their effects on soil organic carbon in abandoned Moso bamboo forests in southeast China - Yaowen Xu; Yan Zhou; Hui Wang; Xiaogai Ge; Ge Gao; Yonghui Cao; Zhengcai Li; Benzhi Zhou (Science of The Total Environment, 2023)

Preclinical evaluation of RQ3013, a broad-spectrum mRNA vaccine against SARS-CoV-2 variants - Shudan Tan; Jinghua Zhao; Xue Hu; Yufeng Li; Zihan Wu; Guoliang Lu; Zhaoli Yu; Binhe Du; Yan Liu; Li Li; Yuchen Chen; Ye Li; et al. (Science Bulletin, 2023)

pH-Responsive graphene oxide/poly (methacrylic acid) hybrid nanofiltration membrane performance for water treatment - Li-yue Sun; De-hao Yu; Zhao-ge Juan; Yao Wang; Yan-xin Wang; Matt J. Kipper; Lin-jun Huang; Jian-guo Tang (Journal of Environmental Chemical Engineering, 2023)

Inducing root redundant development to release oxygen: An efficient natural oxygenation approach for subsurface flow constructed wetland - Jingying Zhang; Qiuhui Yan; Ge Bai; Dun Guo; Yanbin Chi; Bin Li; Lei Yang; Yongxiang Ren (Environmental Research, 2023)

Insights into metal/carbon materials activation of persulfate from a structure–property perspective: Performances, tunable reaction pathways and toxicity - Hao Ge; Min Cheng; DanLian Huang; Ming Yan; Zhen Wei; Gaoxia Zhang; Li Du; Guangfu Wang; Hongda Liu; Shaoheng Liu; Yongxi Chen (Chemical Engineering Journal, 2023)

Chitosan-based molecularly imprinted sponge for selective recognition and recycling of dibenzothiophene from diesel - Yan Huang; Ge Niu; Jie Zhu; Haiyan Ji; Linhua Zhu; Mingqing Hua; Yanhong Chao; Peng Cui; Wenshuai Zhu (Chemical Engineering Journal, 2023)

Analyzing the cellular and molecular atlas of ovarian mesenchymal cells provides a strategy against female reproductive aging - Longzhong Jia; Wenji Wang; Jing Liang; Shudong Niu; Yibo Wang; Jian Yang; Lingyu Li; Ge Wang; Xueqiang Xu; Lu Mu; Kaixin Cheng; Xuebing Yang; et al. (Science China Life Sciences, 2023)

Comparative transcriptome analysis of eyes reveals the adaptive mechanism of mantis shrimp (oratosquilla oratoria) induced by a dark environment - Xiaoli Sun; Ling He; Bujin Ayi; Yuyang Qiu; Jiayue Xu; Wei Yu; Tinghao Yan; Ge Ding; Boping Tang; Gang Wang; Daizhen Zhang (Genetica, 2023)

Determination of niclosamide and its two metabolites in fish by molecularly imprinted microsphere-based pseudo-ELISA - Hao Zhe Hou; Yan Su; Ge Lin Liu; Yao Jia Peng; Jian Ping Wang (Food Additives & Contaminants: Part A, 2023)

Non-invasive prediction of mango quality using near-infrared spectroscopy: Assessment on spectral interferences of different packaging materials - Fangchen Ding; Changzhou Zuo; Juan Francisco García-Martín; Yan Ge; Kang Tu; Jing Peng; Hongmei Xiao; Weijie Lan; Leiqing Pan (Journal of Food Engineering, 2023)

Rapid discrimination of Anji Baicha origin using field-portable spectroradiometer - Ge Jin; Xiang Gui; Yuanyuan Zhu; Delong Zhan; Xinjie Du; Xing Du; Xin Zhang; Yan Zhou; Chuanjian Cui; Chao Zhuo; Xiaochun Wan; Ruyan Hou (Food Control, 2023)

Full-scale experimental study on precast bridge column with grouted sleeve connections and large-diameter reinforcing bars - Penghui Zhang; Zhiqiang Wang; Jiping Ge; Xingfei Yan; Side Liu (Engineering Structures, 2023)

Construction of an ultra-stable mixed conductive layer to stabilize the solid-state electrolyte/Na interface by in-situ interface chemistry - Yujie Yang; Yisu Hao; Yan Zhang; Cong Huang; Bin Yao; Yang Qian; Ge Chang; Zhixiao Liu; Qunli Tang; Aiping Hu; Xiaohua Chen (Chemical Engineering Journal, 2023)

Efficient singlet oxygen nanogenerator with low-spin iron for selective contaminant decontamination - Jingjing Jiang; Shu Niu; Shengda Liu; Hao Zhang; Yansong Liu; Tongze Sun; Donglong Shi; Bowen Zhao; Ge Yan; Mingxin Huo; Dandan Zhou; Shuangshi Dong (Chemical Engineering Journal, 2023)

Demethylation-Driven ligase chain reaction for simultaneously sensitive detection of m6A demethylase FTO and m1A demethylase ALKBH3 in breast cancer at Single-Molecule level - Ming-hao Liu; Qian Zhang; Wan-tong Yu; Jian-Ge Qiu; Hui-min Yuan; Chuan-rui Wang; Bing-Hua Jiang; Yan Zhang; Chun-yang Zhang (Chemical Engineering Journal, 2023)

The influence of spermidine on the build-up of fucoxanthin in Isochrysis sp. Acclimated to varying light intensities - Yahui Bo; Shanshan Wang; Feifei Ma; Artem Yurevich Manyakhin; Guilin Zhang; Xiaohui Li; Chengxu Zhou; Baosheng Ge; Xiaojun Yan; Roger Ruan; Pengfei Cheng (Bioresource Technology, 2023)

Generating high spatial resolution exposure estimates from sparse regulatory monitoring data - Yihui Ge; Zhenchun Yang; Yan Lin; Philip K. Hopke; Albert A. Presto; Meng Wang; David Q. Rich; Junfeng Zhang (Atmospheric Environment, 2023)

Hypothalamic-Modified New Hippocampal Neurons for Alzheimer’s Disease - Yan Gu; Shaoyu Ge (Neuroscience Bulletin, 2023)

Transcriptomic profiling of nuclei from paraformaldehyde-fixed and formalin-fixed paraffin-embedded brain tissues - Yunxia Guo; Junjie Ma; Zhengyue Li; Kaitong Dang; Qinyu Ge; Yan Huang; Guang-zhong Wang; Xiangwei Zhao (Analytica Chimica Acta, 2023)

Plants are the drivers of geographic variation of floral odours in brood site pollination mutualisms: A case study of Ficus hirta - Xiaoxia Deng; Bruno Buatois; Yan-Qiong Peng; Hui Yu; Yufen Cheng; Xuejun Ge; Magali Proffit; Finn Kjellberg (Acta Oecologica, 2023)

Eisenia fetida impact on cadmium availability and distribution in specific components of the earthworm drilosphere - Yan Ge; Caide Huang; Wenhao Zhou; Zhiqiang Shen; Yuhui Qiao (Environmental Science and Pollution Research, 2023)

Analysis of tobacco exposures and high-risk HPV infection in American women: National Health and Nutrition Examination Survey - Liangzi Jiang; Suting Ma; Ge Zhang; Lingling Jiang; Li Yan (Environmental Science and Pollution Research, 2023)
Nicotine is a known toxin, but its relationship with cervicovaginal high-risk human papillomavirus (HR-HPV) infection is uncertain. This study aimed to investigate whether tobacco exposure is associated with elevated cervicovaginal HR-HPV infection in US women, and if the strength of this association varies with the degree of exposure. Cross-sectional data from the 2011–2016 National Health and Nutrition Examination Survey (NHANES), which included a nationally representative sample of US women, were used for the study. Out of 12436 women aged 18–59 who participated in the interview, 3833 were ultimately enrolled in this study. Weighted logistic regression was used to estimate the link between tobacco exposure and cervicovaginal HR-HPV infection. The mean age of participants was 38.6 (SD 12.1) years, and non-Hispanic White individuals accounted for 37.3% of the sample. Those with any tobacco exposure tended to be younger (mean age 37.7 [SD 12.4] years vs 40.3 [11.2] years), non-Hispanic Black (27.8% vs. 15.1%), lower educated (41.8% vs. 29.4%), and have lower family income (39.9% vs. 23.5%). After adjustment, the odds of having HR-HPV infection were 1.32 (95% CI, 1.09–1.59) for those exposed to tobacco, remaining significant in multiple sensitivity analyses and across subgroups. This study, based on a nationally representative sample from the United States, suggests that tobacco exposure is a risk factor for elevated HR-HPV infection in women, highlighting the need for further research into reducing this modifiable risk factor.

The connection between six common air pollution particles and adult brain tumors: a meta-analysis of 26,217,930 individuals - Lu-Ting Shen; Meng-Wei Ge; Fei-Hong Hu; Yi-Jie Jia; Wen Tang; Wan-Qing Zhang; Dan-Yan Zhao; Wang-Qin Shen; Hong-Lin Chen (Environmental Science and Pollution Research, 2023)

Optimization of ship routing and allocation in a container transport network considering port congestion: A variational inequality model - Lingpeng Meng; Hu Ge; Xudong Wang; Wei Yan; Chuanfeng Han (Ocean & Coastal Management, 2023)

Novel and legacy brominated flame retardants in snakes and frogs: Tissue distribution, biomagnification, and maternal transfer - Guanzhen Sun; Xinyu Du; Yan Wu; Ge Yin; Luting Chen; Xiaojun Liu; Yihui Zhou; Yanling Qiu; Tian Lin (Science of The Total Environment, 2023)

Phenylalanine maintains the postharvest quality of ‘Jinfeng’ pear fruit by modulating the tricarboxylic acid cycle and chlorophyll catabolism - Miao Wang; Canying Li; Jiaqi Liu; Shuran Zhang; Yan Guo; Yueruxin Jin; Yonghong Ge (Postharvest Biology and Technology, 2023)

Lithospheric dripping triggered by slab break-off: A possible mechanism for Late Carboniferous magmatism in the eastern Central Asian Orogenic Belt - Zhichao Zhang; Zheng Ji; Wenchun Ge; Hao Yang; Yu Dong; Yanlong Zhang; Yan Jing; Haoran Wu (Lithos, 2023)

Copper enhanced arsenic-accumulation in As-hyperaccumulator Pteris vittata by upregulating its gene expression for As uptake, translocation, and sequestration - Chen-Jing Liu; You-Jing Peng; Chun-Yan Hu; Si-Xue He; Shu-Fen Xiao; Wei Li; Song-Ge Deng; Zhi-Hua Dai; Lena Q. Ma (Journal of Hazardous Materials, 2023)

Nitrification-denitrification co-metabolism in an algal-bacterial aggregates system for simultaneous pyridine and nitrogen removal - Xiaoyu Zhang; Dan Chen; Xinying Hou; Na Jiang; Yan Li; Shijian Ge; Yang Mu; Jinyou Shen (Journal of Hazardous Materials, 2023)

Cross-species analysis of transcriptome emphasizes a critical role of TNF-α in mediating MAP2K7/AKT2 signaling in zearalenone-induced apoptosis - Fa-Li Zhang; Ke-Xin Zhu; Jing-Ya Wang; Min Zhang; Jia-Mao Yan; Qing-Chun Liu; Xiao-Yuan Zhang; Jia-Chen Guo; Xuan Liu; Qi-Cheng Sun; Wei Ge; Lan Li; et al. (Journal of Hazardous Materials, 2023)

Rutin hydrate relieves neuroinflammation in zebrafish models: Involvement of NF-κB pathway as a central network - Ying Hu; Kun Jia; Yatong Zhou; Lixin Chen; Fei Wang; Xiaokun Yi; Yong Huang; Yurui Ge; Xiaomei Chen; Dalong Liao; Yuyang Peng; Yunlong Meng; et al. (Fish & Shellfish Immunology, 2023)

Genomic characterization and phylogenetic analysis of Aleutian mink disease virus identified in a sudden death mink case - Xingyang Cui; Yan Yang; Fang Wang; Jilong Luo; Ping Zhang; Hongyan Chen; Lili Zhao; Junwei Ge (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Multi-scale domain and microstructure engineering for the high-energy-storage BCZT based lead-free relaxor ferroelectric ceramics - Jiayue Song; Fei Yan; Jinfeng Lin; Guanglong Ge; Cheng Shi; Jin Qian; Yali Hao; Yongqi Wei; Wu Yao (Chemical Engineering Journal, 2023)

Dual Förster resonance energy transfer effects enables high photocurrent density and high fill factor in ternary organic solar cells - Hongqian Wang; Daobin Yang; Pengfei Ding; Lin Xie; Zhenyu Chen; Shuncheng Yang; Pengyu Yan; Yuanyuan Meng; Jianqi Zhang; Zhixiang Wei; Ziyi Ge (Chemical Engineering Journal, 2023)

Effect of heavy metals in aquaculture water on the growth of microalgae and their migration mechanism in algae-shellfish system - Haixia Wang; Chun Wang; Baosheng Ge; Xuezhi Zhang; Chengxu Zhou; Xiaojun Yan; Roger Ruan; Pengfei Cheng (Chemical Engineering Journal, 2023)

Mixotrophy, a more promising culture mode: Multi-faceted elaboration of carbon and energy metabolism mechanisms to optimize microalgae culture - Shengzhou Shan; Artem Yurevich Manyakhin; Chun Wang; Baosheng Ge; Jichang Han; Xuezhi Zhang; Chengxu Zhou; Xiaojun Yan; Roger Ruan; Pengfei Cheng (Bioresource Technology, 2023)

Unraveling the intracellular and extracellular self-defense of Chlorella sorokiniana toward highly toxic pyridine stress - Xinying Hou; Yan Li; Xiaoyu Zhang; Shijian Ge; Yang Mu; Jinyou Shen (Bioresource Technology, 2023)

Size-dependent chemical composition of atmospheric nanoparticles in urban Beijing during springtime - Yan Chen; Chenjuan Deng; Ting Lei; Junling Li; Chaofan Lian; Yiran Li; Jun Zheng; Jun Zhao; Dongbin Wang; Zhijun Wu; Lin Wang; Lei Li; et al. (Atmospheric Environment, 2023)

Identification of watermelon H3K4 and H3K27 genes and their expression profiles during watermelon fruit development - Yang Qiao; Yan-Ge Li; Tong-Lu Wei; Hai-Nan Liu; Mao-Song Pei; Xue-Jie Zhu; Zhong-Hou Zhu; Da-Long Guo (Molecular Biology Reports, 2023)

Development of a N6-methyladenosine-directed single quantum dot-based biosensor for sensitive detection of METTL3/14 complex activity in breast cancer tissues - Ming-hao Liu; Wan-tong Yu; Ning-ning Zhao; Jian-Ge Qiu; Bing-Hua Jiang; Yan Zhang; Chun-yang Zhang (Analytica Chimica Acta, 2023)

Sensitive quantification of mercury ions in real water systems based on an aggregation-collision electrochemical detection - Lizhen Liu; Meihong Peng; Zerong Liang; Hong Wu; Hailong Yan; Yi-Ge Zhou (Analytica Chimica Acta, 2023)

Cropland expansion delays vegetation spring phenology according to satellite and in-situ observations - Guosong Zhao; Jinwei Dong; Jilin Yang; Huanjiong Wang; Junhu Dai; Yan Zhou; Yaoping Cui; Quansheng Ge (Agriculture, Ecosystems & Environment, 2023)

Effect of environmental factors on expression of staphylococcal enterotoxin genes - Hong-na Li; Zhao-di Kang; Tao Wang; Tao Li; Yan-ge Yang; Wei-e Zhou; Fei Yuan (Environmental Science and Pollution Research, 2023)

Concentrations, influencing factors, risk assessment methods, health hazards and analyses of polycyclic aromatic hydrocarbons in dairies: a review - Yuxing Ge; Shimin Wu; Kai Yan (Critical Reviews in Food Science and Nutrition, 2023)

Two sesquiterpene lactones, arnicolide B and arnicolide C, isolated from Centipeda minima , exert anti-inflammatory effects in LPS stimulated RAW 264.7 macrophages via inactivation of the MAPK pathway - Ge Wang; Hongfang Liu; Qingran Zhang; Xiaofeng Mou; Yan Zhao; Huaying Fan; Hui Xu; Daquan Chen; Feng Qiu; Feng Zhao (Natural Product Research, 2023)

The behavior of microplastics and nanoplastics release from UV-aged masks in the water - Hao Liang; Ruiyang Guo; Di Liu; Ningning Song; Fangli Wang; Yan Li; Wei Ge; Chao Chai (Science of The Total Environment, 2023)

Cardioprotective properties of quercetin in fescue toxicosis-induced cardiotoxicity via heart-gut axis in lambs (Ovis Aries) - Jing Ge; Sarah Layne Shelby; Yongjie Wang; Palika Dias Morse; Ken Coffey; Jinlong Li; Tuoyu Geng; Yan Huang (Journal of Hazardous Materials, 2023)

GRPR down-regulation inhibits spermatogenesis through Ca2+ mediated by PLCβ/IP3R signaling pathway in long-term formaldehyde-exposed rats - Yan-qi Yang; Rui-fang Sun; Pan Ge; Wen-Xing Li; Xiang Zhang; Jian Zhang; Lu Ye; Nan Zhang; Si-yu Wang; Mo-qi Lv; Dang-xia Zhou (Food and Chemical Toxicology, 2023)

EMT-NH2 zeolite interlayer induces the formation of high-performance polyamide membrane - Shengchao Wei; Yaoli Guo; Ge Yang; Hailing Guo; Zifeng Yan; Svetlana Mintova; Q. Jason Niu (Chemical Engineering Journal, 2023)

Corrigendum to “Rno_circRNA_006061 participates in apoptosis induced by formaldehyde via activating p38/ATF3 pathway” [Chem. Biol. Interact. 381 (2023) 110584] - Pan Ge; Xue-wei Yuan; Xiang Zhang; Zhi-hao Liu; Si-yu Wang; Yan-qi Yang; Qian-nan Wang; Li-jian Qian; Ya-zhao Li; Dang-xia Zhou (Chemico-Biological Interactions, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Piezo2 Channel Upregulation is Involved in Mechanical Allodynia in CYP-Induced Cystitis Rats - Lei Liu; Yan Zhao; Wenhan An; Mengmeng Zhao; Ning Ding; Hanwen Liu; Nan Ge; Jiliang Wen; Xiulin Zhang; Shulu Zu; Wendong Sun (Molecular Neurobiology, 2023)
Mechanical sensing Piezo2 channel in primary sensory neurons has been shown contribute to mechanical allodynia in somatic chronic pain conditions. Interstitial cystitis (IC)-associated pain is often triggered by bladder filling, a presentation that mimics the mechanical allodynia. In the present study, we aimed to examine the involvement of sensory Piezo2 channel in IC-associated mechanical allodynia using a commonly employed cyclophosphamide (CYP)-induced IC model rat. Piezo2 channels in dorsal root ganglia (DRGs) was knocked down by intrathecal injections of Piezo2 anti-sense oligodeoxynucleotides (ODNs) in CYP-induced cystitis rats, and mechanical stimulation–evoked referred bladder pain was measured in the lower abdomen overlying the bladder using von Frey filaments. Piezo2 expression at the mRNA, protein, and functional levels in DRG neurons innervating the bladder was detected by RNA-fluorescence in situ hybridization, western blotting, immunofluorescence, and Ca 2+ imaging, respectively. We found that Piezo2 channels were expressed on most (> 90%) of the bladder primary afferents, including afferents that express CGRP, TRPV1 and stained with isolectin B4. CYP-induced cystitis was associated with Piezo2 upregulation in bladder afferent neurons at the mRNA, protein, and functional levels. Knockdown of Piezo2 expression in DRG neurons significantly suppressed mechanical stimulation–evoked referred bladder pain as well as bladder hyperactivity in CYP rats compared to CYP rats treated with mismatched ODNs. Our results suggest upregulation of Piezo2 channels is involved in the development of bladder mechanical allodynia and bladder hyperactivity in CYP-induced cystitis. Targeting Piezo2 might be an attractive therapeutic approach for IC-related bladder pain.

Chinese “Scholars’ Stones”: a Potential Heritage Stone Resource Under Strong Anthropogenic Pressure - Weilun Kong; Yunhuai Li; Kongliang Li; Mo Chen; Yan Peng; Degao Wang; Lijun Chen; Linghong Ge; Pei Yang; Huiju Wu; Jifei Hu (Geoheritage, 2023)

Hyperglycemia symptom amelioration by Ascophyllum nodosum polysaccharides in mice with type 2 diabetes - Ligen Chen; Liang Shen; Lingyun Zhu; Fengwei Li; Xiaodong Ge; Xiujuan Xia; Hongwei Yan; Tingting Liu; Wei Xu; Rong Shao (Algal Research, 2023)

Comparative analysis of the molecular response characteristics in Platycodon grandiflorus irradiated with heavy ion beams and X-rays - Xiao Liu; Yan Du; Chaoli Xu; Fusheng Wang; Xuehu Li; Luxiang Liu; Xiaohui Ma; Yuanmeng Wang; Linghui Ge; Weibin Ren; Ling Jin; Libin Zhou (Life Sciences in Space Research, 2023)

Quantitative analysis of abandonment and grain production loss under armed conflict in Ukraine - Tingting He; Maoxin Zhang; Wu Xiao; Ge Zhai; Yan Wang; Andong Guo; Cifang Wu (Journal of Cleaner Production, 2023)

Designing low-carbon cement-free binders for stabilization/solidification of MSWI fly ash - Chen Sun; Weizhe Ge; Yuying Zhang; Lei Wang; Yan Xia; Xiaoqing Lin; Qunxing Huang; Shengyong Lu; Daniel C.W. Tsang; Jianhua Yan (Journal of Environmental Management, 2023)

Oxidative acid leaching of indium phosphide waste and recovery of indium metal by cementation with aluminum - Xiaofeng Zhang; Tao Ge; Liang Xu; Yan Sun; Cheng Yang; Yonglin Yao; Yongpan Tian; Zhuo Zhao (Hydrometallurgy, 2023)

Fate of selenium in a Se-enriched region of North China: Translocation, bioaccumulation, source, and health benefits - Kui Cai; Yan Zhao; Zefeng Song; Wenlou Luan; Jian Yang; Li Hu; Xin Liu; Ge Lei; Avelino Núñez Delgado (Environmental Research, 2023)

Rno_circRNA_006061 participates in apoptosis induced by formaldehyde via activating p38/ATF3 pathway - Pan Ge; Xue-wei Yuan; Xiang Zhang; Zhi-hao Liu; Si-yu Wang; Yan-qi Yang; Qian-nan Wang; Li-jian Qian; Ya-zhao Li; Dang-xia Zhou (Chemico-Biological Interactions, 2023)

Multi-scale risk assessment and mitigations comparison for COVID-19 in urban public transport: A combined field measurement and modeling approach - Yinshuai Feng; Yan Zhang; Xiaotian Ding; Yifan Fan; Jian Ge (Building and Environment, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Role of TPEN in Amyloid-β25–35-Induced Neuronal Damage Correlating with Recovery of Intracellular Zn2+ and Intracellular Ca2+ Overloading - Wen-bo Chen; Yu-xiang Wang; Hong-gang Wang; Di An; Dan Sun; Pan Li; Tao Zhang; Wan-ge Lu; Yan-qiang Liu (Molecular Neurobiology, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Aphanochaete xiantaoensis sp. nov., a new member of green algal genus Aphanochaete (Chaetophoraceae, Chaetophorales) based on morphology and molecular phylogeny - Benwen Liu; Jianhua Ge; Yangliang Chen; Qiufeng Yan; Huan Zhu; Guoxiang Liu (Biologia, 2023)

Transcriptome analysis reveals reduced immunity and metabolic level under cold stress in Mauremys mutica - Jiahui OuYang; Yangchun Gao; Yufeng Wei; Huangping Huang; Yan Ge; Jun Zhao; Shiping Gong (Frontiers in Marine Science, 2023)
The yellow pond turtle ( Mauremys mutica ) is widely cultured for food, medicine and for keeping as pets in China. The high risk of disease outbreaks and mortality caused by sudden sharp temperature drop events has significant negative effects on the aquaculture industry of M. mutica . However, the mechanism underlying the damage caused by cold stress is still unclear. To fill this gap, we performed transcriptome sequencing of M. mutica samples collected at three sampling time points (3h, 24h and 48h) during cold treatment, and at a recovery time point (96 h after the end of cold stress). The results showed that immunity and metabolism-related pathways (neuroactive ligand-receptor interactions, cytokine-cytokine receptor interactions and NOD-like receptor signaling pathways) were significantly enriched at both 24h and 48h. The expression of immunity and metabolism-related genes (BS2A1, PIWIL2 and Fads1) significantly decreased at all-time points compared to the control group. These results suggested that impaired immunity and depressed metabolism under cold stress may be the main cause of the massive cold-stress mortality of M. mutica . This study provides novel insights into the molecular mechanisms underlying mass disease and mortality caused by sudden sharp temperature drop events in M. mutica .

Anti-ricin toxin human neutralizing antibodies and DMAbs protection against ricin toxin poisoning - Haotian Yu; Meng Wu; Na Zhao; Mingxin Dong; Yan Wang; Kaikai Yu; Chengbiao Sun; Na Xu; Liangpeng Ge; Wensen Liu (Toxicology Letters, 2023)

A stabilizing benders decomposition method for the accessibility-oriented charging station location problem - Maocan Song; Lin Cheng; Huimin Ge; Yan Li; Chao Sun (Sustainable Cities and Society, 2023)

Mechanisms and adsorption capacities of ball milled biomass fly ash/biochar composites for the adsorption of methylene blue dye from aqueous solution - Huaiyan Li; Jie Kong; Haiting Zhang; Jiale Gao; Yan Fang; Jiaqi Shi; Tao Ge; Ting Fang; Yanhong Shi; Rong Zhang; Ningyuan Zhang; Xinju Dong; et al. (Journal of Water Process Engineering, 2023)

Promoting sensitive colorimetric detection of hydroquinone and Hg2+ via ZIF-8 dispersion enhanced oxidase-mimicking activity of MnO2 nanozyme - Na Liang; Xinyue Ge; Yan Zhao; Lian Xia; Zhi-Ling Song; Rong-Mei Kong; Fengli Qu (Journal of Hazardous Materials, 2023)

Mechanistic insights into the supramolecular structure and physicochemical properties of twin-screw extruded high amylose corn starch with different amylose content by improved electron beam irradiation - Xiangzhen Ge; Hao Duan; Yaxi Zhou; Shiqi Zhou; Huishan Shen; Wei Liang; Zhuangzhuang Sun; Wenjie Yan (Innovative Food Science & Emerging Technologies, 2023)

Conductive metal-organic frameworks with wheel-shaped metallomacrocycle subunits as high-performance supercapacitor electrodes - Yong Yan; Xihao Lin; Jingyuan Ge; Xinhua Li (Chemical Engineering Journal, 2023)

Low-temperature highly selective water delignification based on geopolymer materials - Tao Wang; Jianli Tan; Yan He; Yuanyuan Ge; Xuemin Cui (Bioresource Technology, 2023)

The combined effect of seawater salinity and duration on the survival and growth of eelgrass Zostera marina - Yan-Hao Zhang; Jian-Du Li; Wen-Jie Yan; Fan-Shu Luo; Li Wang; Li-Ming Zuo; Jun-Ge Xu; Wen-Tao Li; Pei-Dong Zhang (Aquatic Botany, 2023)

A review of filamentous sludge bulking controls from conventional methods to emerging quorum quenching strategies - Xin Lu; Ge Yan; Liang Fu; Bin Cui; Jinfeng Wang; Dandan Zhou (Water Research, 2023)

Tectonic nature, subduction, and closure of the Mudanjiang Ocean: Insights from newly discovered oceanic fragments in the Luobei Heilongjiang Complex - Guan-Ying Yu; Hao Yang; Jia-Hao Jing; Xin Ding; Zheng Ji; Yan-Long Zhang; Yu Dong; Wen-chun Ge (Lithos, 2023)

Integrative transcriptome and metabolome revealed the molecular mechanism of Bacillus megaterium BT22-mediated growth promotion in Arabidopsis thaliana - Xiao Liu; Yan Du; Xiaofan Na; Man Wang; Ying Qu; Linghui Ge; Yuanmeng Wang; Linqi Gao; Wenke Bai; Yurong Bi; Libin Zhou (Journal of Plant Physiology, 2023)

Microplastics exacerbate co-occurrence and horizontal transfer of antibiotic resistance genes - Xi Yu; Zhen-Chao Zhou; Xin-yi Shuai; Ze-jun Lin; Zhe Liu; Jin-yu Zhou; Yan-han Lin; Guang-shu Zeng; Zi-ye Ge; Hong Chen (Journal of Hazardous Materials, 2023)

Early Cretaceous Ningguo-Guangde weakly fractionated I-type granitoids, Jiangnan tungsten belt, China: Implications for petrogenesis and W Mo mineralization - Xin Zhang; Jiancheng Xie; Shan Huang; Likai Ge; Quanzhong Li; Jianmin Liu; Jun Yan (Journal of Geochemical Exploration, 2023)

Recycling of waste indium tin oxide target for In-Sn alloy production based on molten salt electrochemistry - Liang Xu; Tao Ge; Gaojie Chen; Yan Sun; Xiaofeng Zhang; Zhongsheng Hua; Yongpan Tian; Zhuo Zhao (Journal of Environmental Chemical Engineering, 2023)

Chlorogenic acid alleviates oxidative damage in hepatocytes by regulating miR-199a-5p/GRP78 axis - Jiaxin Li; Hengju Ge; Yang Xu; Jiahong Xie; Naymul Karim; Fujie Yan; Jianling Mo; Wei Chen (Food Bioscience, 2023)

Ameliorative effect of Fructus Gardeniae against lipotoxicity associated hepatocytes injury through activating Nrf2 signaling pathway - Hengju Ge; Jiaxin Li; Yang Xu; Jiahong Xie; Naymul Karim; Fujie Yan; Jianling Mo; Wei Chen (Food Bioscience, 2023)

Curcumin alleviates lipid deposition in hepatocytes through miR-3666/AMPK axis regulation - Hengju Ge; Jiaxin Li; Yang Xu; Jiahong Xie; Naymul Karim; Fujie Yan; Jianling Mo; Wei Chen (Food Bioscience, 2023)

In situ assembly of graphitic carbon nitride/polypyrrole in a thin-film nanocomposite membrane with highly enhanced permeability and durability - Mengni Ge; Zhuohui Jia; Yan Yang; Ping Dong; Chao Peng; Xi Zhang; Raf Dewil; Yan Zhao; Bart Van der Bruggen; Jianfeng Zhang (Desalination, 2023)

Characteristics prediction of hydrothermal biochar using data enhanced interpretable machine learning - Chao Chen; Zhi Wang; Yadong Ge; Rui Liang; Donghao Hou; Junyu Tao; Beibei Yan; Wandong Zheng; Rositsa Velichkova; Guanyi Chen (Bioresource Technology, 2023)

Homogenization of trees in urban green spaces along the moisture gradient in China - Yan Ouyang; Yi Chen; Guofu Yang; Yuan Ren; Mingjian Yu; Jie Chang; Ying Ge (Urban Forestry & Urban Greening, 2023)

Urban heat dome flow deflected by the Coriolis force - Yan Zhang; Xiaoxue Wang; Yifan Fan; Yongling Zhao; Jan Carmeliet; Jian Ge (Urban Climate, 2023)

Pericarp starch metabolism is associated with caryopsis development and endosperm starch accumulation in common wheat - Jiahui Zhuo; Ke Wang; Ning Wang; Caihong Xing; Da Peng; Xinyu Wang; Ge Qu; Caiyun Kang; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Science, 2023)

Readily regenerated porous fiber-supported metal tin sulfide for rapid and selective removal of cesium from wastewater - Can Liu; Haojie Ge; Linxue Yan; Xiaoping Yu; Yafei Guo; Nelson Belzile; Tianlong Deng (Journal of Cleaner Production, 2023)

The differentiation between condensed and hydrolyzable tannins with different molecular weights in affecting the rheological property of wheat flour-based dough - Wenju Ge; Yan Xu; Meng Niu; Caihua Jia; Siming Zhao (Journal of Cereal Science, 2023)

Antibiofilm mechanism of dielectric barrier discharge cold plasma against Pichia manshurica - Xinlei Hou; Jin Wang; Yuan Mei; Lihong Ge; Jing Qian; Yuli Huang; Menglu Yang; Huajia Li; Yanli Wang; Zhengcai Yan; Dengshui Peng; Jianhao Zhang; et al. (Innovative Food Science & Emerging Technologies, 2023)

Active pollination in a functionally dioecious Ficus species: An interplay between pollinator behaviour and floral morphology - Bai-Ge Miao; Ming-Xin Liu; Bo Wang; Yan-Qiong Peng; Annick Lesne; Finn Kjellberg; K．Charlotte Jandér (Flora, 2023)

Ion transmembrane behaviors in selective electrodialysis for acid recovery: Impact of ion categories - Junying Yan; Huangying Wang; Haiyang Yan; Ruirui Li; Rong Fu; Weicheng Fu; Liang Ge; Baoying Wang; Yaoming Wang; Tongwen Xu (Desalination, 2023)

Highly enhanced energy storage performance of trilayered gradient polymer-based nanocomposite via 2D SNO@Ag nanosheets - Hairui Bai; Guanglong Ge; Fei Yan; Kun Zhu; Jin Qian; Cheng Shi; Yanxia Li; Haijiao Xie; Bo Shen; Jiwei Zhai (Chemical Engineering Journal, 2023)

Uncertainty in regional scale assessment of landslide susceptibility using various resolutions - Ge Yan; Guoan Tang; Sijin Li; Dingyang Lu; Liyang Xiong; Shouyun Liang (Natural Hazards, 2023)

Methylated Chromenoquinoline as a Novel Nucleus Fluorescent Probe for Nucleic Acid Imaging - Zhi-Hao Zhang; Qing Yu; Gang Zhang; Hai-Yan Peng; Ru Sun; Yu-Jie Xu; Jian-Feng Ge (Journal of Fluorescence, 2023)

Dispersal syndromes mediate phylogenetic distance decay relationships in a dendritic stream network - Yihao Ge; Jorge García‐Girón; Jani Heino; Zhenyuan Liu; Chen Zhang; Yunzhi Yan; Zhicai Xie; Zhengfei Li (Journal of Biogeography, 2023)
Aim Understanding the mechanisms underlying the structure and connectivity of ecological communities is a central issue in biogeography. Dispersal syndromes are tightly woven into organisms' life history seen across populations and communities, but measuring dispersal is still complicated in practice. We investigated the role of dispersal syndromes (here, associated with body size, adult flying ability and voltinism) to predict phylogenetic distance decay relationships (DDRs) of aquatic insect assemblages in dendritic stream networks. Location Du River Basin, China. Taxon Aquatic insects (Coleoptera, Diptera, Ephemeroptera, Hemiptera, Lepidoptera, Megaloptera, Odonata, Plecoptera and Trichoptera). Methods We applied multiple methods (i.e. deconstruction approach, null models, Mantel tests and partial Mantel tests) to enhance our basic understanding of phylogenetic distance decay patterns. To provide additional insights into correlates of phylogenetic dissimilarity between stream sites, we modelled potential dispersal routes based on overland, watercourse and cost distances. Results Overland distances were among the main correlates of phylogenetic distance decay in the stream networks studied, suggesting that aquatic insects disperse overland seeking for habitats suitable for survival and reproduction. However, local environmental filtering was generally more important for phylogenetic DDRs than geographical distances alone. The interaction between environmental vs. dispersal processes in driving spatial patterns of phylogenetic dissimilarity was contingent on different dispersal syndromes. More specifically, significant phylogenetic DDRs were detected only for subsets of large‐bodied, univoltine taxa with strong adult flying abilities, such as dragonflies. Main Conclusions Overall, historical constraints affect the phylogenetic DDRs in aquatic insects. Dispersal syndromes associated with body size, adult flying ability and voltinism are key features underlying distance decay in phylogenetic assemblage similarity and the evolutionary legacies of aquatic insects in dendritic stream networks.

Surface wave exploration technology for the tunnel overlying strata with vehicle vibration source - Yuefeng Yan; Chengyu Sun; Tengfei Lin; Jiao Wang; Xixi Huang; Qixin Ge; Dayong Zhou (Tunnelling and Underground Space Technology, 2023)

Sulfur dioxide may predominate in the adverse effects of ambient air pollutants on semen quality among the general population in Hefei, China - Feng Zhang; Hang Li; Wenting Xu; Ge Song; Zhanpeng Wang; Xiaohong Mao; Yiqiu Wei; Mengyang Dai; Yuying Zhang; Qunshan Shen; Feifei Fu; Jing Tan; et al. (Science of The Total Environment, 2023)

Adsorptive removal of oxytetracycline in wastewater by Cu/Al doped carbon microspheres prepared from low-molecular-weight chitosan - Yan Huang; Leichao Wang; Ge Niu; Mingqing Hua; Linhua Zhu; Peng Cui; Xiaowei Li; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Journal of Environmental Chemical Engineering, 2023)

Characteristics, chemical transformation and source apportionment of volatile organic compounds (VOCs) during wintertime at a suburban site in a provincial capital city, east China - BaoLin Wang; ZhenGuo Liu; ZiAng Li; YuChun Sun; Chen Wang; ChuanYong Zhu; Lei Sun; Na Yang; Ge Bai; GuoLan Fan; XiaoYan Sun; ZhiYong Xia; et al. (Atmospheric Environment, 2023)

Optical Coherence Tomography in Cerebrovascular Disease: Open up New Horizons - Ran Xu; Qing Zhao; Tao Wang; Yutong Yang; Jichang Luo; Xiao Zhang; Yao Feng; Yan Ma; Adam A. Dmytriw; Ge Yang; Shengpan Chen; Bin Yang; et al. (Translational Stroke Research, 2023)

Transcriptomic and proteomic analysis reveals (E)-2-hexenal modulates tomato resistance against Botrytis cinerea by regulating plant defense mechanism - Jihong Zhang; Yuqiong Li; Shenglong Du; Zhiping Deng; Quanwu Liang; Ge Song; Haihua Wang; Mingli Yan; Xuewen Wang (Plant Molecular Biology, 2023)

Applications of bioremediation and phytoremediation in contaminated soils and waters: CREST publications during 2018–2022 - Chen-Jing Liu; Song-Ge Deng; Chun-Yan Hu; Peng Gao; Eakalak Khan; Chang-Ping Yu; Lena Q. Ma (Critical Reviews in Environmental Science and Technology, 2023)

Ecotoxicity induced by total, water soluble and insoluble components of atmospheric fine particulate matter exposure in Caenorhabditis elegans - Xiaoming Liu; Pengxiang Ge; Zhenyu Lu; Maoyu Cao; Wankang Chen; Zhansheng Yan; Mindong Chen; Junfeng Wang (Chemosphere, 2023)

Recent advances in the gut microbiome and microbial metabolites alterations of coronary artery disease - Yuxiang Dai; Zhonghan Sun; Yan Zheng; Junbo Ge (Science Bulletin, 2023)

A continuous paleorecord of vegetation and environmental change from Erxianyan Wetland over the past 60,000 years in central China - Menglin Song; John Dodson; Fengyan Lu; Ge Shi; Hong Yan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Enhanced degradation of poly(ethylene terephthalate) by the addition of lactic acid / glycolic acid: composting degradation, seawater degradation behavior and comparison of degradation mechanism - Tian-Yuan Liu; Peng-Yuan Xu; Dan Huang; Bo Lu; Zhi-Chao Zhen; Wei-Zhen Zheng; Yan-Chao Dong; Xiao Li; Ge-Xia Wang; Jun-Hui Ji (Journal of Hazardous Materials, 2023)

Interaction and phase behavior of whey protein and propylene glycol alginate complex condensates - Ge Shi; Ce Shi; Yongkang Luo; Hui Hong; Jiaran Zhang; Yan Li; Yuqing Tan (Food Chemistry, 2023)

Prevalence and genetic diversity of canine coronavirus in northeastern China during 2019–2021 - Nuowa Li; Yue Bai; Runhang Liu; Zhiyuan Guo; Xin Yan; Kongrui Xiang; Feng Liu; Lili Zhao; Junwei Ge (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Bifunctional carbon nanofibrous interlayer embedded with cobalt single atoms for polysulfides trapping and catalysis in lithium-sulfur batteries - Beibei Song; Haoyue Zhao; Gang Zhao; Han Li; Can Ge; Guilong Yan; Jian Fang (Chemical Engineering Journal, 2023)

Response characteristics of antibiotic resistance genes and bacterial communities during agricultural waste composting: Focusing on biogas residue combined with biochar amendments - Yuewei He; Xiaowei Yin; Fanghong Li; Bo Wu; Ling Zhu; Dabing Ge; Nanyi Wang; Anwei Chen; Lihua Zhang; Binghua Yan; Hongli Huang; Lin Luo; et al. (Bioresource Technology, 2023)

Fine mapping and candidate gene analysis of qFL-A12-5: a fiber length-related QTL introgressed from Gossypium barbadense into Gossypium hirsutum - Xianghui Xiao; Ruixian Liu; Juwu Gong; Pengtao Li; Ziyin Li; Wankui Gong; Aiying Liu; Qun Ge; Xiaoying Deng; Shaoqi Li; Quanjia Chen; Hua Zhang; et al. (Theoretical and Applied Genetics, 2023)

Deciphering differences in microbial community composition and multifunctionality between healthy and Alternaria solani-infected potato rhizosphere soils - Fangyan Wang; Fang Wang; Haoqing Zhang; Fangjin Qin; Wu Xiang; Chuanfa Wu; Chengqi Yan; Zhenke Zhu; Jianping Chen; Tida Ge (Plant and Soil, 2023)

Remediation of polycyclic aromatic hydrocarbons in aged agricultural soil using spent Pleurotus eryngii mushroom substrate - Wei Ge; Huan Zhou; Yan Li; Yanqin Wang; Zhenfeng Zhou; Juan Wu; Chao Chai (Journal of Soils and Sediments, 2023)

24-Epibrassinolide Enhances Resistance Against Colletotrichum fructicola by Promoting Lignin Biosynthesis in Camellia sinensis L. - Lan Zhang; Zheng Zhang; Golam Jalal Ahammed; Xiaorong Wang; Huihan Fang; Peng Yan; Li-Ping Zhang; Shibei Ge; Jianyu Fu; Wen-Yan Han; Xin Li (Journal of Plant Growth Regulation, 2023)

Characterizing spatial, diurnal, and seasonal patterns of agricultural irrigation expansion-induced cooling in Northwest China from 2000 to 2020 - Chao Zhang; Quansheng Ge; Jinwei Dong; Xuezhen Zhang; Yan Li; Songjun Han (Agricultural and Forest Meteorology, 2023)

Decoupling of N and P aggravated upward along food chains in an urban river ecosystem - Shenqun An; Zhengbing Yan; Ying Song; Qiang Fu; Feiyang Ge; Zehao Wu; Wei An; Wenxuan Han (Chemosphere, 2023)

Mixed bromine/chlorine transformation products of tetrabromobisphenol A formed in the combustion of printed circuit boards: Emission characteristics and transformation pathways - Xiang Ge; Yanpeng Gao; Yan Yang; Guanhui Chen; Shengtao Ma; Beibei Hu; Yingxin Yu; Taicheng An (Science of The Total Environment, 2023)

Surprising leopard restoration in fragmented ecosystems reveals connections as the secret to conservation success - Fu Yanwen; Zhao Guojing; Dai Wenqian; Wang Yue; Li Jiawei; Tan Mengyu; Li Yan; Liu Haoran; Xie Bing; Jin Xiao; Fan Enyu; Zhao Lulu; et al. (Science of The Total Environment, 2023)

Hyperforin: A natural lead compound with multiple pharmacological activities - Xin-Xin Li; Yu Yan; Jia Zhang; Kang Ding; Cong-Yuan Xia; Xue-Ge Pan; Yan-Jing Shi; Jie-Kun Xu; Jun He; Wei-Ku Zhang (Phytochemistry, 2023)

Damming has changed the migration process of microplastics and increased the pollution risk in the reservoirs in the Shaying River Basin - Jiachen Shen; Xu Gu; Run Liu; Hongyu Feng; Dianpeng Li; Yan Liu; Xufei Jiang; Ge Qin; Shuqing An; Ning Li; Xin Leng (Journal of Hazardous Materials, 2023)

CO2 methanation over the Ni-based catalysts supported on the hollow ZSM-5 zeolites: Effects of the hollow structure and alkaline treatment - Yan Cui; Bin Chen; Leilei Xu; Mindong Chen; Cai-e Wu; Jian Qiu; Ge Cheng; Ning Wang; Jingxin Xu; Xun Hu (Fuel, 2023)

Low-tortuosity carbon electrode derived from Wood@ZIF-67 for supercapacitor applications - Zhen Zhang; Songlin Deng; Delong Wang; Yan Qing; Ge Yan; Lei Li; Yiqiang Wu (Chemical Engineering Journal, 2023)

Modification of anaerobic digestion model No.1 with Machine learning models towards applicable and accurate simulation of biomass anaerobic digestion - Yadong Ge; Junyu Tao; Zhi Wang; Chao Chen; Lan Mu; Haihua Ruan; Yakelin Rodríguez Yon; Hong Su; Beibei Yan; Guanyi Chen (Chemical Engineering Journal, 2023)

Synergistically enhanced structural, thermal and interfacial stability of K0.45MnO2 via tailoring the local structure for high-energy and high-power potassium-ion batteries - Yan Huang; Xinyuan Zhang; Hezhe Lin; Zhixuan Wei; Yi Zeng; Xin Ge; Wei Zhang; Xiaoqi Wang; Xu Jin; Ze Xiang Shen; Fei Du (Chemical Engineering Journal, 2023)

A numerical rotating water tank can reproduce the Coriolis effect on the urban heat dome flow - Yifan Fan; Yan Zhang; Shaopeng Wang; Xiaoxue Wang; Jiang Lu; Jian Ge (Building and Environment, 2023)

Simulation of integrated anaerobic digestion-gasification systems using machine learning models - Yadong Ge; Junyu Tao; Zhi Wang; Chao Chen; Rui Liang; Lan Mu; Haihua Ruan; Yakelin Rodríguez Yon; Beibei Yan; Guanyi Chen (Bioresource Technology, 2023)

Chronic hypoxia and Cu2+ exposure induce gill remodeling of largemouth bass through endoplasmic reticulum stress, mitochondrial damage and apoptosis - Qiao Liu; Hong Wang; Jiayu Ge; Lisen Li; Jie Luo; Kuo He; Haoxiao Yan; Xin Zhang; Rabia Tahir; Wei Luo; Shiyi Chen; Zhang Cheng; et al. (Aquatic Toxicology, 2023)

Genome-wide signatures of the geographic expansion and breeding of soybean - Ying-Hui Li; Chao Qin; Li Wang; Chengzhi Jiao; Huilong Hong; Yu Tian; Yanfei Li; Guangnan Xing; Jun Wang; Yongzhe Gu; Xingpeng Gao; Delin Li; et al. (Science China Life Sciences, 2023)

Attenuated African swine fever virus through serial passaging of viruses in cell culture: a brief review on the knowledge gathered during 60 years of research - Xiaoyue Zhang; Zhenzhong Wang; Shengqiang Ge; Yuanyuan Zuo; Haodong Lu; Yan Lv; Naijun Han; Yumei Cai; Xiaodong Wu; Zhiliang Wang (Virus Genes, 2023)

Trace elements in red swamp crayfish (Procambarus clarkii) in China: Spatiotemporal variation and human health implications - Hui Li; Huaiyan Li; Haiting Zhang; Jing Cao; Tao Ge; Jiale Gao; Yan Fang; Wenling Ye; Ting Fang; Yanhong Shi; Rong Zhang; Xinju Dong; et al. (Science of The Total Environment, 2023)

External-loop split-type dynamic membrane photobioreactor for the treatment of high-strength pyridine wastewater: Improved photosynthetic oxygenation and mitigated membrane fouling - Xiaoyu Zhang; Na Jiang; Xinying Hou; Yan Li; Shijian Ge; Yang Mu; Jinyou Shen (Journal of Hazardous Materials, 2023)

Cadmium contributes to heat tolerance of a hyperaccumulator plant species Sedum alfredii - Lingling Xu; Shengke Tian; Yan Hu; Jianqi Zhao; Jun Ge; Lingli Lu (Journal of Hazardous Materials, 2023)

Measurement of atmospheric nanoparticles: Bridging the gap between gas-phase molecules and larger particles - Chao Peng; Chenjuan Deng; Ting Lei; Jun Zheng; Jun Zhao; Dongbin Wang; Zhijun Wu; Lin Wang; Yan Chen; Mingyuan Liu; Jingkun Jiang; Anpei Ye; et al. (Journal of Environmental Sciences, 2023)

Mechanism of iron doping promoting high temperature deNOx and anti-water vapor and SO2 poisoning of ZrW(Fe)Ox - Zhanzhi Ge; Yan Ding; Xinqi Huang; Yuesong Shen (Fuel, 2023)

One-step synthesis of porous Li4SiO4 pellets by polyvinyl alcohol (PVA) method for CO2 capture - Ruicheng Fu; Ge Yu; Junna Cheng; Yingchao Hu; Shuiping Yan (Fuel, 2023)

CO2 methanation over the Ni-based catalysts supported on nano-CeO2 with varied morphologies - Yufang Bian; Chunying Xu; Xueying Wen; Leilei Xu; Yan Cui; Shuhan Wang; Cai-e Wu; Jian Qiu; Ge Cheng; Mindong Chen (Fuel, 2023)

Characterization and comparison of lipids from human and ewe colostrum based on lipidomics analysis - Shuangshuang Wang; Zhaojun Liu; Yuxuan Song; Yan Zhang; Lili Zhao; Lei Zhang; Xin Lü; Haiyan Wang; Ximei Zhang; Jiaying Zhang; Wupeng Ge (Food Chemistry, 2023)

Effect of dry heat treatment on multi-structure, physicochemical properties, and in vitro digestibility of potato starch with controlled surface-removed levels - Qian Zhang; Hao Duan; Yaxi Zhou; Shiqi Zhou; Xiangzhen Ge; Huishan Shen; Wenhao Li; Wenjie Yan (Food Hydrocolloids, 2023)

Numerical study on flexural and bond-slip behaviours of GFRP profiled-concrete composite beams with groove shear connector - Wenjie Ge; Zhiwen Zhang; Zhongwei Guan; Ashraf Ashour; Yue Ge; Yiwen Chen; Hongbo Jiang; Chuanzhi Sun; Shan Yao; Weihua Yan; Dafu Cao (Engineering Structures, 2023)

Estimation of input energy spectrum from pseudo-velocity response spectrum incorporating the influences of magnitude, distance, and site conditions - Haizhong Zhang; Yan-Gang Zhao; Fang-Wen Ge; Yingchi Fang; Tsutomu Ochiai (Engineering Structures, 2023)

Gold nanoclusters-engineered dual-emitting nanofibrous film for fluorescent discrimination and visual sensing of explosives - Wenxing Gao; Qiang Li; Wencheng Zhong; Xiaomeng Zhou; Yibo Ge; Qi-Long Yan; Li Shang (Chemical Engineering Journal, 2023)

Fluidized nanoparticles catalyzed oxygen evolution reaction: Enhanced stability, kinetics and electrocatalytic activity - Dianmei Song; Hailong Yan; Wei Xu; Yi-Ge Zhou (Chemical Engineering Journal, 2023)

Stimuli-responsive pesticide carriers based on porous nanomaterials: A review - Jie Zhou; Guangyang Liu; Zhaojiang Guo; Miao Wang; Chenyu Qi; Ge Chen; Xiaodong Huang; Shuo Yan; Donghui Xu (Chemical Engineering Journal, 2023)

Micro-tabless-pouch-cell (MTPC) with high energy density and exposed functional current collector for flexible device - Yige Xiong; Xiaohui Yan; Taibai Li; Huixin Jin; Ziliang Chen; Xuejiao Xu; Xiang Ji; Xiang Ge (Chemical Engineering Journal, 2023)

Design strategies of perovskite nanofibers electrocatalysts for water splitting: A mini review - Yaobin Wang; Yan Jiang; Yunxia Zhao; Xinlei Ge; Qian Lu; Ting Zhang; Dongsheng Xie; Meng Li; Yunfei Bu (Chemical Engineering Journal, 2023)

Comparisons of cirrus clouds and their linkages to meteorology at the SACOL and the SGP sites - Zixiang Dong; Jinming Ge; Ang Gao; Zeen Zhu; Jialin Yan; Qingyu Mu; Jing Su; Xuan Yang; Xiaoyu Hu (Atmospheric Research, 2023)

Shift work and nonalcoholic fatty liver disease incidence among Chinese rail workers: a 4-year longitudinal cohort study - Jiahui Xu; Shu Ni; Yuming Wang; Mengfan Yan; Xueli Yang; Han Ge; Zizhuo Jia; Ze Yang; Anqi Shan; Huanyu Liu; Nai-jun Tang (International Archives of Occupational and Environmental Health, 2023)

Evaluating the effects of contact time and leaching solution on measured solubilities of aerosol trace metals - Rui Li; Shuwei Dong; Chengpeng Huang; Feng Yu; Fu Wang; Xiaofei Li; Huanhuan Zhang; Yan Ren; Mingxian Guo; Qingcai Chen; Baozhu Ge; Mingjin Tang (Applied Geochemistry, 2023)

Darwin's naturalization conundrum reconciled by changes of species interactions - Jiang Wang; Shao‐Peng Li; Yuan Ge; Xiao‐Yan Wang; Song Gao; Tong Chen; Fei‐Hai Yu (Ecology, 2023)
Although phylogenetic distance between native and exotic species has a close link with their interactions, it is still unclear how environmental stresses and species interactions influence the relationship between phylogenetic distance and biological invasions. Here we assessed the effect of invader–native phylogenetic distance on the growth of the invader ( Symphyotrichum subulatum ) under three levels of drought (no, moderate, or intense drought). Under no drought, interspecific competition between close relatives was the dominant process and native communities more closely related to the invader showed higher resistance to invasion, supporting Darwin's naturalization hypothesis. In contrast, under intense drought, facilitation between close relatives by mutualism with arbuscular mycorrhizal fungi (AMF) became more important, and the invader became more successful in their more closely related native communities, supporting the preadaptation hypothesis. The colonization rate of AMF of the invader was higher in more closely related native communities regardless of the drought treatment, but it was only positively related to invader biomass under intense drought. Therefore, the shift of species interactions from competition to facilitation may be ascribed to the promotion of AMF to invasion occurring under intense drought, which leads to the effect of closely related natives on the invader shifting from negative to positive. Our results provide a new angle to resolve Darwin's naturalization conundrum from the change of species interactions along a stress gradient, and provide important clues for invasion management when species interactions change in response to global climatic change.

Enhance energy supply of largemouth bass (Micropterus salmoides) in gills during acute hypoxia exposure - Qiao Liu; Hong Wang; Jiayu Ge; Jie Luo; Kuo He; Haoxiao Yan; Xin Zhang; Rabia Tahir; Wei Luo; Zhiqiong Li; Song Yang; Liulan Zhao (Fish Physiology and Biochemistry, 2022)

Interannual shift of tropical high cloud diurnal cycle under global warming - Zhenquan Wang; Jinming Ge; Jialin Yan; Wenxue Li; Xuan Yang; Meihua Wang; Xiaoyu Hu (Climate Dynamics, 2022)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Synergistic removal of organic pollutants from water by CTF/BiVO4 heterojunction photocatalysts - Yan Yu; Yanan Sun; Beixiao Ge; Jiawen Yan; Kaili Zhang; Hui Chen; Jinxing Hu; Juntao Tang; Shuang Song; Tao Zeng (Environmental Science and Pollution Research, 2022)

Distribution and ecological risk assessment of heavy metals in sediments of Dajiuhu Lake Wetland in Shennongjia, China - Jiumei Wang; Jiwen Ge; Xiaojing Yang; Dandan Cheng; Chenhao Yuan; Ziwei Liu; Shiyu Yang; Yan Guo; Yansheng Gu (Environmental Science and Pollution Research, 2022)

Effect of gravel content on the detachment of colluvial deposits in Benggang - Li-ting Zhang; Fang Shuai; Li-bo Chen; Yan-he Huang; Jin-shi Lin; Yue Zhang; Hong-li Ge; Fang-shi Jiang (Journal of Mountain Science, 2022)

Two new alkaloids from Tibetan medicine of Hypecoum leptocarpum - Bo Sun; Israa Assani; Chun-Gu Wang; Mu-Xuan Wang; Ling-Fei Liu; Yan Li; Ge Yan; Yun-Ruo Yang; Zhi Chen; Zhi-Xin Liao (Natural Product Research, 2022)

Nutritional Components, Biochemical Characteristics, Enzyme Activities, and Growth Differences of Five Freshwater Fish Species? - Xiaona Jiang; Yan Li; Jingwen Tian; Chitao Li; Yanlong Ge; Xuesong Hu; Lei Cheng; Xiaodan Shi; Lianyu Shi; Zhiying Jia (Fishes, 2022)
Common carp (Cyprinus carpio) is an economically important fish worldwide, with many of its species bred for consumption. However, there are few reports on the comprehensive comparative analysis of the muscle nutritional quality and stress resistance characteristics of different common carp species. In this study, after 15 months of feeding in the same environment, the nutritional components, serum biochemical indices, liver antioxidant and intestinal digestive enzyme activities, and muscle growth-related gene expression were determined in Songpu mirror carp (SPM; Cyprinus carpio Songpumirror), Heilongjiang wild carp (HLJ; Cyprinus carpio haematopirus), cold-resistant strain of purse red carp (CPR; Cyprinus carpio ‘Red purse cold-resistant’), Songhe carp (SH; Cyprinus carpio ‘Songhe’), and Songpu carp (SP; Cyprinus carpio Songpu). Muscle nutrient composition showed that HLJ had a significantly lower crude fat content and higher docosahexaenoic acid (DHA) + eicosapentaenoic acid (EPA) proportion than the other four common carp species (p

Numerical study on crack propagation of rock mass using the time sequence controlled and notched blasting method - Xinping Li; Mingnan Xu; Yang Wang; Gang Wang; Junhong Huang; Weisong Yin; Ge Yan (European Journal of Environmental and Civil Engineering, 2022)

Genotyping USDA rice (Oryza spp.) mini-core collection with functional markers for important agronomic traits - Kehu Li; Lily Yan Wang; Huanhuan Ren; Yongyi Ge (Genetic Resources and Crop Evolution, 2022)

Twin peaks of in-hospital mortality among patients with STEMI across five phases of COVID-19 outbreak in China: a nation-wide study - Jianping Li; Nan Zhang; Ziyi Zhou; Xiao Huang; Weiyi Fang; Hongbing Yan; Jiyan Chen; Weimin Wang; Dingcheng Xiang; Xi Su; Bo Yu; Yan Wang; et al. (Science China Life Sciences, 2022)

Spatial variation in bacterial community and dissolved organic matter composition in groundwater near a eutrophic lake - Ning Ma; Li Gao; Yan Zhang; Zhengkui Ge; En Hu; Baozhu Pan; Jian Wang; Ming Li (Aquatic Ecology, 2022)

The preparation of slow-release fertilizers with biomass ash and water/waste acid solutions from desulfurization and denitrification of flue gas - Yongfeng Qi; Ziqian Wang; Panle Ge; Meiting Wang; Chuanling Zhang; Huawei Wang; Lingzhi Zhao; Jiang Wu; Yan Li (Environmental Science and Pollution Research, 2022)

Failure process of a lateral slope deposit and its effect on debris flood formation - Xiaojun Guo; Yonggang Ge; Meiqiang Zhan; Hua Yan (Bulletin of Engineering Geology and the Environment, 2022)

Determination of Fe, Ni, Cu, Zn, Cd and Pb in seawater by isotope dilution automatic solid-phase extraction—ICP-MS - Yuncong Ge; Ruifeng Zhang; Ziyuan Jiang; Zhan Shen; Maojun Yan (Acta Oceanologica Sinica, 2022)

Radioactivity of Strontium-90 in Soil Samples Along the Hai River in Tianjin, China - Fei Chen; Linlin Yan; Qiang Xiong; Xiao Ge; Jing Liang; Zhen Zhang; Shengyuan Yang; Ling Jiao (Water, Air, & Soil Pollution, 2022)

OsAPL controls the nutrient transport systems in the leaf of rice (Oryza sativa L.) - Zhen Yan; Man-Yu Yang; Biligen-Gaowa Zhao; Guo Li; Qing Chao; Feng Tian; Ge Gao; Bai-Chen Wang (Planta, 2022)

Dynamic changes of reactive oxygen species in paddy overlying water: mechanisms and implications - Shaochong Liu; Mengxi Tan; Danyu Huang; Dixiang Wang; Mengyuan Geng; Jialin Wen; Changyin Zhu; Liqiang Ge; Ning Chen; Yan Gao; Jiangye Li; Jianbin Pan; et al. (Journal of Soils and Sediments, 2022)

Regulation of OsLPR1 gene on the formation of rice root iron plaque under low phosphorus - Yan Ding; Menglian Ren; Shuangrong Mo; Jing Liu; Zegang Wang; Cailin Ge; Yulong Wang (Plant Biotechnology Reports, 2022)

The impact of TOPBP1 mutations in human cancers on the DNA damage response - Zhenzhen Yan; Xiuling Ge; Jiaxu Wang; Feng Xu; Mengyao Li; Xiuhua Liu; Xiaochun Yu; Chen Wu (Genome Instability & Disease, 2022)

Genetic variation and association mapping of phenolic, flavonoid content and antioxidant capacity in USDA rice mini-core collection - Kehu Li; Qingzhu Li; Lily Yan Wang; Huanhuan Ren; Yongyi Ge (Genetic Resources and Crop Evolution, 2022)

Geochronology and geochemistry of the W-Mo-ore-related granitic rocks from eastern Ningzhen, lower Yangtze river belt, eastern China - Fangyue Wang; Yongjie Guo; Haiyang Yan; Haiou Gu; He Sun; Can Ge (Acta Geochimica, 2022)

Transition in tectonic regime from the Paleo-Asian Ocean to Paleo-Pacific Ocean: constraints from the Jurassic adakitic and I-type granites, and calc-alkaline diorites at the northern margin of the North China Craton - Yan Jing; Wen-Chun Ge; Yu Dong; Hao Yang; Zheng Ji; Jun-Hui Bi; Hong-Ying Zhou; De-He Xing (International Geology Review, 2022)

Litter nitrogen concentration changes mediate effects of drought and plant species richness on litter decomposition - Jiang Wang; Yuan Ge; Johannes H. C. Cornelissen; Xiao-Yan Wang; Song Gao; Yi Bai; Tong Chen; Zhong-Wang Jing; Chong-Bang Zhang; Wen-Li Liu; Jun-Min Li; Fei-Hai Yu (Oecologia, 2022)

Analysis of volatile organic compounds in exhaled breath after radiotherapy - Dianlong Ge; Xue Zou; Yajing Chu; Jijuan Zhou; Wei Xu; Yue Liu; Qiangling Zhang; Yan Lu; Lei Xia; Aiyue Li; Chaoqun Huang; Pei Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Species Composition and Assemblages of Ichthyoplankton in Sansha Bay, Fujian Province, China - Yan Jiang; Bai-an Lin; Hao-yang He; Guang-mao Ding; Li-ting Yan; Ge Zhang; Min Liu; Lian-ming Zheng (Frontiers in Marine Science, 2021)
Sansha Bay (26.40−27.00°N, 119.50−120.20°E) is a typical semi-enclosed bay, located in northern Fujian Province, China, and adjacent to the East China Sea. The ichthyoplankton species composition and assemblage structure were investigated based on monthly sampling at 25 stations in April−September 2019, covering the important spring and summer spawning seasons in the region. Sampling was conducted in the first 3−5 days of the full moon or new moon phases using a standard plankton net through horizontal and vertical tows during daytime. In total, 25,819 ichthyoplankton samples were collected, of which 25,449 samples (i.e., 24,757 eggs and 692 larvae) were from horizontal tows. For horizontal tow samples, the ichthyoplankton were classified into 58 taxa in 15 orders and 23 families with a combination of external morphology and DNA barcoding analyses, from pelagic to demersal and benthic species. The dominant order was the Gobiiformes, including 23 species (39.7% of all species). The dominant taxa, in terms of relative abundance and frequency of occurrence, consisted of commercially important fishes, such as Setipinna tenuifilis (Valenciennes, 1848) (Engraulidae), Epinephelus akaara (Temminck and Schlegel, 1842) (Serraenidae), Collichthys lucidus (Richardson, 1844), Nibea albiflora (Richardson, 1846) (Sciaenidae), Acanthopagrus schlegelii (Bleeker, 1854), and Pagrus major (Temminck and Schlegel, 1843) (Sparidae), accounting for 78.9% of the horizontal tow samples. Low-valued and small-sized fishes, such as Stolephorus commersonnii Lacepède, 1803 (Engraulidae), Solea ovata Richardson, 1846 (Soleidae), Nuchequula nuchalis (Temminck and Schlegel, 1845), and Photopectoralis bindus (Valenciennes, 1835) (Leiognathidae), were also dominant species, accounting for 11.4% of the horizontal tow samples. The ichthyoplankton assemblage was categorized into five different temporal assemblages based on the cluster and nonmetric multidimensional scaling analysis, namely, April, May, June, July, and August−September (ANOSIM, Global R = 0.656, p < 0.01) with the highest density and richness of ichthyoplankton occurred in May. The spatial distribution pattern showed that the high density (ind./m 3 ) of ichthyoplankton occurred mainly in S12–S25 in Guanjingyang and along the Dongchong Peninsula coastline into Dongwuyang, while low density occurred mainly in S01–S11 in the northwest waters of Sandu Island (ANOVA, F = 8.270, p < 0.05). Temperature, salinity, and chlorophyll a were key factors structuring the ichthyoplankton assemblages in Sansha Bay. In addition, this study revealed the changes of the ichthyoplankton composition, density, and spatial distribution in Sansha Bay over the past three decades.

A Systematic Study on Berthing Capacity Assessment of Sanya Yazhou Fishing Port by Typhoon Prediction Model - Hongli Ge; Zhenlu Wang; Bingchen Liang; Zhaozi Zhang; Zhiduo Yan; Ziwang Li (Journal of Marine Science and Engineering, 2021)
This paper sheds light on the effect of combination modes on the evaluation of berthing capacity for Sanya Yazhou Fishing Port (SYFP) under hypothetical typhoon conditions. By statistically analysing the maximum probability of moving speeds and directions of historical typhoons passing through the fishing port, the representative typhoon path was determined with the nonparametric regression method. The designed typhoon wind fields of levels 12–17 were generated based on Holland’s parametric wind model. Then, the MIKE 21 BW model was used to obtain the high-precision wave distribution in the fishing port. The boundary conditions (significant wave height and peak period) of the MIKE 21 BW model were calculated by combining the MIKE 21 SW model with the designed typhoon wind fields. In SYFP, ships usually adopt the modes of multi-ship side-by-side and single anchor mooring during typhoons. In fair weather, approximately 158 vessels can be berthed if they are all large ones, while approximately 735 vessels can be moored if they are all small ones. However, with an increase in typhoon levels, the anchoring area for small vessels decreases. From the perspective of wave distribution in the fishing port, the number of large vessels moored was hardly affected by typhoons. This can be attributed to the breakwater, which significantly decreases the large wave height in the fishing port. Finally, a study on the framework of a method for hazard assessment of berthing capacity in the coming typhoon-driven storm waves was set up.

Assessment of river ecosystem health in Tianjin City, China: index of ecological integrity and water comprehensive pollution approach - Yan Wang; Shang Zhao; Mingdong Sun; Xubo Lv; Wenqian Cai; Xiangqin Xu; Hongxiang Ge; Kun Lei (Frontiers of Earth Science, 2021)

Characteristics of migration and speciation of trace elements during co-processing of antibiotic residues in a circulating fluidized bed - Haiping Xiao; Jinlin Ge; Xinyao Li; Dahai Yan; Zhong Liu (Environmental Science and Pollution Research, 2021)

Acrolein Induces Systemic Coagulopathy via Autophagy-dependent Secretion of von Willebrand Factor in Mice after Traumatic Brain Injury - Wenxing Cui; Xun Wu; Dayun Feng; Jianing Luo; Yingwu Shi; Wei Guo; Haixiao Liu; Qiang Wang; Liang Wang; Shunnan Ge; Yan Qu (Neuroscience Bulletin, 2021)
Traumatic brain injury (TBI)-induced coagulopathy has increasingly been recognized as a significant risk factor for poor outcomes, but the pathogenesis remains poorly understood. In this study, we aimed to investigate the causal role of acrolein, a typical lipid peroxidation product, in TBI-induced coagulopathy, and further explore the underlying molecular mechanisms. We found that the level of plasma acrolein in TBI patients suffering from coagulopathy was higher than that in those without coagulopathy. Using a controlled cortical impact mouse model, we demonstrated that the acrolein scavenger phenelzine prevented TBI-induced coagulopathy and recombinant ADAMTS-13 prevented acrolein-induced coagulopathy by cleaving von Willebrand factor (VWF). Our results showed that acrolein may contribute to an early hypercoagulable state after TBI by regulating VWF secretion. mRNA sequencing (mRNA-seq) and transcriptome analysis indicated that acrolein over-activated autophagy, and subsequent experiments revealed that acrolein activated autophagy partly by regulating the Akt/mTOR pathway. In addition, we demonstrated that acrolein was produced in the perilesional cortex, affected endothelial cell integrity, and disrupted the blood-brain barrier. In conclusion, in this study we uncovered a novel pro-coagulant effect of acrolein that may contribute to TBI-induced coagulopathy and vascular leakage, providing an alternative therapeutic target.

Sporadic hand, foot, and mouth disease cases associated with non-C4 enterovirus 71 strains in Xiamen, China, from 2009 to 2018 - Mengyuan Chen; Shuizhen He; Qiang Yan; Jianmei Zhang; Caiyu Li; Xiaosong Su; Shiyin Zhang; Tingdong Li; Shengxiang Ge; Min Chen; Jun Zhang; Ningshao Xia (Archives of Virology, 2021)

Dexmedetomidine alleviates cardiomyocyte apoptosis and cardiac dysfunction may be associated with inhibition of RhoA/ROCK pathway in mice with myocardial infarction - Tao Sun; Qian Gong; Ying Wu; Zhiming Shen; Yan Zhang; Shenglin Ge; Jing-Si Duan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Mechanism of Low Phosphorus Inducing the Main Root Lengthening of Rice - Yan Ding; Zegang Wang; Shuangrong Mo; Jing Liu; Yuan Xing; Yuanping Wang; Cailin Ge; Yulong Wang (Journal of Plant Growth Regulation, 2021)

Precise Control and Experimental Evaluation of a Novel Endoscopic Suturing Device for Large Perforations - Liaoyuan Ai; Chengli Song; Shuchen Ge; Shiju Yan; Lin Mao; Alfred Cuschieri (Journal of Medical and Biological Engineering, 2021)

Altered structural and functional connectivity in CSF1R-related leukoencephalopathy - Fei-Xia Zhan; Ze-Yu Zhu; Qing Liu; Hai-Yan Zhou; Xing-Hua Luan; Xiao-Jun Huang; Xiao-Li Liu; Wo-Tu Tian; Shi-Ge Wang; Xiao-Xuan Song; Guang Chen; Ming-Liang Zhao; et al. (Brain Imaging and Behavior, 2021)

Ecological thresholds of phytoplankton community across environmental gradients in the harmful algal blooms-frequently-occurring, subtropical coastal waters, East China Sea - Ran Ye; Chunying Ge; Qiong Wang; Qing Xu; Guofeng Xu; Yongkang Yan; Mingli Qin; Yanhong Cai; Yuejun Fei (Acta Oceanologica Sinica, 2021)

Functional redundancy and specific taxa modulate the contribution of prokaryotic diversity and composition to multifunctionality - Yan Li; Yuan Ge; Jichen Wang; Congcong Shen; Jianlei Wang; Yong‐Jun Liu (Molecular Ecology, 2021)
Observational and experimental evidence has revealed the functional importance of microbial diversity. However, the effects of microbial diversity loss on ecosystem functions are not consistent across studies, which are probably tempered by microbial functional redundancy, specific taxa and functions evaluated. Here we conducted diversity manipulation experiments in two independent soils with distinct prokaryotic communities, and investigated how the initial community traits (e.g., distinct functional redundancy and taxonomic composition) modulate the contribution of prokaryotic diversity loss and composition shift to eight ecosystem functions related to soil nutrient cycling. We found that diversity loss impaired three functions (potential nitrification rate, N 2 ‐fixation activity and phosphatase) and multifunctionality only in the communities with low functional redundancy, but all examined functions were unaffected in the communities with high functional redundancy. All significantly affected functions belonged to specialized functions, while the broad function (soil basal respiration) was unaffected. Moreover, prokaryotic composition explained more functional variation than diversity, which was ascribed to the crucial role of specific taxa that influence particular functions. Taken together, this study provides empirical evidence for identifying the mechanism underlying the ecosystem response to changes in microbial community, with implications for improving the prediction of ecosystem process models and managing microbial communities to promote ecosystem services.

Mitogen-activated protein kinase action in plant response to high-temperature stress: a mini review - Shuangrong Mo; Ying Qian; Wenjuan Zhang; Lu Qian; Yan Wang; Ge Cailin; Haidong Ding (Protoplasma, 2021)

Projections from D2 Neurons in Different Subregions of Nucleus Accumbens Shell to Ventral Pallidum Play Distinct Roles in Reward and Aversion - Yun Yao; Ge Gao; Kai Liu; Xin Shi; Mingxiu Cheng; Yan Xiong; Sen Song (Neuroscience Bulletin, 2021)

Divergent responses in morphology and life history to an Asplanchna kairomone between attached and free-swimming Brachionus dorcas (Rotifera) - Shan Jiang; Yan Bai; Fan Sun; Le-Le Ge; Yi-Long Xi (Hydrobiologia, 2021)

Efficient photocatalytic degradation of volatile organic compounds over carbon quantum dots decorated Bi2WO6 under visible light - Yangqing Liu; Changjun Zhu; Jingwen Sun; Yan Ge; Fujiao Song; Guanzhong Wang; Qi Xu (Environmental Science and Pollution Research, 2021)

Influences of pika and simulated grazing disturbances on bare patches of alpine meadow in the Yellow River Source Zone - Jie-xia Li; Xi-lai Li; Jay Gao; Yan Shi; Ge-liang Ma; Ka-zhao-cai-rang (Journal of Mountain Science, 2021)

Geometric model for toppling-prone deformation of layered reverse-dip slope - Liangfu Xie; Ying Ge; Jiaqi Zhang; Shunli Tan; Bo Wang; Echuan Yan; Yongjun Qin; Jianhu Wang; Chen Shi; Guangming Yu (Natural Hazards, 2021)

Molecular cloning and functional characterization of the hypoxia-inducible factor-1α in bighead carp (Aristichthys nobilis) - Yan Lin; Ling-Hong Miao; Bo Liu; Bing-Wen Xi; Liang-Kun Pan; Xian-Ping Ge (Fish Physiology and Biochemistry, 2021)

Hypoxic re-exposure retains hematological but not performance adaptations post-altitude training - Bing Yan; Xiaochuan Ge; Jiabei Yu; Yang Hu; Olivier Girard (European Journal of Applied Physiology, 2021)

Middle–late permian I-type granitoids from the Diaobingshan region in the northern margin of the North China Craton: insight into southward subduction of the Paleo–Asian Ocean - Yan Jing; Zheng Ji; Wen-Chun Ge; Yu Dong; Hao Yang; Jun-Hui Bi (International Geology Review, 2021)

Mercury Bioaccumulation in Freshwater Snails as Influenced by Soil Composition - Ge Zhang; Deliang Yin; Tianrong He; Yiyuan Xu; Shu Ran; Xian Zhou; Xiang Tian; Yan Wang (Bulletin of Environmental Contamination and Toxicology, 2021)

Factors associated with a SARS-CoV-2 recurrence after hospital discharge among patients with COVID-19: systematic review and meta-analysis - Meng-qi Yao; Qiu-xian Zheng; Jia Xu; Jing-wen Deng; Tian-tian Ge; Hai-bo Zhou; Feng-tian Wu; Xin-yu Gu; Qin Yang; Yan-li Ren; Gang Wang; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2020)

Nuclear Factor-κB Pathway Mediates the Molecular Pathogenesis of LMNA-Related Muscular Dystrophies - Yanbin Fan; Dandan Tan; Xu Zhang; Danyu Song; Xingzhi Chang; Shuang Wang; Hui Yan; Lin Ge; Haipo Yang; Carsten Bönnemann; Jingying Liu; Suxia Wang; et al. (Biochemical Genetics, 2020)

Bearing performance of offshore bucket foundation with internal cruciform skirt under combined loading - Zhong Xiao; Ying Liu; Borui Ge; Dengfeng Fu; Zengfeng Zhou; Yue Yan (Marine Georesources & Geotechnology, 2020)

Populeuphrines A and B, two new cembrane diterpenoids from the resins of Populus euphratica - Kai-Xin Liu; Da-Peng Qin; Yan-Xia Zhu; Shao-Xiang Wang; Ya-Bin Jiao; Peng-Ling Ge; Yong-Xian Cheng (Natural Product Research, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

The role of Th17 cells in psoriasis - Binbin Li; Liangliang Huang; Peng Lv; Xiang Li; Ge Liu; Yan Chen; Ziyu Wang; Xiaoxian Qian; Yixiao Shen; Yunman Li; Weirong Fang (Immunologic Research, 2020)

Temperature variations evidenced by records on the latest spring snowing dates in Hangzhou of eastern China during 1131-1270AD - Haolong Liu; Junhu Dai; Junhui Yan; Fanneng He; Quansheng Ge; Chongxing Mu (Journal of Geographical Sciences, 2020)

Prevalence of Autism Spectrum Disorder in China: A Nationwide Multi-center Population-based Study Among Children Aged 6 to 12 Years - Hao Zhou; Xiu Xu; Weili Yan; Xiaobing Zou; Lijie Wu; Xuerong Luo; Tingyu Li; Yi Huang; Hongyan Guan; Xiang Chen; Meng Mao; Kun Xia; et al. (Neuroscience Bulletin, 2020)

Feature Selection for Microarray Data Classification Using Hybrid Information Gain and a Modified Binary Krill Herd Algorithm - Ge Zhang; Jincui Hou; Jianlin Wang; Chaokun Yan; Junwei Luo (Interdisciplinary Sciences: Computational Life Sciences, 2020)

Phosphorus supply via a fed-batch strategy improves lipid heterotrophic production of Chlorella regularis - Liang Fu; Ge Yan; Yunbao Li; Qingcheng Li; Dandan Zhou (Environmental Science and Pollution Research, 2020)

Negative effects of rare earth oxide nanoparticles of La2O3, Nd2O3, and Gd2O3 on the ammonia-oxidizing microorganisms - Yan Yue; Lin Qi; Yan Li; Jichen Wang; Congcong Shen; Yuan Ge (Journal of Soils and Sediments, 2020)

Shelf-life Prediction of Chilled Penaeus vannamei Using Grey Relational Analysis and Support Vector Regression - Xingxing Huang; Ming Chen; Wenjuan Wang; Yan Ge; Jing Xie (Journal of Aquatic Food Product Technology, 2020)

The characteristics of oestrone mobility in water and soil by the addition of Ca-biochar and Fe–Mn-biochar derived from Litchi chinensis Sonn. - Huan-yu Tao; Hui Ge; Jianghong Shi; Xiaowei Liu; Wei Guo; Mengtao Zhang; Yaobin Meng; Xiao-yan Li (Environmental Geochemistry and Health, 2020)

Detection, genetic, and codon usage bias analyses of the VP2 gene of mink bocavirus - Weizhi Xin; Yuqi Liu; Yan Yang; Tianzhi Sun; Lingdi Niu; Junwei Ge (Virus Genes, 2020)

Possible aerosol transmission of COVID-19 and special precautions in dentistry - Zi-yu Ge; Lu-ming Yang; Jia-jia Xia; Xiao-hui Fu; Yan-zhen Zhang (Journal of Zhejiang University-SCIENCE B, 2020)

Leukocyte immunoglobulin-like receptor B4 protects against cardiac hypertrophy via SHP-2-dependent inhibition of the NF-κB pathway - Heng Zhou; Ning Li; Yuan Yuan; Ya-Ge Jin; Qingqing Wu; Ling Yan; Zhou-Yan Bian; Wei Deng; Di-Fei Shen; Hongliang Li; Qi-Zhu Tang (Journal of Molecular Medicine, 2020)

The Complete Genome of Emcibacter congregatus ZYLT, a Marine Bacterium Encoding a CRISPR-Cas 9 Immune System - Zhe Zhao; Rui-an Zhang; Ge-yi Fu; Ran Zhang; Yan-fang Nie; Cong Sun; Min Wu (Current Microbiology, 2020)

Illumina MiSeq sequencing and network analysis the distribution and co-occurrence of bacterioplankton in Danjiangkou Reservoir, China - Zhao-Jin Chen; Ge Xu; Chuan-Yu Ding; Bao-Hai Zheng; Yan Chen; Hui Han; Yu-Ying Li; Jian-Wei Shi; Lan-Qun Hu (Archives of Microbiology, 2020)

Microbial, Physical, and Chemical Changes in Galveston Bay Following an Extreme Flooding Event, Hurricane Harvey - Jamie L. Steichen; Jessica M. Labonté; Rachel Windham; David Hala; Karl Kaiser; Samantha Setta; Patricia C. Faulkner; Hernando Bacosa; Ge Yan; Manoj Kamalanathan; Antonietta Quigg (Frontiers in Marine Science, 2020)

Hurricanes Accelerate Dissolved Organic Carbon Cycling in Coastal Ecosystems - Ge Yan; Jessica M. Labonté; Antonietta Quigg; Karl Kaiser (Frontiers in Marine Science, 2020)

Pore morphology and fractal dimension of ash deposited in catalyst diesel particulate filter - Haohao Wang; Jianwei Tan; Yunshan Ge; Jiachen Li; Xindi Yan; Chunjie Wang; Liqun Lv; Dan Tan; Weidong Tian; Yalin Wang; Lijun Hao (Environmental Science and Pollution Research, 2020)

Interannual Variability and Scenarios Projection of Sea Ice in Bohai Sea Part I: Variation Characteristics and Interannual Hindcast - Yan Jiao; Fei Huang; Qingrong Liu; Ge Li; Yaru Li; Qingxi Yu; Yiding Zhao (Journal of Ocean University of China, 2020)

Impact of sea ice decline in the Arctic Ocean on the number of extreme low‐temperature days over China - Feifan Ge; Tao Yan; Lu Zhou; Yuelin Jiang; Wei Li; Yufen Fan; Yishu Wang; Kebiao Mao; Wenge Wu (International Journal of Climatology, 2020)
The variation in the number of extreme low‐temperature days (NELD) during winter over China is examined. The NELD mainly has a significant decreasing trend across China. The leading NELD empirical orthogonal function (EOF) mode also shows consistent change characteristics over China, and a Mann–Kendall (MK) test of its time coefficients indicates that the NELD abruptly changed in approximately 1980. The impact of sea ice concentrations in the Arctic Ocean on the NELD is investigated. Sea ice concentration declines in the Barents Sea and the sea east of Greenland have significant negative effects on the NELD. Sea surface temperatures in these regions are negatively correlated with the NELD. The study analyses the influence mechanism by researching the composite atmosphere variable anomalies between years with below‐normal NELD and those with above‐normal NELD.

Scorpion Venom Heat-Resistant Peptide is Neuroprotective against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2020)

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

Assembly of root-associated microbial community of typical rice cultivars in different soil types - Yan Xu; Yi Ge; Jianxiao Song; Christopher Rensing (Biology and Fertility of Soils, 2020)

Effects of different 2A peptides on transgene expression mediated by tricistronic vectors in transfected CHO cells - Yan-mei Li; Meng Wang; Tian-yun Wang; Yong-ge Wei; Xiao Guo; Chun-liu Mi; Chun-peng Zhao; Xiang-xiang Cao; Yuan-yuan Dou (Molecular Biology Reports, 2020)

Treatment and recurrence on re-treatment tuberculosis patients: a randomized clinical trial and 7-year perspective cohort study in China - Jian Du; Le Zhang; Yan Ma; X.-Y. Chen; Q.-P. Ge; X.-Z. Tian; Weiwei Gao; Zhongwei Jia (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Antioxidative and Probiotic Activities of Lactic Acid Bacteria Isolated from Traditional Artisanal Milk Cheese from Northeast China - Yunjia Shi; Xingyang Cui; Shanshan Gu; Xin Yan; Rui Li; Shuang Xia; Hongyan Chen; Junwei Ge (Probiotics and Antimicrobial Proteins, 2019)

Relationship between phenotype and genotype of 102 Chinese newborns with Prader–Willi syndrome - Meng-Meng Ge; Yan-Yan Gao; Bing-Bing Wu; Kai Yan; Qian Qin; HuiJun Wang; WenHao Zhou; Lin Yang (Molecular Biology Reports, 2019)

Comprehensive genetic diagnosis of patients with Duchenne/Becker muscular dystrophy (DMD/BMD) and pathogenicity analysis of splice site variants in the DMD gene - Yan-mei Yang; Kai Yan; Bei Liu; Min Chen; Li-ya Wang; Ying-zhi Huang; Ye-qing Qian; Yi-xi Sun; Hong-ge Li; Min-yue Dong (Journal of Zhejiang University-SCIENCE B, 2019)

Arsenic migration during co-processing of secondary residues from ammonium paratungstate production in cement kiln - Haiping Xiao; Jinlin Ge; Yu Chen; Zheng Peng; Dahai Yan; Li Li; Kare Helge Karstensen; Christian J. Engelsen; Qifei Huang (Environmental Science and Pollution Research, 2019)

Molecular characterization of new emerging sub-genotype VIIh Newcastle disease viruses in China - Hualei Liu; Jingjing Wang; Shengqiang Ge; Yan Lv; Yin Li; Dongxia Zheng; Yunling Zhao; David Castellan; Zhiliang Wang (Virus Genes, 2019)

Overexpression of BcbZIP134 negatively regulates the biosynthesis of saikosaponins - Jiao Xu; Su-Rui Wu; Yan-Hong Xu; Zhan-Yu Ge; Chun Sui; Jian-He Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

OsRhoGAP2 promoter drives inflorescence-preferential expression and confers responses to abiotic stresses in transgenic Arabidopsis - Junjun Huang; Xintian Yan; Jiajia Li; Jia Shi; Jingjing Peng; Jingyao Du; Huiwen Ge; Meina Wang; Wenjing An; Kaijie Wang; Huahua Wang; Weihong Liang (Acta Physiologiae Plantarum, 2019)

Long-term observation of cyanobacteria blooms using multi-source satellite images: a case study on a cloudy and rainy lake - Meng Mu; Chuanqing Wu; Yunmei Li; Heng Lyu; Shengzhong Fang; Xiang Yan; Ge Liu; Zhubin Zheng; Chenggong Du; Shun Bi (Environmental Science and Pollution Research, 2019)

Available soil nutrients and water content affect leaf nutrient concentrations and stoichiometry at different ages of Leucaena leucocephala forests in dry-hot valley - Yongming Lin; Aimin Chen; Siwei Yan; Loretta Rafay; Kun Du; Daojie Wang; Yonggang Ge; Jian Li (Journal of Soils and Sediments, 2019)

Ectomycorrhizal fungi inoculation alleviates simulated acid rain effects on soil ammonia oxidizers and denitrifiers in Masson pine forest - Yan Li; Zhan Chen; Ji‐Zheng He; Qing Wang; Congcong Shen; Yuan Ge (Environmental Microbiology, 2019)
Summary Acid rain can cause severe effects on soil biota and nutrient biogeochemical cycles in the forest ecosystem, but how plant‐symbiotic ectomycorrhizal fungi will modulate the effects remains unknown. Here, we conducted a full factorial field experiment in a Masson pine forest by simultaneously controlling the acidity of the simulated rain (pH 5.6 vs. pH 3.5) and the ectomycorrhizal fungi Pisolithus tinctorius inoculation (non‐inoculation vs. inoculation), to investigate the effects on ammonia oxidizers and denitrifiers. After 10 months, compared with the control (rain pH 5.6, and non‐inoculation), simulated acid rain (pH 3.5) reduced soil nutrient content, decreased archaeal amoA gene abundance and inhibited denitrification enzyme activity. Also, simulated acid rain altered the community compositions of all the examined functional genes (archaeal amoA , bacterial amoA , nirK , nirS and nosZ ). However, inoculation with ectomycorrhizal fungi under acid rain stress recovered soil nutrient content, archaeal amoA gene abundance and denitrification enzyme activity to levels comparable to the control, suggesting that ectomycorrhizal fungi inoculation ameliorates simulated acid rain effects. Taken together, ectomycorrhizal fungi inoculation – potentially through improving soil substrate availability – could alleviate the deleterious effects of acid rain on nitrogen cycling microbes in forest soils.

Chemical constituents from Alisma plantago - aquatica subsp . orientale (Sam.) Sam and their anti-inflammatory and antioxidant activities - Xin-Yu Zhao; Gang Wang; Yan Wang; Xiang-Ge Tian; Jian-Chao Zhao; Xiao-Kui Huo; Cheng-Peng Sun; Lei Feng; Jing Ning; Chao Wang; Bao-Jing Zhang; Xun Wang (Natural Product Research, 2018)

Antibacterial and Antibiofilm Activity of Lactic Acid Bacteria Isolated from Traditional Artisanal Milk Cheese from Northeast China Against Enteropathogenic Bacteria - Xingyang Cui; Yunjia Shi; Shanshan Gu; Xin Yan; Hongyan Chen; Junwei Ge (Probiotics and Antimicrobial Proteins, 2018)

Flavobacterium zaozhuangense sp. nov., a new member of the family Flavobacteriaceae, isolated from metolachlor-contaminated soil - Qing Chen; Hong-Mei Wang; Wen Zhuang; Zhong-Guan Sun; Jing Chen; Yan Ge; Ji-guo Qiu; Jian He (Antonie van Leeuwenhoek, 2018)

Late Cretaceous basalts and rhyolites from Shimaoshan Group in eastern Fujian Province, SE China: age, petrogenesis, and tectonic implications - Xi-Yao Li; San-Zhong Li; Yan-Hui Suo; Li-Ming Dai; Ling-Li Guo; Feng-Jian Ge; Pei-Jun Lin (International Geology Review, 2018)

Arsenic removal from water by metal-organic framework MIL-88A microrods - Hao Wu; Meng-Dan Ma; Wei-Zhuo Gai; Hongxun Yang; Jian-Ge Zhou; Zhenxiang Cheng; Pingguang Xu; Zhen-Yan Deng (Environmental Science and Pollution Research, 2018)

Protective Effect of Agaricus blazei Polysaccharide Against Cadmium-Induced Damage on the Testis of Chicken - Yangyang Song; Ruili Zhang; Hongmei Wang; Yan Yan; Ge Ming (Biological Trace Element Research, 2018)

Improvements on the particle-filter-based GLONASS phase inter-frequency bias estimation approach - Yumiao Tian; Maorong Ge; Frank Neitzel; Linguo Yuan; Dingfa Huang; Letao Zhou; Haoming Yan (GPS Solutions, 2018)

Homoeolog Expression Is Modulated Differently by Different Subgenomes in Brassica napus Hybrids and Allotetraploids - Dawei Zhang; Qi Pan; Chen Tan; Lili Liu; Xianhong Ge; Zaiyun Li; Mingli Yan (Plant Molecular Biology Reporter, 2018)

The effects of phylogeny, life-history traits and altitude on the carbon, nitrogen, and phosphorus contents of seeds across 203 species from an alpine meadow - Hai-Yan Bu; Peng Jia; Wei Qi; Kun Liu; Dang-Hui Xu; Wen-Jing Ge; Xue-Jing Wang (Plant Ecology, 2018)

Effect of nitrite exposure on oxygen-carrying capacity and gene expression of NF-κB/HIF-1α pathway in gill of bighead carp (Aristichthys nobilis) - Yan Lin; Ling-Hong Miao; Wu-Xiao Zhang; Wen-Jing Pan; Hua-Liang Liang; Xian-Ping Ge; Yan-Shun Xu; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou; Si-Lei Xia (Aquaculture International, 2018)

A new DDA model for kinematic analyses of rockslides on complex 3-D terrain - Hong Zhang; Shu-guang Liu; Wei Wang; Lu Zheng; Ying-bin Zhang; Yan-qiang Wu; Zheng Han; Yan-ge Li; Guang-qi Chen (Bulletin of Engineering Geology and the Environment, 2018)

Two new protostane-type triterpenoids from Alisma orientalis - Xiu-Lan Xin; Xin-Yu Zhao; Xiao-Kui Huo; Xiang-Ge Tian; Cheng-Peng Sun; Hou-Li Zhang; Yan Tian; Yong Liu; Xun Wang (Natural Product Research, 2018)

Native and non-native halophytes resiliency against sea-level rise and saltwater intrusion - Lian Xue; Xiuzhen Li; Zhongzheng Yan; Qian Zhang; Wenhui Ding; Xing Huang; Bo Tian; Zhenming Ge; Qiuxiao Yin (Hydrobiologia, 2018)

Monoclonal antibody-based serological assays for detection of Potato virus S in potato plants - Ge Song; Jia-yu Wu; Yan Xie; Yong Liu; Ya-juan Qian; Xue-ping Zhou; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2017)

Bioinformatic prediction and analysis of glucolipid metabolic regulation by miR-34a in Megalobrama amblycephala - Ling-Hong Miao; Wen-Jing Pan; Yan Lin; Xian-Ping Ge; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou (Genes & Genomics, 2017)

Promotional effect of rare earth-doped manganese oxides supported on activated semi-coke for selective catalytic reduction of NO with NH3 - Zheng Yan; Yanxin Qu; Lili Liu; Xinlei Ge; Jiayao Yang; Lihong Wei; Tianhua Yang; Xidong Wang (Environmental Science and Pollution Research, 2017)

The effect of emodin on Staphylococcus aureus strains in planktonic form and biofilm formation in vitro - Xin Yan; Shanshan Gu; Yunjia Shi; Xingyang Cui; Shanshan Wen; Junwei Ge (Archives of Microbiology, 2017)

Influence of Micropatterned Silk Fibroin Films on Human Umbilical Endothelial Cell Behaviors - Danyan Wang; Yan Sun; Xili Ding; Ge Peng; Tongqiang Zou; Haifeng Liu; Yubo Fan (Journal of Medical and Biological Engineering, 2017)

Adiponectin Suppresses T Helper 17 Cell Differentiation and Limits Autoimmune CNS Inflammation via the SIRT1/PPARγ/RORγt Pathway - Kai Zhang; Yawei Guo; Zhenzhen Ge; Zhihui Zhang; Yurong Da; Wen Li; Zimu Zhang; Zhenyi Xue; Yan Li; Yinghui Ren; Long Jia; Koon-Ho Chan; et al. (Molecular Neurobiology, 2017)

Association Between Serum Zinc Levels and the Risk of Parkinson’s Disease: a Meta-Analysis - Hualei Sun; Xinxin Liu; Huina Ge; Teng Wang; Yan Wang; Wenjie Li (Biological Trace Element Research, 2017)

Evaluation on the Production of Food Crop Straw in China from 2006 to 2014 - Hui Li; Yan Cao; Xingming Wang; Xin Ge; Buqing Li; Chengqian Jin (BioEnergy Research, 2017)

Capacities and failure modes of suction bucket foundation with internal bulkheads - Zhong Xiao; Borui Ge; Yan Wang (Journal of Ocean University of China, 2017)

Deletion of mammalian sterile 20-like kinase 1 attenuates neuronal loss and improves locomotor function in a mouse model of spinal cord trauma - Pan-feng Wang; Da-yuan Xu; Yuntong Zhang; Xiao-bin Liu; Yan Xia; Pan-yu Zhou; Qing-ge Fu; Shuo-gui Xu (Molecular and Cellular Biochemistry, 2017)

The emergence of the hyperinvasive vine, Mikania micrantha (Asteraceae), via admixture and founder events inferred from population transcriptomics - Ming Yang; Ziwen He; Yelin Huang; Lu Lu; Yubin Yan; Lan Hong; Hao Shen; Ying Liu; Qiang Guo; Lu Jiang; Yanwu Zhang; Anthony J. Greenberg; et al. (Molecular Ecology, 2017)
Biological invasions that involve well‐documented rapid adaptations to new environments provide unequalled opportunities for testing evolutionary hypotheses. Mikania micrantha Kunth (Asteraceae), a perennial herbaceous vine native to tropical Central and South America, successfully invaded tropical Asia in the early 20th century. It is regarded as one of the most aggressive weeds in the world. To elucidate the molecular and evolutionary processes underlying this invasion, we extensively sampled this weed throughout its invaded range in South‐East and South Asia and surveyed its genetic structure using variants detected from population transcriptomics. Clustering results suggest that more than one source population contributed to this invasion. Computer simulations using genomewide genetic variation support a scenario of admixture and founder events during invasion. The genes differentially expressed between native and invasive populations were found to be involved in oxidative and high light intensity stress responses, pointing to a possible ecological mechanism of adaptation. Our results provide a foundation for further detailed mechanistic and population studies of this ecologically and economically important invasion. This line of research promises to provide new mitigation strategies for invasive species as well as insights into mechanisms of adaptation.

On the coupling between precipitation and potential evapotranspiration: contributions to decadal drought anomalies in the Southwest China - Shanlei Sun; Haishan Chen; Weimin Ju; Guojie Wang; Ge Sun; Jin Huang; Hedi Ma; Chujie Gao; Wenjian Hua; Guixia Yan (Climate Dynamics, 2017)

Flavonol glycosides from the leaves of Elaeagnus pungens - Ying-ying Shang; Qin Qin; Meng-Shun Li; Hai-yan Xu; Yue-bin Ge (Natural Product Research, 2017)

Neutrophil-To-Lymphocyte Ratio Predicts 3-Month Outcome of Acute Ischemic Stroke - Sen Qun; Yan Tang; Jing Sun; Zhaoxia Liu; Juncang Wu; Ji Zhang; Jidong Guo; Zhiqiang Xu; Dan Zhang; Zhengxu Chen; Fuyong Hu; Xingshun Xu; et al. (Neurotoxicity Research, 2017)

Modifying the Autism Spectrum Rating Scale (6–18 years) to a Chinese Context: An Exploratory Factor Analysis - Hao Zhou; Lili Zhang; Xuerong Luo; Lijie Wu; Xiaobing Zou; Kun Xia; Yimin Wang; Xiu Xu; Xiaoling Ge; Yong-Hui Jiang; Eric Fombonne; Weili Yan; et al. (Neuroscience Bulletin, 2017)

Chinese Norms for the Autism Spectrum Rating Scale - Hao Zhou; Lili Zhang; Xiaobing Zou; Xuerong Luo; Kun Xia; Lijie Wu; Yimin Wang; Xiu Xu; Xiaoling Ge; Yong-Hui Jiang; Eric Fombonne; Weili Yan; et al. (Neuroscience Bulletin, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

The complete chloroplast genome of a rare candelabra primrose Primula stenodonta (Primulaceae) - Cai-Yun Zhang; Tong-Jian Liu; Hai-Fei Yan; Xue-Jun Ge; Gang Hao (Conservation Genetics Resources, 2017)

Characterization of the whole chloroplast genome of an endangered species Primula kwangtungensis (Primulaceae) - Cai-Yun Zhang; Tong-Jian Liu; Yuan Xu; Hai-Fei Yan; Gang Hao; Xue-Jun Ge (Conservation Genetics Resources, 2017)

Antimicrobial mechanism of the major active essential oil compounds and their structure–activity relationship - Xian Hui; Ge Yan; Fang-Lin Tian; Heng Li; Wen-Yun Gao (Medicinal Chemistry Research, 2017)

Fluorescent Detection of Phosphate in Aqueous Solution Based on Near Infrared Emission Ag2S QDs/Metal − Organic Shell Composite - Dan Yan; Yu He; Yili Ge; Gongwu Song (Journal of Fluorescence, 2017)

Trace projection transformation: a new method for measurement of debris flow surface velocity fields - Yan Yan; Peng Cui; Xiaojun Guo; Yonggang Ge (Frontiers of Earth Science, 2016)

Distinct expression patterns of the GDP dissociation inhibitor protein gene (OsRhoGDI2) from Oryza sativa during development and abiotic stresses - Jun-jun Huang; Jing Zhang; Yu-fan Hao; Xin-tian Yan; Jia Shi; Gao-hua Wang; Jing-yao Du; Hui-wen Ge; Hua-hua Wang; Wei-hong Liang (Biologia, 2016)

The growth and reproduction performance of TALEN-mediated β-lactoglobulin-knockout bucks - Hengtao Ge; Chenchen Cui; Jun Liu; Yan Luo; Fusheng Quan; Yaping Jin; Yong Zhang (Transgenic Research, 2016)

Chain elongation analog of resveratrol as potent cancer chemoprevention agent - Yan-Fei Kang; Hai-Xia Qiao; Long-Zuo Xin; Li-Ping Ge (Journal of Physiology and Biochemistry, 2016)

Sensitive Naked Eye and Autofluorescence Detection of Cu2+ in Biological Fluids by Polyethyleneimine Microspheres - Dan Yan; Chun Deng; Yu He; Yili Ge; Gongwu Song (Journal of Fluorescence, 2016)

Three new sulphur glycosides from the seeds of Descurainia sophia - Wei-sheng Feng; Chun-Ge Li; Xiao-Ke Zheng; Ling-Ling Li; Wen-Jing Chen; Yan-Li Zhang; Yan-Gang Cao; Jian-Hong Gong; Hai-Xue Kuang (Natural Product Research, 2016)

Salidroside protects cortical neurons against glutamate-induced cytotoxicity by inhibiting autophagy - Wei-Yong Yin; Qiang Ye; Huan-Jie Huang; Nian-Ge Xia; Yan-Yan Chen; Yi Zhang; Qiu-Min Qu (Molecular and Cellular Biochemistry, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

The partitioning behavior of trace element and its distribution in the surrounding soil of a cement plant integrated utilization of hazardous wastes - Zhenzhou Yang; Yan Chen; Yongqi Sun; Lili Liu; Zuotai Zhang; Xinlei Ge (Environmental Science and Pollution Research, 2016)

Socio-economic vulnerability of the megacity of Shanghai (China) to sea-level rise and associated storm surges - Baiyang Yan; Shasha Li; Jun Wang; Zhenming Ge; Liquan Zhang (Regional Environmental Change, 2016)

Nobiletin attenuates cardiac dysfunction, oxidative stress, and inflammatory in streptozotocin: induced diabetic cardiomyopathy - Ning Zhang; Zheng Yang; Shi-Zhao Xiang; Ya-Ge Jin; Wen-Ying Wei; Zhou-Yan Bian; Wei Deng; Qi-Zhu Tang (Molecular and Cellular Biochemistry, 2016)

Detection of novel adenoviruses in fecal specimens from rodents and shrews in southern China - Xue-yan Zheng; Min Qiu; Xue-mei Ke; Wei-jie Guan; Jin-ming Li; Shu-ting Huo; Shao-wei Chen; Xue-shan Zhong; Wen Zhou; Yi-quan Xiong; Jing Ge; Qing Chen (Virus Genes, 2016)

Improved tilt-depth method for fast estimation of top and bottom depths of magnetic bodies - Yan-Guo Wang; Jin Zhang; Kun-Peng Ge; Xiao Chen; Feng-Jun Nie (Applied Geophysics, 2016)

Combined Finite-Discrete Element Method for Simulation of Hydraulic Fracturing - Chengzeng Yan; Hong Zheng; Guanhua Sun; Xiurun Ge (Rock Mechanics and Rock Engineering, 2016)

Effect of La(NO3)3 and Ce(NO3)3 on shoot induction and seedling growth of in vitro cultured anoectochilus roxburghii - Yingya Xu; Guifang Zhang; Yan Wang; Ge Guo (Journal of Plant Biology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Pretreatments with injured microenvironmental signals altered the characteristics of human umbilical cord mesenchymal stem cells - Huiling Cao; Qian Hui; Yongmin Yan; Chunbing Zhang; Xuewen Yang; Liang Ge; Wenrong Xu (Biotechnology Letters, 2016)

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

Isolation and characterization of twenty-two polymorphic microsatellite markers from Gardenia jasminoides (Rubiaceae) - YAN-QIN XU; GUO-YAN WEI; YIN ZHOU; FEI GE; GUANG-MING LUO (Journal of Genetics, 2015)

Passive-source multitaper-spectral method based low-frequency data reconstruction for active seismic sources - Pan Zhang; Li-Guo Han; Yan Zhou; Zhuo Xu; Qi-Xin Ge (Applied Geophysics, 2015)

The Effects of Levetiracetam on Cerebrospinal Fluid and Plasma NPY and GAL, and on the Components of Stress Response System, hs-CRP, and S100B Protein in Serum of Patients with Refractory Epilepsy - Wenzhen Chen; Yan Tan; Yuxing Ge; Yujuan Chen; Xueyuan Liu (Cell Biochemistry and Biophysics, 2015)

New norditerpenoid alkaloids from Aconitum vilmorinianum Komarov - Cui-Ling Chen; Wen-Hong Tan; Yan Wang; Zhi-Ge Xue; Chun-Ping Wan; Zhu-Ya Yang; Zhi-Hong Zhou; Xiao-Xia Ma (Journal of Natural Medicines, 2015)

Biotransformation of 20(S)-protopanaxatriol by Mucor racemosus and the anti-cancer activities of some products - Guangtong Chen; Hongjuan Ge; Yan Song; Jianlin Li; Xuguang Zhai; Juanjuan Wu; Xiang Ling (Biotechnology Letters, 2015)

Complete mitochondrial genome sequence for the Malayan Pangolin Manis javanica (Pholidota, Manidae) - Weiye Li; Shiping Gong; Liushuai Hua; Yan Ge; Fumin Wang; Fanghui Hou (Conservation Genetics Resources, 2015)

Tissue lipid metabolism and hepatic metabolomic profiling in response to supplementation of fermented cottonseed meal in the diets of broiler chickens - Cun-xi Nie; Wen-ju Zhang; Yong-qiang Wang; Yan-feng Liu; Wen-xia Ge; Jian-cheng Liu (Journal of Zhejiang University-SCIENCE B, 2015)

Effect of Cyclophosphamide on Expression of MMP-9 and TGF-β1 in Renal Tissue of Rats with Diabetes Mellitus - Yan Zhang; Ge Wu; Xiaozhou Hu; Jin Zhang (Cell Biochemistry and Biophysics, 2015)

Diaphorobacter ruginosibacter sp. nov., isolated from soybean root nodule, and emended description of the genus Diaphorobacter - Xiu Li Wei; Meng Sha Han; Cong Cong Xia; Shu Lan Ding; Lin Xu; Yan Bing Lin; Li Wang; Ge Hong Wei (Archives of Microbiology, 2015)

Sigma 1 receptor activation regulates brain-derived neurotrophic factor through NR2A-CaMKIV-TORC1 pathway to rescue the impairment of learning and memory induced by brain ischaemia/reperfusion - Qian Xu; Xue-Fei Ji; Tian-Yan Chi; Peng Liu; Ge Jin; Shao-Li Gu; Li-Bo Zou (Psychopharmacology, 2015)

The effect of SCF and ouabain on small intestinal motility dysfunction induced by gastric cancer peritoneal metastasis - Dan Kong; Jing Li; Baoshan Zhao; Bairong Xia; Lei Zhang; Yan He; Xiuli Wang; Lei Gao; Yufu Wang; Xiaoming Jin; Ge Lou (Clinical & Experimental Metastasis, 2015)

Microbial transformation of 20(S)-protopanaxatriol by Mucor spinosus - Xue Yang; Hongjuan Ge; Yan Song; Jianlin Li; Guangtong Chen (Biotechnology Letters, 2015)

Paleoclimate modeling in China: A review - Dabang Jiang; Ge Yu; Ping Zhao; Xing Chen; Jian Liu; Xiaodong Liu; Shaowu Wang; Zhongshi Zhang; Yongqiang Yu; Yuefeng Li; Liya Jin; Ying Xu; et al. (Advances in Atmospheric Sciences, 2015)

Characterisation of novel linear antigen epitopes on North American-type porcine reproductive and respiratory syndrome virus M protein - Qian Wang; Jiazeng Chen; Jinmei Peng; Tongqing An; Chaoliang Leng; Yan Sun; Xin Guo; Xinna Ge; Zhijun Tian; Hanchun Yang (Archives of Virology, 2014)

Association between the MMP-9−1562 C>T polymorphism and the risk of stroke: a meta-analysis - Zhen-Zhen Fan; Zhao-Ming Ge; Hong-Bin Cai; Zhi-Yan Liu; Pei Liu; Hao-Yue Wang (Molecular Biology Reports, 2014)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

Grid-Based Land-Use Composition and Configuration Optimization for Watershed Stormwater Management - Ge Zhang; Subhrajit Guhathakurta; Susannah Lee; Amy Moore; Lijiao Yan (Water Resources Management, 2014)

A field study of the relationship between sulfide-bound metals and bioaccumulation by Limnodrilus sp. in a heavily polluted river - Feng Li; Xiang-yun Zeng; Yun-jun Yu; Chang-hua Wu; Ge Mai; Wei-wei Song; Yan-mao Wen; Zhi-peng Duan; Jia-yu Yang (Environmental Monitoring and Assessment, 2014)

Sex Differences in Iron Status and Hepcidin Expression in Rats - Wei-Na Kong; Qiao-Man Niu; Lan Ge; Nan Zhang; Shao-Feng Yan; Wei-Bin Chen; Yan-Zhong Chang; Shu-E Zhao (Biological Trace Element Research, 2014)

C-type natriuretic peptide inhibiting vascular calcification might involve decreasing bone morphogenic protein 2 and osteopontin levels - Jing-Jing Chen; Jing Zhang; Yan Cai; Ye-Bo Zhou; Ge-Bo Wen; Chao-Shu Tang; Yong-Fen Qi; Zhi-Sheng Jiang (Molecular and Cellular Biochemistry, 2014)

Development of an ATI-NDVI method for estimation of soil moisture from MODIS data - Lei Lu; Ge-Ping Luo; Ji-Yan Wang (International Journal of Remote Sensing, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Isolation and Characterization of 14 Polymorphic Microsatellite Loci in the Big-Headed Turtle (Platysternon megacephalum) - Liushuai Hua; Fumin Wang; Shiping Gong; Yan Ge; Guoling Chen; Jinping Chen (Biochemical Genetics, 2014)

Molecular and biochemical characterization of Sclerotinia sclerotiorum laboratory mutants resistant to dicarboximide and phenylpyrrole fungicides - Ya-Bing Duan; Chang-Yan Ge; Ming-Guo Zhou (Journal of Pest Science, 2014)

Modeling study of regional severe hazes over mid-eastern China in January 2013 and its implications on pollution prevention and control - ZiFa Wang; Jie Li; Zhe Wang; WenYi Yang; Xiao Tang; BaoZhu Ge; PinZhong Yan; LiLi Zhu; XueShun Chen; HuanSheng Chen; Wei Wand; JianJun Li; et al. (Science China Earth Sciences, 2014)

Xanthoceraside attenuates tau hyperphosphorylation and cognitive deficits in intracerebroventricular-streptozotocin injected rats - Peng Liu; Li-Bo Zou; Li-Hua Wang; Qing Jiao; Tian-Yan Chi; Xue-Fei Ji; Ge Jin (Psychopharmacology, 2014)

Purifying synthetic high-strength wastewater by microalgae chlorella vulgaris under various light emitting diode wavelengths and intensities - Zhigang Ge; Hui Zhang; Yuejin Zhang; Cheng Yan; Yongjun Zhao (Journal of Environmental Health Science and Engineering, 2013)
The high-strength wastewater is now well known as a threat to the natural water since it is highly possible to arouse water eutrophication or algal blooms. The effects of various light emitting diode wavelengths and intensities on the microalgae biological wastewater treatment system was studied in this research. The various nutrient removals and economic efficiencies represented similar variation trends, and these variations under both high C and N loading treatments were similar too. The order for microalgae C . vulgaris reproduction in terms of dry weight and nutrient removal efficiency both were red > white > yellow > blue, under high carbon and nitrogen loading treatments, indicating that the red light was the optimum light wavelength. Furthermore, considering the optimal light intensity in terms of nutrient removal efficiency was 2500 and 2000 μmol/m 2 •s, while in terms of economic efficiency was 1000, 1500 and 2000 μmol/m 2 •s. Therefore, the optimum light intensity was found to be 2000 μmol/m 2 •s. In addition, the optimal experimental illumination time was determined as 120 h. The Chlorella vulgaris microalgae biological wastewater treatment system utilized in this research was able to purify the high-strength carbon and nitrogen wastewater effectively under optimum light wavelength and intensity.

Association between interferon gamma +874 T>A polymorphism and acute renal allograft rejection: evidence from published studies - Yu-Zheng Ge; Ran Wu; Rui-Peng Jia; Hao Liu; Peng Yu; Yan Zhao; Yu-Ming Feng (Molecular Biology Reports, 2013)

A geospatial web portal for sharing and analyzing greenhouse gas data derived from satellite remote sensing images - Hao Lin; Bailang Yu; Zuoqi Chen; Yingjie Hu; Yan Huang; Jianping Wu; Bin Wu; Rong Ge (Frontiers of Earth Science, 2013)

Fine mapping TaFLW1, a major QTL controlling flag leaf width in bread wheat (Triticum aestivum L.) - Shulin Xue; Feng Xu; Guoqiang Li; Yan Zhou; Musen Lin; Zhongxia Gao; Xiuhong Su; Xiaowu Xu; Ge Jiang; Shuang Zhang; Haiyan Jia; Zhongxin Kong; et al. (Theoretical and Applied Genetics, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Doubled haploids of novel trigenomic Brassica derived from various interspecific crosses - X. X. Geng; S. Chen; I. A. Astarini; G. J. Yan; E. Tian; J. Meng; Z. Y. Li; X. H. Ge; M. N. Nelson; A. S. Mason; A. Pradhan; W. J. Zhou; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Quantification of serum HBXAP DNA in lung cancer patients by quantitative fluorescent polymerase chain reaction - Yu-Lei Hou; Hui Chen; Ming-Jian Ge; Feng-Zeng Li; Cheng-Jun Xue; Yan-Feng Wu; Hai-Xia Luo (Molecular Biology Reports, 2013)

Combinational biosynthesis of phycocyanobilin using genetically-engineered Escherichia coli - Baosheng Ge; Yan Li; Haixiang Sun; Shuai Zhang; Peijie Hu; Song Qin; Fang Huang (Biotechnology Letters, 2013)

Time lag between carbon dioxide influx to and efflux from bare saline-alkali soil detected by the explicit partitioning and reconciling of soil CO2 flux - Xi Chen; Wen-Feng Wang; Ge-Ping Luo; Long-Hui Li; Yan Li (Stochastic Environmental Research and Risk Assessment, 2013)

The Control of Land-Use Patterns for Stormwater Management at Multiple Spatial Scales - Ge Zhang; Subhro Guhathakurta; Gang Dai; Lingying Wu; Lijiao Yan (Environmental Management, 2013)

Molecular epidemiology of hepatitis C virus among different groups of people in the province of Fujian, China - Ying Ye; Yan-sheng Yan; Ge Chen; Ping-ping Yan; Wu-xiong Zheng; Yan-qin Deng; Xiu-hui Yang; Shou-li Wu; Zhi-shan Zhang (Archives of Virology, 2013)

Seasonal migration by a large forest ungulate: a study on takin (Budorcas taxicolor) in Sichuan Province, China - Tian-Pei Guan; Bao-Ming Ge; William J. McShea; Sheng Li; Yan-Ling Song; Chad M. Stewart (European Journal of Wildlife Research, 2013)

De-novo characterization of the soft-shelled turtle Pelodiscus sinensis transcriptome using Illumina RNA-Seq technology - Wei Wang; Cai-yan Li; Chu-tian Ge; Lei Lei; You-ling Gao; Guo-ying Qian (Journal of Zhejiang University-SCIENCE B, 2013)

Is a new invasive herb emerging? Molecular confirmation and preliminary evaluation of natural hybridization between the invasive Sphagneticola trilobata (Asteraceae) and its native congener S. calendulacea in South China - Wei Wu; Ren-Chao Zhou; Guang-Yan Ni; Hao Shen; Xue-Jun Ge (Biological Invasions, 2013)

Thaxtomin A-deficient endophytic Streptomyces sp. enhances plant disease resistance to pathogenic Streptomyces scabies - Lan Lin; Hui Ming Ge; Tong Yan; Yan Hua Qin; Ren Xiang Tan (Planta, 2012)

Molecular characterization and dynamic expression patterns of two types of γ-gliadin genes from Aegilops and Triticum species - Shunli Wang; Xixi Shen; Pei Ge; Jie Li; Saminathan Subburaj; Xiaohui Li; F. J. Zeller; S. L. K. Hsam; Yueming Yan (Theoretical and Applied Genetics, 2012)

Synthesis, Characterization, Optical Properties and Theoretical Studies of Novel Substituted Imidazo[1,5-a]pyridinyl 1,3,4-Oxadiazole Derivatives - Yan-Qing Ge; Teng Wang; Gui Yun Duan; Li Hua Dong; Xiao Qun Cao; Jian Wu Wang (Journal of Fluorescence, 2012)

Wolbachia Strengthens Cardinium-Induced Cytoplasmic Incompatibility in the Spider Mite Tetranychus piercei McGregor - Lu-Yu Zhu; Kai-Jun Zhang; Yan-Kai Zhang; Cheng Ge; Tetsuo Gotoh; Xiao-Yue Hong (Current Microbiology, 2012)

Influence of UGT genetic polymorphism on the interindividual variability in mitiglinide pharmacokinetic in Chinese - Jing-feng Xu; Zhan-qing Wang; Chen-xia Yan; Qian Xu; Lin Xu; Gang-tao Zhao; Yong-ge Yang (Medicinal Chemistry Research, 2012)

Effects of high modes on the wind-induced response of super high-rise buildings - Ruoqiang Feng; Guirong Yan; Jinming Ge (Earthquake Engineering and Engineering Vibration, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

An efficient three-component, one-pot synthesis of 2-alkylthio-4-amino-5-cyano-6-aryl(alkyl)pyrimidines in water - Qiao-Yan Li; Ze-Mei Ge; Tie-Ming Cheng; Run-Tao Li (Molecular Diversity, 2012)

Identification and molecular characterisation of HMW glutenin subunit 1By16* in wild emmer - M. Jin; Z.-Z. Xie; P. Ge; J. Li; S.-S. Jiang; S. Subburaj; X.-H. Li; F.-J. Zeller; S.-L.-K. Hsam; Y.-M. Yan (Journal of Applied Genetics, 2012)

Effect of the calcium sensing receptor on rat bone marrow-derived mesenchymal stem cell proliferation through the ERK1/2 pathway - Zhihui Xu; Ling Yan; Yingbing Ge; Qing Zhang; Naiquan Yang; Min Zhang; Yingming Zhao; Peng Sun; Jinghong Gao; Zhengxian Tao; Zhijian Yang (Molecular Biology Reports, 2012)

PDGF-AA Mediates B104CM-Induced Oligodendrocyte Precursor Cell Differentiation of Embryonic Neural Stem Cells Through Erk, PI3K, and p38 Signaling - Jian-Guo Hu; Yan-Xia Wang; Hong-Ju Wang; Ming-Sheng Bao; Zhen-Huan Wang; Xin Ge; Feng-Chao Wang; Jian-Sheng Zhou; He-Zuo Lü (Journal of Molecular Neuroscience, 2012)

Norcantharidin, a protective therapeutic agent in renal tubulointerstitial fibrosis - Ying Li; Yan Ge; Fu You Liu; You Ming Peng; Lin Sun; Jun Li; Qiong Chen; Yan Sun; Kun Ye (Molecular and Cellular Biochemistry, 2012)

The therapeutic potential of G-CSF in pressure overload induced ventricular reconstruction and heart failure in mice - Ji Ming Li; Zhi Feng Yao; Yun Zeng Zou; Jun Bo Ge; Ai Li Guan; Jian Wu; Shou Ling Mi; Yan Yan Liang; Zhen Ma (Molecular Biology Reports, 2012)

Rapid and Sensitive Detection of Listeria monocytogenes by Loop-Mediated Isothermal Amplification - Meng-Jun Tang; Sheng Zhou; Xiao-Yan Zhang; Jun-Hua Pu; Qing-Lian Ge; Xiu-Jun Tang; Yu-Shi Gao (Current Microbiology, 2011)

Analysis of the External Pressure on Casings Induced by Salt-Gypsum Creep in Build-up Sections for Horizontal Wells - Weifeng Ge; Mian Chen; Yan Jin; Fuxiang Zhang; Yunhu Lu; Pei Yang; Jihui Ding; Hao Zeng (Rock Mechanics and Rock Engineering, 2011)

Impact of long-range transport and under-cloud scavenging on precipitation chemistry in East China - Yuhua Li; Yan Wang; Aijun Ding; Xiaohuan Liu; Jia Guo; Penghui Li; Minghu Sun; Fuling Ge; Wenxing Wang (Environmental Science and Pollution Research, 2011)

A mitochondria-localized glutamic acid-rich protein (MGARP/OSAP) is highly expressed in retina that exhibits a large area of intrinsic disorder - Shaoling Qi; Yifeng Wang; Mingxue Zhou; Yunxiao Ge; Yongbin Yan; Jian Wang; Samuel Shao-Min Zhang; Shuping Zhang (Molecular Biology Reports, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Alkaline-stress response in Glycine soja leaf identifies specific transcription factors and ABA-mediated signaling factors - Ying Ge; Yong Li; De-Kang Lv; Xi Bai; Wei Ji; Hua Cai; Ao-Xue Wang; Yan-Ming Zhu (Functional & Integrative Genomics, 2011)

Phytoliths in woody plants from the northern slope of the Changbai Mountain (Northeast China), and their implication - Yong Ge; Dong Mei Jie; Yan Lei Sun; Hong Mei Liu (Plant Systematics and Evolution, 2011)

The effect of depression on the thermal nociceptive thresholds in rats with spontaneous pain - Yuan-Lin Su; Ning Wang; Ge Gao; Jin-Yan Wang; Fei Luo (Neuroscience Bulletin, 2010)

Comparative features of colorectal and gastric cancers with microsatellite instability in Chinese patients - Yan-qin Huang; Ying Yuan; Wei-ting Ge; Han-guang Hu; Su-zhan Zhang; Shu Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Detrital zircon and apatite fission track data in the Liaoxi basins: Implication to Meso-Cenozoic thermo-tectonic evolution of the northern margin of the North China Craton - Yi Yan; Xiaoqiong Hu; Ge Lin; Weiliang Liu; Zhengjiang Song (Journal of Earth System Science, 2010)

Effects of pentobarbital anesthesia on nociceptive processing in the medial and lateral pain pathways in rats - Ning Wang; Yang Zhang; Jin-Yan Wang; Ge Gao; Fei Luo (Neuroscience Bulletin, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Overexpression of Trpp5 contributes to cell proliferation and apoptosis probably through involving calcium homeostasis - Yan Xiao; Xiaoyan Lv; Ge Cao; Guohui Bian; Jingjing Duan; Jianzhong Ai; Huan Sun; Qingwei Li; Qiutan Yang; Tielin Chen; Danhua Zhao; Ruizhi Tan; et al. (Molecular and Cellular Biochemistry, 2010)

Microbial community analysis in crab ponds by denaturing gradient gel electrophoresis - Yan Fen Cheng; Qun Lan Zhou; Jun Xie; Xian Ping Ge; Wei-Yun Zhu; Bo Liu (World Journal of Microbiology and Biotechnology, 2010)

Impact of female cigarette smoking on circulating B cells in vivo: the suppressed ICOSLG, TCF3, and VCAM1 gene functional network may inhibit normal cell function - Feng Pan; Tie-Lin Yang; Xiang-Ding Chen; Yuan Chen; Ge Gao; Yao-Zhong Liu; Yu-Fang Pei; Bao-Yong Sha; Yan Jiang; Chao Xu; Robert R. Recker; Hong-Wen Deng (Immunogenetics, 2010)

Polybrominated diphenyl ethers and their methoxylated metabolites in anchovy (Coilia sp.) from the Yangtze River Delta, China - Guan-yong Su; Zi-shen Gao; Yijun Yu; Jia-chun Ge; Si Wei; Jian-fang Feng; Feng-yan Liu; John P. Giesy; Michael H. W. Lam; Hong-xia Yu (Environmental Science and Pollution Research, 2010)

Carbon/nitrogen ratio as a major factor for predicting the effects of organic wastes on soil bacterial communities assessed by DNA-based molecular techniques - Yuan Ge; Chengrong Chen; Zhihong Xu; Simon M. Eldridge; Kwong Yin Chan; Yan He; Ji-Zheng He (Environmental Science and Pollution Research, 2010)

Magnetic cell sorting and flow cytometry sorting methods for the isolation and function analysis of mouse CD4+ CD25+ Treg cells - Hang Yan; Chen-guang Ding; Pu-xun Tian; Guan-qun Ge; Zhan-kui Jin; Li-ning Jia; Xiao-ming Ding; Xiao-ming Pan; Wu-jun Xue (Journal of Zhejiang University-SCIENCE B, 2009)

Denudation history of South China block and sediment supply to northern margin of the South China Sea - Yi Yan; Xiaoqiong Hu; Ge Lin; Bin Xia; Xiaoyong Li; Remesh Chandra Patel (Journal of Earth Science, 2009)

Cloning and functional analysis of wheat V-H+-ATPase subunit genes - Qian Zhao; Yan-Jun Zhao; Bao-Cun Zhao; Rong-Chao Ge; Ming Li; Yin-Zhu Shen; Zhan-Jing Huang (Plant Molecular Biology, 2009)

pH Fluorescent Probes: Chlorinated Fluoresceins - Feng-Yan Ge; Li-Gong Chen (Journal of Fluorescence, 2008)

Autophagy is activated and might protect neurons from degeneration after traumatic brain injury - Yan-Bo Zhang; Sheng-Xing Li; Xi-Ping Chen; Li Yang; Yun-Ge Zhang; Ran Liu; Lu-Yang Tao (Neuroscience Bulletin, 2008)

Production and characterization of intertribal somatic hybrids of Raphanus sativus and Brassica rapa with dye and medicinal plant Isatis indigotica - Yuqin Tu; Jian Sun; Yan Liu; Xianhong Ge; Zhigang Zhao; Xingcheng Yao; Zaiyun Li (Plant Cell Reports, 2008)

The endoplasmic reticulum (ER)-target protein Bik induces Hep3B cells apoptosis by the depletion of the ER Ca2+ stores - Xiaoping Zhao; Li Wang; Yan Sun; Ling Ye; Jian Lu; Yaozong Yuan; Guanxiang Qian; Shengfang Ge (Molecular and Cellular Biochemistry, 2008)

Lipopolysaccharide induces expression of SSeCKS in rat lung microvascular endothelial cell - Chun Cheng; Haiou Liu; Haiyan Ge; Ji Qian; Jing Qin; Linlin Sun; Menling Chen; Meijuan Yan; Aiguo Shen (Molecular and Cellular Biochemistry, 2007)

Isolation and characterization of a novel cDNA encoding ERF/AP2-type transcription factor OsAP25 from Oryza Sativa L. - Xiao-Yan Fu; Zhen Zhang; Ri-He Peng; Ai-Sheng Xiong; Jin-Ge Liu; Li-Juan Wu; Feng Gao; Hong Zhu; Zhao-Kui Guo; Quan-Hong Yao (Biotechnology Letters, 2007)

Optimized Coagulation of High Alkalinity, Low Temperature and Particle Water: pH Adjustment and Polyelectrolytes as Coagulant Aids - Jianfeng Yu; Dongsheng Wang; Mingquan Yan; Changqing Ye; Min Yang; Xiaopeng Ge (Environmental Monitoring and Assessment, 2007)

Correlation Between Antifungal Agent Phenazine-1-Carboxylic Acid and Pyoluteorin Biosynthesis in Pseudomonas sp. M18 - Yi-He Ge; Dong-Li Pei; Yan-Hong Zhao; Wei-Wei Li; Shu-Fang Wang; Yu-Quan Xu (Current Microbiology, 2007)

Association of MTHFR C677T and SHMT1 C1420T with susceptibility to ESCC and GCA in a high incident region of Northern China - Yimin Wang; Wei Guo; Yutong He; Zhifeng Chen; Denggui Wen; Xiufeng Zhang; Na Wang; Yan Li; Hui Ge; Jianhui Zhang (Cancer Causes & Control, 2007)

Screen p53 mutations in hepatocellular carcinoma by FASAY: A novel splicing mutation - Xiao-mo Wu; Jing-geng Fu; Wang-zhong Ge; Jiang-yan Zhu; Jun-yong Wang; Wei Zhang; Wei Qian; Ke-ke Huo (Journal of Zhejiang University-SCIENCE B, 2007)

Improved production of an enzyme that hydrolyses raw yam starch by Penicillium sp. S-22 using fed-batch fermentation - Hai-Yan Sun; Xiang-Yang Ge; Wei-Guo Zhang (Biotechnology Letters, 2006)

Reliable genetic analyses based on formalin-fixed materials: a new noninvasive sampling perspective for the giant panda - Qiu-Hong Wan; Jian-Qiu Yu; Yan-Ge Yong; Sheng-Guo Fang (Conservation Genetics, 2006)

A clinical and molecular-genetic analysis of Chinese patients with lattice corneal dystrophy and novel Thr538Pro mutation in theTGFBI (BIGH3) gene - Ping Yu; Yangshun Gu; Yuehong Yang; Xiaoyi Yan; Liu Chen; Zhen Ge; Ming Qi; Jianmin Si; Lei Guo (Journal of Genetics, 2006)

New Fluorescent Labels: 4- and 7-Chlorofluorescein - Feng-Yan Ge; Xi-Long Yan; Fan-Yong Yan; Hui-Ying Pan; Li-Gong Chen (Journal of Fluorescence, 2005)

Lipoprotein lipase gene is in linkage with blood pressure phenotypes in Chinese pedigrees - Wenjie Yang; Jianfeng Huang; Dongliang Ge; Cailiang Yao; Xiufang Duan; Yan Shen; Boqin Qiang; Dongfeng Gu (Human Genetics, 2004)

Analysis of Expression of the Binary Toxin Genes from Bacillus sphaericus in Anabaena and the Potential in Mosquito Control - Xudong Xu; Ge Yan; Renqiu Kong; Xiangping Liu; Lihong Yu (Current Microbiology, 2000)

Significant enhancement of lipase enantioselectivity toward (S)- Ketoprofen ester at pH 2 - You-Yan Liu; Jian-He Xu; Qiu-Ge Xu; Ying Hu (Biotechnology Letters, 1999)